Myth-Making: On-going Impacts of Historical Education Policy on Beliefs About Māori in Education - Hetaraka, Maia (New Zealand Journal of Educational Studies, 2022)
The history of educational policy-making in Aotearoa New Zealand is also a history in myth-making. Myths about Māori in education are deeply embedded in educational and social thought, because they have their origins in the first political interactions between Māori and Pākeha. These interactions were motivated by contradicting forces—Māori determination to participate in the changing economic and technological landscape, contrasted against British perceptions of their own cultural superiority and inherent right to rule indigenous populations. British superiority was enshrined in aggressive and racist laws that disenfranchised and dispossessed Māori of lands, resources, economies, and attempted to de-culturalise Māori. Laws were in turn translated to policy and practice that reinforced deep seeded myths that have negatively positioned Māori socially, politically and educationally. As Aotearoa New Zealand education progresses toward a commitment to teach our dual and difficult histories, it is necessary to also expose and analyse the ways negative positioning of Māori has been purposefully built into our education system. Understanding how political histories have influenced our education system may better equip education professionals to identify and question their own conscious and unconscious biases, and to challenge and change a system that has its origins racist philosophy, reinforced by policy. Education professionals who are able to deconstruct carefully fortified, damaging myth-making about Māori will be well positioned to lead authentic movement toward a shared future.

Tino rangatiratanga in post-treaty settlement Aotearoa: Challenges of co-governance, and evolving treaty partners - Erueti, Andrew (PUBLIC LAW REVIEW, 2025)
This article considers the puzzle of the location of tino rangatiratanga in the post-Treaty settlements era in the context of current controversy in New Zealand over recognising Maori self-determination or tino rangatiratanga as guaranteed by Art 2 of the Treaty of Waitangi. On one level, the current political and legal struggles reflect a fundamental tension between Maori aspirations for tino rangatiratanga and the state's desire to maintain centralised sovereignty. At a deeper level, the government opposition to co-governance stems from questions about the evolving role of the Treaty - in particular the guarantee of tino rangatiratanga and its ability to apply to a much wider range of Treaty issues (other than natural resources) and Treaty partners; for example, non-tribal Maori collectives serving urban Maori and not bound like tribes by kinship ties. The Waitangi Tribunal, originally established to facilitate Treaty settlements, is now at the centre of this shift in thinking to expand the interpretation of tino rangatiratanga. In a recent series of reports, the Tribunal has recognised the diversity of Maori identity and the legitimacy of non-tribal collectives as Treaty partners, particularly when these organisations are created by and responsive to the socio-economic needs of Maori. The proliferation of Treaty partners thus raises issues of co-ordination and coherence - how do these many partners engage effectively with the Crown and is every Maori organisation a Treaty partner for the purposes of Art 2 tino rangatiratanga? And does provision of social services by these Treaty partners violate the right to equality?
Keywords: Decision making–Evaluation; Equality; Māori (New Zealand people)–Civil rights; Race discrimination; Reparation (Criminal justice); Sovereignty; Treaty of Waitangi

Co-governance Design and Implementation: Lessons from Norman v Tūpuna Maunga o Tāmaki Makaurau Authority - Houghton, Jayden (New Zealand Universities Law Review, 2024)
Norman v Tūpuna Maunga o Tāmaki Makaurau Authority is a judicial review of the Tūpuna Maunga o Tāmaki Makaurau Authority's decision to fell and remove all the exotic (non-native) trees on Ōwairaka/Mt Albert. Whilst the High Court dismissed the review and allowed the operation to proceed, that decision was overturned by the Court ofAppeal because the Maunga Authority failed to consult in accordance with statutory requirements. The Norman litigation has implications and lessons for all co-governance arrangements in Aotearoa New Zealand. This article argues that whilst the relevant Treaty of Waitangi settlement legislation allows for meaningful power-sharing within the Maunga Authority, and the co-governance partners sought to meaningfully share power, the Maunga Authority could have done more to consult and act in good faith. It also contends that tikanga Māori gives rise to a duty to consult and ought to be contemplated by counsel as a basis for a duty to consult in the future.
Keywords: Actions & defenses (Law); Courts; Judicial review; Trees

Tino Rangatiratanga and Mana Motuhake: Nation, state and self-determination in Aotearoa New Zealand - Paora, Ropata; Tuiono, Teanau; Flavell, Te Ururoa; Hawksley, Charles; Howson, Richard (AlterNative: An International Journal of Indigenous Peoples, 2011)
This article brings perspectives from three Māori activists, each promoting issues of self-determination in different ways. It centres on tino rangatiratanga and mana motuhake, two concepts that inform modern Māori activism and life and practice, and more recently conceptions of Māoridom as “nation”. Using a Gramscian framework we argue that the New Zealand state has over time created a notion of one people within one state, and has in the past incorporated challenges to its legitimacy within a framework of popular consent. The desire by some Māori activists for self-determination promotes a separateness that to some extent challenges this idea of nation–state unity. An examination of these modern Māori activist politics allows us to observe the operations of hegemony as it forms and reforms in modern New Zealand.

The Treaty and “Treating” Māori Health: Politics, policy and partnership - Whitinui, Paul (AlterNative: An International Journal of Indigenous Peoples, 2011)
This paper will argue that the Treaty of Waitangi, signed on 6 February 1840 by Māori and the Crown, has a made significant contribution to informing and advancing Māori health practices in Aotearoa New Zealand. A key focus of this paper relates to (re)validating the Treaty to improve Māori health outcomes and providing a strategy for evaluating the current health status of Māori. There is a growing concern among Māori that the health sector continues to perpetuate notions of ?treating? Māori health more so than empowering M?ori to control their own processes for being healthy. Moreover, a major shift constitutionally (that is, self-determining the right to be healthy) as well as institutionally (that is, developing approaches to greater access to health provision) is required to enable Māori to achieve better health outcomes moving forward. Finally, a number of important culturally innovative, responsive and inclusive perspectives are shared to enhance our engagement with the Treaty and Māori health from a socio-cultural perspective.

Becoming whānau: Māori and Pākehā working together on the Indigenous-led campaign,# ProtectIhumātao - Hancock, Frances; Newton, Pania (Ethnicities, 2022)

The case of ihumatao: Interrogating competing corporate and indigenous visions of the future - Hancock, Frances; Lee-Morgan, Jenny; Newton, Pania; McCreanor, Tim (New Zealand Sociology, 2020)

"We don't have time for that carry-on anymore" – Protest and the construction of space at Waitangi in the 1980s - Schmidt, Tyson (Architectural History Aotearoa, 2009)
The 6th of February is New Zealand's annual day of cultural performance par excellence. It is not a rememberance and reflection of what is undoubtedly this country's most important historical moment, but instead an enactment of contemporary understandings of the Treaty of Waitangi by both Māori and the Crown. Architecturally this performance is played out at, and between, Te Tii marae and the Treaty grounds at Waitangi. The partnership between Māori and the Crown is spatially expressed each year by symbolically important rituals being conducted and protocols observed at each specific site. People gather, welcomes occur, addresses are given, entertainment provided, bridges crossed, debates take place, demands are made, and protests held. The actions of the various parties are frequently beamed into households by the television networks and reported in the national newspapers, leading to a national construction of space that represents current perceptions of cultural and race relations. The 1980s saw a significant shift in the construction of Waitangi as space. Following the rise of the land rights movement in the 1960s and 1970s, Māori activists focussed their efforts on Waitangi and Waitangi Day more than ever before. The government responded by denying access to the Treaty grounds, then retreating from Waitangi celebrations, and then eventually returning by the end of the decade. Waitangi as space became a pawn in a political contest, and its place in the national psyche moved with each action and counter-action.
Keywords: Biculturalism—New Zealand; Demonstrations; Discrimination; Te Tiriti o Waitangi (Aotearoa); The Treaty of Waitangi (New Zealand); Waitangi Day (New Zealand)

Māori Sovereignty or Death - Rata, Arama; Brayne, Gabriella; Barber, Simon (Decolonization of Criminology and Justice, 2023)
In her 1984 book ‘Māori Sovereignty’, Donna Awatere sustains a blistering polemic on ‘white culture’ that still retains its rhetorical force 40 years later. Her construction of a sharply delineated binary between a monolithic notion of ‘white culture’ as against ‘taha Māori’ can come at the cost of simplification. But this is not at all to say that Awatere is wrong when she says it is ‘Māori Sovereignty or death’. In this paper, we extend Awatere’s work by analysing relationships between colonialism and capital. We begin by situating Awatere’s work in its historical context, outlining major shifts in the global political economy, and drawing on Awatere’s analysis of Fascism to account for contemporary Far Right movements. Building from the inextricability of Fascism from the settler colonial/imperialist economy, we explore Awatere’s framing of whiteness as a system of racial exploitation and violence that enforces the state’s genocidal claims to sovereignty, defined through necropower – capitalism’s consumption of racialised death. We then consider the contradictions between capitalism and constitutional transformation. By scanning revolutionary movements elsewhere (in particular the Chilean movement for plurinationalism), we identify the need for extra-parliamentary, broad-based, popular power and constituent authority from below, as well as Indigenous solidarities and international alliances to circumvent anti-Māori populism and confront capital. In reflecting on the power of death, and the need for counter-hegemonic culture capable of securing the transition out of capitalism, we are drawn to the revolutionary essence of whakapapa as an Indigenous ontology that eternally resists necropower.

Whakapapa of a Prison Riot: Prison Censorship, Free Speech, and the Fight against Fascism - Rakete, Emmy; Lamusse, Ti (2024)
Starting with the whakapapa of the Waikeria Prison Uprising in 2020/21, this article examines what the suppression of prisoners’ freedom of speech tells us about the struggle to defeat the far right. Drawing on the authors’ personal experience of censorship at the hands of the Crown, the article demonstrates the futility of relying on the capitalist state to achieve the liberation of exploited and oppressed people. The article critiques liberal ‘safetyism’ as a demobilising force, which prioritises fear for personal safety over the necessity of struggle. In contrast, the authors argue that it is only through mass struggle that we can defeat the far right and liberate ourselves.

Ram raiding the colony: Māori youth crime in capitalist ideology - Rākete, Emmy; Cox, Kendra (2025)
The 2023 New Zealand general election was marked by media narratives about a youth crime crisis, with special emphasis placed on ram raids and the Māori children and young people blamed for perpetrating them. We show that empirical data do not support the claim that youth crime is surging, and argue that fears of ram raids tap into longstanding beliefs about Māori. Using archival sources from the era of early European settlement in Aotearoa, we show that Pākehā settlers constructed Māori children and young people as uniquely dangerous delinquents. Using Louis Althusser’s theory of ideology and subjectivation, we argue that this delinquentisation played a key role in constituting a colonial ideology that would justify primitive accumulation, colonisation, and the imposition of the capitalist mode of production in Aotearoa. Looking to the contemporary neoliberal era, we argue that moral panics about ram raids continue this colonial ideology of delinquentisation. By subjectivating children and young people as delinquents, the capitalist class is able to use the criminal justice system to displace responsibility for the crisis of social reproduction precipitated by neoliberal economic policy. We conclude by showing the limitations of this strategy and arguing for intensified struggle against the ideology of delinquentisation.

Settler/Invader Identity and Belonging in Aotearoa New Zealand: Critiquing “Tāngata Tiriti” and Moving Toward the Collective Future - Simon, Hemopereki (Ethnic Studies Review, 2023)
This Kaupapa Māori writing inquiry explores “Tāngata Tiriti” (People of the Treaty) as a settler/invader identity term in Aotearoa New Zealand. Derived from the failed policy platform of “biculturalism” and “Indigenous inclusion,” Tāngata Tiriti is a byproduct of neoliberalism and settler/invader colonialism that fails to provide for Indigenous inclusion, mana motuhake (Indigenous sovereignty) and tino rangatiratanga (self-determination). This article argues that Tāngata Tiriti should be abandoned due to the 2014 paradigm shift surrounding Te Tiriti o Waitangi (Te Tiriti) and mana motuhake from the Te Paparahi o Te Raki report and the author’s subsequent research on non-signatory hapū and iwi. Pākehā settler/invader perspectives on Tāngata Tiriti are compared with Tāngata Moana and Asian scholarly understandings. The author advocates adopting Tāngata Moana thinking around letting Māori as mana whenua lead “wayfinding” and “meaning-making” to define allyship and promote a “collective future” together based on Māori constitutional values that are generally universal throughout Pacific cultures. Instead of settler/invader identity constructs and the doctrine of the nation as a White possession, movement toward a collective future must begin from a place of sovereign relationality. The pedagogy of teaching Te Tiriti must change, the ill-conceived Tāngata Tiriti identity must be abandoned, and “New Zealand” as a settler/invader colonial enterprise must end. Our future must be post-settler/invader colonial and post-Tiriti and must recognize unceded mana motuhake or sovereignty.

Decolonising Ethics : considerations of power, politics and privilege in Aotearoa/New Zealand - Boulton, Amohia (Southern African Journal of Social Work and Social Development, 2018)
Indigenous peoples across the world have a shared experience of colonisation; a process that has resulted in war, disease and the decimation of their lands, homes and peoples. In New Zealand, the effects of colonisation are still evident with Māori (the indigenous people of New Zealand) experiencing poorer outcomes compared with non-Māori citizens across a range of social, health and well-being indicators. This paper is a case study of work being done in New Zealand, which may have resonance with work in South Africa, and other countries with a history of colonisation. It begins with a brief history of the impacts of colonisation on Māori before considering the concept of decolonisation. The author outlines the work her organisation does as an independent, tribally owned, Māori health research centre to advance a decolonisation agenda. Reflecting on their emancipatory and democratising ambitions as researchers provides the opening for a discussion about indigenous ethics. The paper presents a number of Māori ethical principles that guide their work, arguing that were such principles applied in the development and implementation of social policy and legislation, the effect would be a fairer, more equitable policy that better meets the needs of Māori as citizens. Recent legislation enacted to improve New Zealand’s care and protection system for children is discussed to illustrate the need for greater consideration of Māori values when developing legislation that directly impacts Māori. The paper concludes with a challenge to policymakers, practitioners, academics, and researchers alike to actively contribute to an agenda of liberation, emancipation and decolonisation for indigenous peoples.
Keywords: Care and protection; Care ethics; Decolonisation; Indigenous ethics; Māori; Self-Determination

Māori and Pasifika leaders’ experiences of government health advisory groups in New Zealand - Came, Heather; McCreanor, Tim; Haenga-Collins, Maria; Cornes, Rhonda (Kōtuitui: New Zealand Journal of Social Sciences Online, 2019)
Māori and Pasifika populations in New Zealand experience poorer health outcomes than other New Zealanders. These inequalities are a deeply entrenched injustice. This qualitative study explores the experiences of six Māori and Pasifika leaders on health policy-making advisory committees. All had extensive experience in the health system. They were recruited, provided semi-structured interviews, the data coded, and a thematic analysis undertaken. Our findings show that inequalities in the health system are reproduced in advisory committees. Participants noted their knowledge and interests were devalued and they experienced racism and tokenistic engagement. Some indicated it took considerable effort to establish credibility, be heard, have impact, and navigate advisory meetings, but even then their inputs were marginalised. Health policy advisory committees need deeper engagement and more genuine recognition of Māori and Pasifika knowledge. Māori and Pasifika leaders have constructive solutions for eliminating health inequities that could benefit all New Zealanders.
Keywords: Māori; New Zealand; Pasifika; health policy; racism

Māori Issues - Mutu, Margaret (The Contemporary Pacific, 2023)

Conceptualising Indigenous Rights in Aotearoa New Zealand - Erueti, Andrew (New Zealand Universities Law Review, 2017)
Examines ‘significant’ reforms implemented in NZ over the past 30 years to recognise the rights of Māori as an indigenous people. Overviews the conceptual basis for settlements lodged under the Treaty of Waitangi, legal claims by Māori to natural resources and other reforms. Identifies a lack of measures that recognise Māori political authority, and asserts that successive governments have deliberately discounted the normative value of ‘historical conceptual categories’, instead choosing to emphasise categories that deliver lesser substantive rights.

Indigenous Peoples Rights under International Law - Adcock, Fleur; Charters, Claire (The New Zealand Yearbook of International Law, 2009)
In 2009 international legal negotiations of particular relevance to Indigenous peoples continued under the United Nations (UN) Framework Convention on Climate Change (UNFCCC); the Convention on Biodiversity (CBD); and the auspices of the World Intellectual Property Office (WIPO). As in previous years, international human rights monitoring bodies developed jurisprudence on the rights of Indigenous peoples, contributing to the development of customary international law in the field. New Zealand was the subject of the UN Human Rights Council's (HRC) universal periodic review (UPR) process for the first time in 2009. The HRC focused on Maori and their rights during the UPR with calls for New Zealand to support the UN General Assembly's Declaration on the Rights of Indigenous Peoples (Indigenous Peoples' Declaration) and to consider constitutional entrenchment of international human rights instruments and the Treaty of Waitangi.New Zealand's reluctance to recognise Indigenous peoples' rights persisted in 2009. New Zealand did not endorse the Indigenous Peoples' Declaration and Indigenous peoples' rights did not feature prominently in New Zealand's statements in international fora.
Keywords: Indigenous peoples–Civil rights; Indigenous peoples–Legal status; laws; etc.; International law

Indigenous Peoples Rights under International Law - Charters, Claire (The New Zealand Yearbook of International Law, 2008)
The developments that have taken place in New Zealand in relation to Indigenous Peoples rights under International law are discussed. Details of different committees formed and laws enacted to ensure and protect the same are highlighted.
Keywords: Indigenous peoples–Civil rights; Indigenous peoples–Legal status; laws; etc.; International law; New Zealand

Indigenous Peoples Rights under International Law - Charters, Claire (The New Zealand Yearbook of International Law, 2007)
2007 was a significant year for Indigenous peoples and international law. The United Nations (UN) General Assembly adopted the Declaration on the Rights of Indigenous Peoples (the Declaration on Indigenous Peoples), after more than 20 years of negotiations, and the Human Rights Council established the Expert Mechanism on the Rights of Indigenous Peoples (the EMRIP). Further, the World Intellectual Property Office (WIPO) continued its work on traditional knowledge, as did the working groups associated with the Convention on Biodiversity (CBD). Indigenous issues were considered in institutions such as the World Health Organisation (WHO) and, of course, the Permanent Forum on Indigenous Issues. New Zealand was also the subject of review by the UN Committees on the Elimination of Racial Discrimination (CERD Committee) and the Elimination of Discrimination Against Women (CEDAW Committee) on its compliance with its human rights obligations, some of which raised issues involving Maori. This review details New Zealand's state practice in these institutions.
Keywords: Human rights; Indigenous peoples (International law); Indigenous peoples–Civil rights; Indigenous peoples–Legal status; laws; etc.; New Zealand

Indigenous peoples' rights under international law - Te Aho, Fleur (The New Zealand Yearbook of International Law, 2015)
This note reviews New Zealand's state practice regarding Indigenous peoples' rights under international law in 2015 and traces key international developments concerning those rights. In 2015 New Zealand demonstrated support for efforts to improve Indigenous participation in the United Nations (UN) and extend the mandate of the UN Expert Mechanism on the Rights of Indigenous Peoples (EMRIP) to advance implementation of the UN Declaration on the Rights of Indigenous Peoples (UNDRIP). But it indicated that - domestically - the UNDRIP would be implemented within existing legal and constitutional arrangements. There were several noteworthy developments regarding Indigenous peoples' rights during the year. Indigenous peoples and their rights received limited reference in the 2030 Agenda for Sustainable Development agreed by the UN General Assembly (GA) and in the Paris Agreement negotiated under the auspices of the UN Framework Convention on Climate Change (UNFCCC). Nationally, draft bills proposing significant changes to the law governing Māori land and te reo Maori (the Maori language) were released, which will contribute to growing jurisprudence in these areas. In November the text of the Trans-Pacific Partnership (TPP) was made public, which includes an exception clause on the Treaty of Waitangi (Treaty). The UN Committee against Torture (CAT) and the UN Working Group on Arbitrary Detention (WGAD) commented on the human rights situation of Māori. The GA, the UN Human Rights Council (HRC), international human rights treaty monitoring bodies and others also devoted attention to Indigenous peoples' rights in the course of their work.
Keywords: Children's rights; Maori (New Zealand people)–Criminal justice system; New Zealand; Permanent Forum on Indigenous Issues (United Nations); United Nations. Human Rights Committee

Extractive industry, human rights and indigenous rights in New Zealand's exclusive economic zone - Erueti, Andrew; Pietras, Joshua (The New Zealand Yearbook of International Law, 2020)
This article is a response to the recent surge of interest over extractive industry in New Zealand and the opposition to this by many iwi. The New Zealand government has in recent years made offshore exploration and production a high priority. By the extractive industry, we mean the people, companies, and activities involved in removing oil and gas, metals, coal, stone and other useful resources from the ground.
Keywords: Aboriginal Australians–Civil rights; Discoveries in geography–Environmental aspects; Dispute resolution (Law); Economic zones (Law of the sea); Mineral industries–Economic aspects; Mineral industries–Government policy; New Zealand

New Zealand's ‘Maori foreign policy’ and China: a case of instrumental relationality? - Smith, Nicholas Ross; Holster, Bonnie (International Affairs, 2023)
In 2021, Aotearoa New Zealand's Foreign Minister, Nanaia Mahuta, sketched out a kaupapa Māori (collective Māori vision) foreign policy for New Zealand based on four tikanga Māori (Māori customary practices and behaviours): manaakitanga (hospitality), whanaungatanga (connectedness), mahi tahi and kotahitanga (unity through collaboration), and kaitiakitanga (guardianship and the protection of intergenerational wellbeing). This article makes a novel contribution to the global International Relations body of literature by questioning to what extent New Zealand's ‘Māori foreign policy’ has been applied to its relationship with China. Through assessing the communications of Mahuta and other officials, it is found that New Zealand is utilizing a kaupapa Māori framework towards China: ‘the taniwha and the dragon’. It is argued that New Zealand is attempting to consolidate the maturity of the Sino-New Zealand relationship, as well as differentiate itself from the other Anglosphere countries that have recently pushed back on China. In doing so, not only is New Zealand something of an outlier, it is demonstrating how eschewing a western-centric understanding of foreign policy for a more relational view based on indigenous knowledge and perspectives (in this case, from te ao Māori: the Māori worldview) can be applied at a time of increasing great power competition.

The Maori Electoral Option Campaign: Problems of Measuring 'Success' - Comrie, Margie; Gillies, Annemarie; Day, Mary (Political Science, 2002)

Māori Electoral Participation - Fitzgerald, Eljon; Stevenson, Brendan; Tapiata, Jacob (A Report Produced for the Electoral Commission by the Best Outcomes for Māori: Te Hoe Nuku Roa Group. http://www. elections. org. nz/research-statistics/research/participation-research, 2007)

Mana wahine: Decolonising gender in Aotearoa - Pihama, Leonie (Australian feminist studies, 2020)

Ngā Kāmiti wahine: theorising the politicisation of Māori women in the late nineteenth century - Rangiheuea, Tania (2002)

It's quite simple really - Jackson, Moana (Yearbook of New Zealand Jurisprudence, 2007)

Tikanga as the First Law of New Zealand: An Important Cognitive Shift - Fox, Caren (Amicus Curiae, 2022)

Tikanga as the first law of Aotearoa - Mikaere, Ani (Yearbook of New Zealand Jurisprudence, 2007)

Cultural invasion continued: The ongoing colonisation of Tikanga Maori - Mikaere, Ani (Yearbook of New Zealand Jurisprudence, 2005)

'Maranga Ake Ai' the Heroics of Constitutionalising Te Tiriti O Waitangi/the Treaty of Waitangi in Aotearoa New Zealand - Ruru, Jacinta; Kohu-Morris, Jacobi (Federal Law Review, 2020)

The Land Remains: Māori youth and the politics of belonging - Kidman, Joanna (AlterNative: An International Journal of Indigenous Peoples, 2012)
This paper extends recent work in the geography of youth and childhood with an exploration of the ways that indigenous Māori teenagers who have grown up in regional tribal environments deploy land narratives as they construct a range of fluid socio-spatial cultural identities. The discussion is based on the findings of a multi-tribal study undertaken in the aftermath of government legislation that had led to widespread Māori political protest. Data generated in the course of the study took the form of digital photographs taken by the participants coupled with their explanations about the images. It is argued that Māori young people who are immersed in these environments draw on an extensive repertoire of tropes about the land which in turn influences a territorialized politics of belonging. These politics of belonging become particularly evident during periods of heightened political tension between indigenous peoples and the Crown.

The double trusteeship of Te Tiriti o Waitangi: Pā to Plate and the sixth Labour government - Kawharu, Merata; Tapsell, Paul (Political Science, 2025)

Local Maori development and government policies - Kawharu, Merata (Social Policy Journal of New Zealand, 2001)

Mana wahine: Decolonising politics - Simmonds, Naomi (Women's studies Journal, 2011)

Technically political: The post-politics (?) of the New Zealand emissions trading scheme - Driver, Elizabeth; Parsons, Meg; Fisher, Karen (Geoforum, 2018)

Indigenous climate justice in Aotearoa New Zealand: the dangers of (mis) recognition within climate policymaking - Parsons, Meg; Crease, Roa Petra (Inland Waters, 2024)

River co-governance and co-management in Aotearoa New Zealand: enabling Indigenous ways of knowing and being - Fisher, Karen; Parsons, Meg (Transnational Environmental Law, 2020)

The key actors of Waikato River co-governance: situational analysis at work - Muru-Lanning, Marama (AlterNative: An International Journal of Indigenous Peoples, 2012)

Maori election petitions of the 1870s: Microcosms of dynamic Maori and Pakeha political forces - Warbrick, Paerau (Journal of New Zealand Studies, 2021)
Maori election petitions to the 1876 Eastern Maori and the 1879 Northern Maori elections were high-stakes political manoeuvres. The outcomes of such challenges were significant in the weighting of political power in Wellington. This was a time in New Zealand politics well before the formation of political parties. Political alignments were defined by a mixture of individual charismatic men with a smattering of provincial sympathies and individual and group economic interests. Larger-than-life Maori and Pakeha political characters were involved in the election petitions, providing a window not only into the complex Maori political relationships involved, but also into the stormy Pakeha political world of the 1870s. And this is the great lesson about election petitions. They involve raw politics, with all the political theatre and power play, which have as much significance in today's politics as they did in the past. Election petitions are much more than legal challenges to electoral races. There are personalities involved, and ideological stances between the contesting individuals and groups that back those individuals. Maori had to navigate both the Pakeha realm of central and provincial politics as well as the realm of Maori kin-group politics at the whanau, hapu and iwi levels of Maoridom. The political complexities of these 1870s Maori election petitions were but a microcosm of dynamic Maori and Pakeha political forces in New Zealand society at the time.
Keywords: Elections–Political aspects; Elections–Social aspects; History–Influence; Maori (New Zealand people)–Legal status; laws; etc.; New Zealand; Political parties

E-Whanaungatanga: The role of social media in Māori political empowerment - Waitoa, Joanne; Scheyvens, Regina; Warren, Te Rina (AlterNative: An International Journal of Indigenous Peoples, 2015)
Lower voter turnout and lack of political empowerment sees Māori engaging less than Pākehā (European New Zealanders) with the political system to the detriment of Māori development. This paper explores the potential of social media to enhance Māori development via political engagement. Mana Party Facebook pages are used as a case study to investigate if social media can encourage Māori political awareness and participation. Results found that social media has both positive and negative implications for political engagement and indigenous development. While social media aligns with tikanga Māori (values/customs) through tino rangatiratanga (self-determination) and whanaungatanga (relationships/networks), other aspects such as cultural misappropriation conflict with Māori values. The paper explores tensions in the use of social media for political engagement among indigenous peoples and offers a framework promoting e-whanaungatanga to illustrate how they might use social media in a way that emphasizes the positive and mitigates the negative aspects of the platform.

Rangatahi Maori climate action: A dialogue with nature-based solutions - Te One, Annie; Menzies, Diane; Pooley, Brittany; Logan-Riley, India (Nature-Based Solutions, 2024)
This article explores the broad area of rangatahi Māori climate activism. As a research team made up of academics, rangatahi and rangatahi Māori activists, this perspective piece discusses the importance of whakapapa, belonging and connections to the environment as a foreground to climate activism. While we highlight the lack of academic research focussed on rangatahi Māori climate activism, we show that there is a plethora of activity happening through digital and social media which provides a rich space for sharing innovative ideas for a just future in which nature is centered. We suggest that there are many commonalities between the current articulations of Nature-Based Solutions and rangatahi Māori activism and that greater dialogue between these spaces is vital for any solutions being offered for an environmentally just future for Aotearoa.
Keywords: Activism; Climate change; Digital media; Environment; Mātauranga; Rangatahi

Tikanga and New Zealand political parties—heading in the “right” direction? case study—2020 General Election - Te One, Annie; Caird, Clair (AlterNative, 2024)
This article examines references to tikanga Māori (Māori (the Indigenous Peoples of New Zealand) values) by New Zealand political parties. The article grounds itself in some of the wider debates relating to the incorporation and application of tikanga, Māori values, across New Zealand in both legal and political contexts, with particular review of legislative references. An analysis of New Zealand political party policies and constitutions from the 2020 General election showed that over half of the political parties who campaigned made some reference to tikanga, but there was great variation in how tikanga was interpreted. This article assesses some of the opportunities and complexities of New Zealand political party engagement with tikanga Māori.
Keywords: Election; Political Parties; Tikanga; Voting; Parties; Parliament

It's Not about Race, It's about Rights - Sullivan, Ann; Toki, Valmaine (Studies in Law, Politics, and Society, 2012)
Keywords: Local Government; Representation; Treaty of Waitangi

Public sector reform and indigenous entrepreneurship - Sullivan, Ann; Margaritis, Dimitri (International Journal of Entrepreneurial Behavior & Research, 2000)
This paper considers the implications of the liberalization of the New Zealand economy for entrepreneurial development by indigenous New Zealand Maori tribal organizations. Since 1984 the economic objective of the State has been to create a modern market economy free of price distortions, bureaucratic management and government protectionism. One of the State’s responses to enabling tribal organizations to provide for increased self‐determination and to lessen Maori State dependency was to seriously address the issue of compensation to Maori of resources that had been expropriated or confiscated during the past 150 years. While there have been difficulties in reaching agreement on appropriate or adequate allocations of Crown‐owned resources or compensation, the transferal of resources to private (but collective) Maori ownership is now providing a substantial economic base to build corporate and other entrepreneurial activities. It is argued that such willingness and commitment to transfer resources from the State back to the original owners was a manifest outcome of government’s adoption of liberal economic policies.
Keywords: Economics; Policy; Settlements

The politics of reconciliation in New Zealand - Sullivan, Ann (Political Science, 2016)
Reconciliation in New Zealand involves recognition, reparations and an apology for past injustices relating to breaches of the Treaty of Waitangi. In 1840, Māori and the British Crown signed a treaty that promised a beneficial relationship to both signatories. Almost immediately after the Treaty was signed and continuing through to today, promises inherent in the principles of the Treaty have been breached. However, in 1975, a government-appointed permanent commission of inquiry was established to investigate actions or omissions of the Crown that breach the promises made in the Treaty of Waitangi. The Waitangi Tribunal and the Ministry of Justice provide the institutional mechanisms used in New Zealand to foster reconciliation. This article will discuss how the state has moved iwi from being in Treaty ‘grievance mode’ to one of tino rangatiratanga/Māori self-determination and demonstrates how reconciliation has integrated Treaty settlement iwi into the mainstream New Zealand economy.
Keywords: Indigenous rights; Māori; politics; reconciliation; treaty

The Maori Party and the Media: Representations in Mainstream Print Leading to the 2005 Election - Sullivan, Ann (Pacific Journalism Review, 2008)
This article investigates the 2005 pre-election print media coverage of the Maori Party and its candidates. It shows that while the reporters and journalists generally represented the Maori Party in a fair and unbiased manner, at times their reporting was undermined by unbalanced or biased editing or subediting.
Keywords: Elections–Press coverage; Journalism–Political aspects; Mass media–Political aspects; New Zealand; Press and politics

Barriers to and opportunities for the restoration of mana in emergency management legislation and its implementation for Māori - Reid, John; Awatere, Shaun; Rout, Matthew; Campbell, Emily; Huang, Annie; Warmenhoven, Tui (Disasters, 2025)
Ever since colonisation by the British in 1840, Māori, the indigenous peoples of Aotearoa New Zealand, have been fighting to reclaim their mana (authority and influence) over their whenua (land). They were set to regain mana in emergency management (EM) through a parliamentary Bill, but a recent change of government has seen this legislation discharged. This paper explores the barriers to and the opportunities for gains in authority and influence in EM, with authority understood as representation on the national and regional EM bodies, and influence as incorporation of the Māori worldview into legislation and supporting EM implementation documentation. The study applies these different levels of analysis to two case studies to examine any EM-related changes between the Christchurch earthquake in February 2011 and the arrival of Cyclone Gabrielle in February 2023. The paper offers several strategies at both analytical levels that Māori could use to further their mana under the current government.
Keywords: Aotearoa; Māori; New Zealand; disaster risk reduction; emergency management; legislation

Maori Prophetic Movements as Sites of Political Resistance: A Critical Analysis - Rangiwai, Byron (Te Kaharoa, 2017)
This article will argue that Māori prophetic movements were sites of political resistance where Māori prophets resisted colonisation and developed syncretic theologies that gave their followers a sense of hope within a tumultuous colonial environment. The movements of four Māori prophets will be discussed in chronological order: Te Atua Wera and the Nākahi movement; Te Ua Haumēne and the Pai Mārire or Hauhau movement; Te Kooti’s Ringatū movement; and Rua Kēnana and the Iharaira movement. This article will critically analyse these Māori prophetic movements as sites of religious and political resistance to show how Māori prophets challenged colonisation and land loss.

A critical review of the Cabinet Circular on Te Tiriti o Waitangi and the Treaty of Waitangi advice to ministers - O’Sullivan, Dominic; Came, Heather; McCreanor, Tim; Kidd, Jacquie (Ethnicities, 2021)
The New Zealand state developed from a treaty between the British Crown and hapū (sub-tribes) in 1840. The te Reo (Māori language) text and the English version of the agreement are fundamentally different. Breaches of this treaty and tension over how the political relationship between Māori and the Crown should proceed are ongoing. In 2019, the Cabinet Office issued a Circular instructing bureaucratic advisers of the questions they should address when providing advice to ministers on the agreement’s contemporary application. In this article, we use Critical Tiriti Analysis (CTA) – an analytical framework applied to public policies – to suggest additional and alternative questions to inform bureaucratic advice. The article defines CTA in detail and shows how using it in this way could protect Māori rights to tino rangatiratanga (a sovereignty and authority that is not subservient to others) and substantive engagement, as citizens, in the formation of public policy. This article’s central argument is that the Circular reflects an important evolution in government policy thought. However, in showing how the Circular privileges the English version (the Treaty of Waitangi) over the Māori text (Te Tiriti o Waitangi), the article demonstrates how Māori political authority remains subservient to the Crown in ways that Te Tiriti did not intend. We show through the conceptual illustration of the care and protection of Māori children, despite the significant evolution in government thought that it represents, these rights are not fully protected by the Circular. This is significant because it was Te Tiriti, with its protection of extant Māori authority and sovereignty, that was signed by all but 39 of the more than 500 chiefs who agreed to the British Crown establishing government over their own people, but who did not agree to the colonial relationship which may be read into the English version.
Keywords: Cabinet; Critical Tiriti Analysis; Public Policy; Self-Determintation; Te Tiriti o Waitangi; Treaty of Waitangi

Critical Tiriti Analysis: A prospective policy making tool from Aotearoa New Zealand - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Tim (Ethnicities, 2023)
Restrictions on Indigenous peoples’ contributions to policymaking pervade post-settler societies like Australia, Canada and Aotearoa. Such effects are observed in spite of agreements like Te Tiriti o Waitangi in Aotearoa and the United Nations’ Declaration on the Rights of Indigenous Peoples. Te Tiriti, negotiated between the British Crown and Māori (Indigenous peoples of Aotearoa), may have been entered into honourably by both parties, but the Crown has consistently resisted its implementation. Contemporary colonialism is characterised by the entrenched and on-going displacement of Indigenous people’s authority by settler states, rationalised by race as a determinant of human worth. Impacts include land alienation, unsustainable resource exploitation and marginalising Indigenous voices from opportunities to make policy consistent with Indigenous values and preferred ways of living. Colonialism normalises institutional racism so that public policy outcomes are persistently unjust. This article describes Critical Tiriti Analysis (CTA), an original contribution to transforming colonial policy, which retrospectively evaluates whether any specific policy document is consistent with Te Tiriti. Substantial interest in CTA from policymakers, practitioners, and scholars led to the development of the tool as a prospective guide to making policy that is consistent with authoritative interpretations of Te Tiriti, and therefore, more likely effective in producing public policies which eliminate inequities. CTA was initially focused on health policy and built on a series of questions that arise from our interpretations of the text of Te Tiriti, contemporary Tiriti scholarship and jurisprudence, and our observations of the ways in which the method is being used by ourselves and others. Although deeply grounded in Aotearoa, we argue that CTA may be transferable to other colonial contexts, such as the Australian where treaties between First Nations and the state are being contemplated, and Canada which has passed legislation to implement the Declaration on the Rights of Indigenous Peoples.
Keywords: Public Policy; Te Tiriti o Waitangi

The Politics of Indigenous Exclusion in Australia and New Zealand - O’Sullivan, Dominic (Current History, 2024)
In both Australia and New Zealand, Indigenous peoples have called for alternative non-colonial political arrangements. In October 2023, Australians voted in a referendum against distinctive Indigenous participation in public policymaking, which had been proposed as a step toward a more inclusive political system. On the same day, New Zealand elected a new Parliament, leading to the formation of a government comprising three parties that had campaigned against what they saw as excessive Māori political influence. Comparing these developments and the histories of the two countries raises questions about liberal equality, democratic citizenship, and whether all or just some citizens should own the liberal democratic state.

Te Tiriti o Waitangi—neither “one people” nor partners: rangatiratanga and inclusive democratic kāwanatanga - O’Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2024)
Te Pati Māori (The Māori Party) proposes removing the British monarch as head of state so that Te Tiriti o Waitangi’s (the Māori text of the Treaty of Waitangi) (Te Tiriti) promise of fulfilling partnership may be realized. The ACT (Association of Consumers and Taxpayers) Party’s alternative argument is that partnership is among a body of treaty principles that give Māori people (Indigenous peoples of New Zealand) political advantage over others. These alternative perspectives transcend time because neither partnership nor equality as the ACT party presents it meets the possibilities of liberal democratic citizenship that may be read into Te Tiriti. Instead, equality is enhanced by interpreting Te Tiriti as constituting a commonwealth with hapū (sub-tribes) as existing political communities, and kāwanatanga (government) as a new one, with powers and responsibilities grounded in equal tikanga (cultural practices and proper conduct). The powers of government may then be shared, through participatory parity.

Maori Self-Determination: Towards Differentiated Liberal Citizenship - O'Sullivan, Dominic (Australian Journal of Politics & History, 2019)
During the 1980s and 1990s biculturalism was the ascendant political philosophy for managing the relationship between the New Zealand Crown and the indigenous Maori population. Biculturalism understood Maori politics as a partnership between Maori and the state, grounded in the Treaty of Waitangi, the agreement signed in 1840 from which British government was established. Biculturalism was presented as morally superior to multiculturalism which was understood as setting aside Maori Treaty rights and rights of prior occupancy in favour of less substantive rights available to Maori as one of many ethnic minorities. However, a deeper reading of multicultural political theory provides an instructive critique of biculturalism's inherent limits from the perspective of the Maori right to self-determination. It shows why biculturalism's influence waned. It also shows why Matike Mai o Aotearoa, a blueprint for constitutional transformation commissioned by tribal leaders is unlikely to succeed as a contemporary attempt to reassert biculturalism's influence. Multicultural theory is not a panacea for the right to self-determination, but it does not restrict the development of a broader Maori-centred differentiated liberal citizenship in the ways that biculturalism precludes.
Keywords: Biculturalism; Multicultural; Politics; Self-Determination

Indigeneity, Ethnicity, and the State: Australia, Fiji, and New Zealand - O’Sullivan, Dominic (Nationalism and Ethnic Politics, 2014)
This article draws on the politics of indigeneity to distinguish the claims of first occupancy from simple ethnic identity politics, illustrating that relative political marginalization in Australasia is not so much a function of minority status but of indigeneity itself. The politics of indigeneity's aim is to create political space for self-determination and a particular indigenous share in the sovereign authority of the nation-state itself. The Australasian states are compared with Fiji to demonstrate that the significance of historical constraints on political authority transcend the withdrawal of a colonial power and the restoration of collective indigenous majority population status.

Māori Self-Determination: In the Modern Political Context - O'Sullivan, Dominic (AlterNative: An International Journal of Indigenous Peoples, 2005)
Keywords: Commonwealth; Democracy; Political Parties; Te Tiriti o Waitangi

Introducing critical Tiriti policy analysis through a retrospective review of the New Zealand Primary Health Care Strategy - O’Sullivan, D; Came, Heather; McCreanor, T (Ethnicities, 2020)
BackgroundTe Tiriti o Waitangi was negotiated between the British Crown and Indigenous Māori leaders of Aotearoa New Zealand in 1840. Māori understood the agreement as an affirmation of political authority and a guarantee of British protection of their lands and resources. The Crown understood it as a cession of sovereignty. The tension remains, though legal and political developments in the last 35 years, have established that the agreement places a mandatory obligation on the Crown to protect and promote Māori health. It also requires that Māori may exercise rangatiratanga, or responsibility and authority, in relation to health policy development and implementation.MethodsTe Tiriti is, then, an instrument against which health policy is justly and efficaciously evaluated. This paper introduces critical Tiriti analysis as such an evaluative method. Critical Tiriti analysis involves reviewing policy documents against the Preamble and the Articles of te Tiriti o Waitangi. The review process has five defined phases: (i) orientation; (ii) close reading; (iii) determination; (iv) strengthening practice and (v) Māori final word.ResultsWe present a working example of critical Tiriti analysis using the New Zealand Government’s Primary Health Care Strategy published in 2001. This policy analysis found poor alignment with te Tiriti overall and the indicators of its implementation that we propose.ConclusionThis paper provides direction to policy makers wanting to improve Māori health outcomes and ensure Māori engagement, leadership and substantive authority in the policy process. It offers an approach to analysing policy that is simple to use and, inherently, a tool for advancing social justice.
Keywords: Critical Tiriti Analysis; Healthcare; Policy Analysis

The Waitangi Tribunal’s WAI 2575 Report - O’Sullivan, Dominic; Came, Heather; Kidd, Jacquie; McCreanor, Timothy (Health and Human Rights, 2020)
Te Tiriti o Waitangi, a treaty negotiated between Māori (the Indigenous peoples of Aotearoa) and the British Crown, affirmed Māori sovereignty and guaranteed the protection of hauora (health). The Waitangi Tribunal, established in 1975 to investigate alleged breaches of the agreement, released a major report in 2019 (registered as WAI 2575) about breaches of te Tiriti within the health sector in relation to primary care, legislation, and health policy. This article explores the implications of this report for the New Zealand health sector and the decolonial transformation of health systems. The tribunal found that the Crown has systematically contravened obligations under te Tiriti across the health sector. We complement the tribunal’s findings, through critical analysis, to make five substantive recommendations: (1) the adoption of Tiriti-compliant legislation and policy; (2) recognition of extant Māori political authority (tino rangatiratanga); (3) strengthening of accountability mechanisms; (4) investment in Māori health; and (5) embedding equity and anti-racism within the health sector. These recommendations are critical for upholding te Tiriti obligations. We see these requirements as making significant contributions to decolonizing health systems and policy in Aotearoa and thereby contributing to aspirations for health equity as a transformative concept.

Co-Governance and the Case for Shared Decision Making - Jones, Carwyn (Policy Quarterly, 2023)
This article explores some of the key features of co-governance, or shared decision making, between Māori and the Crown. Co-governance models create the conditions for making better decisions by sharing decision making with Māori where Māori communities have a distinctive interest. Such models are able to draw on the distinctive experiences, knowledge and expertise that Māori communities can bring. Shared decision making enhances the legitimacy and durability of decisions by giving effect to rights under te Tiriti o Waitangi. The article also identifies some key principles of effective co-governance and provides some brief examples where shared decision making is being implemented to illustrate the range of situations in which such models are applicable.
Keywords: Co-Governance; Treaty settlements

Region-level Pākehā warmth towards Māori enhances collective action intentions: An extension of the social identity model of collective action (SIMCA) - Houkamau, Carla; Bahamondes, Joaquín; Osborne, Danny; Sibley, Chris (International Journal of Intercultural Relations, 2024)
New Zealand is a peaceful nation, but ongoing political tensions and inequities between Māori (the indigenous peoples of New Zealand) and Pākehā (the majority group of Europeans) persist as a result of its colonial history. Identifying ways to redress the enduring legacy of colonialism are therefore of critical importance. Accordingly, this paper examines data from 7017 Māori, as well as 37,233 Pākehā, to examine the impact of regional-level Pākehā warmth towards Māori on Māori support for progressive collective action. Results reveal that Pākehā warmth towards Māori varies markedly across 257 regional wards (regional units created for New Zealand electoral purposes). Moreover, multilevel modelling demonstrates that Pākehā warmth towards Māori at the region-level correlates positively with Māori identity and political efficacy at the individual level which, in turn, both correlate positively with collective action support. Collectively, these results demonstrate the impact of the broader social climate on social change, while identifying a previously-unknown facilitator of collective action support (namely, a broader context of warmth towards structurally disadvantaged groups).
Keywords: Activism; Māori; Political rights; Social identity model of collective action (SIMCA)

A fine risk: Ethics in Kaupapa Maori politics - Hoskins, Te Kawehau (New Zealand Journal of Educational Studies, 2012)
Kaupapa Maori theory is broadly underpinned by a politics that has strategically promoted forms of cultural essentialism and oppositional political stances/power analyses, which have been useful to the revitalisation of culture and the assertion of rights and recognition. Although they serve Maori struggles, these positions often become less self-consciously strategic, and more often lead to accepted political orthodoxy. At the same time, Kaupapa Maori has asserted the importance of theory developed from indigenous - Maori ways of thinking and acting. In this article I contribute to such a project by reflecting on Maori cultural ethics and what they might offer to theorising social and political relations beyond the oppositional colonised-coloniser binary. With particular reference to the work of Emmanuel Levinas, I argue that Maori orientations suggest an imperative to relationship - not opposition, and to responsibility for others - not simply the assertion of rights claims. A politics informed by Maori cultural ethics glimpses a different, certainly riskier, but ultimately more radical and productive politics.
Keywords: Ethics; Maori (New Zealand people)–Education; Maori (New Zealand people)–Politics and government; Political science

Does the New Zealand Government owe Māori an apology? - Hook, G. R.; Raumati, L. P. (Mai Review, 2008)

Indigenous Representational Choices: Results from a Large Qualitative Survey on Māori Electoral Roll Choice - Greaves, Lara Marie; Hini, Rebecca; Overbye, Hannah R.; Brink, Kaylee Grace (Journal of Race, Ethnicity, and Politics, 2025)
Different participatory mechanisms for the representation of Indigenous peoples have been proposed across states. Since their creation in 1867, the Māori electorates in the national Parliament have led to dedicated representation for Māori (Indigenous peoples of New Zealand). However, only half of Māori choose to vote on the Māori roll, the remainder choosing to vote on the General roll, illustrating that roll choice is not based simply on group representation. This survey aimed to ask Māori (N = 1,958) in their own words why they made their roll choice. Through a deductive codebook thematic analysis, a range of codes were constructed around the reasoning behind roll choice. Māori on the Māori roll made their choice because they valued Māori representation; as an expression of their identity; to support the electorates; as a strategic choice; or they had been influenced by others or through education. Those on the General roll felt their roll was the default or a more familiar option; the Māori roll had less of an impact; it was a strategic choice, or they appreciated greater candidate variety; or they valued the smaller geographic electorate size. Some felt Māori no longer needed separate representation or felt less connected to their identity as Māori. The results have implications for both Māori and Indigenous representation through dedicated representational mechanisms.
Keywords: Indigenous; Māori; Māori electorates; Voting; Parties; Parliament; representation; voter enrolment

Moving beyond “Contingent”: Descriptive Representation by and for Indigenous Peoples - Greaves, Lara; Curtin, Jennifer (Politics & Gender, 2023)
When Jane Mansbridge’s (1999) article was first submitted, more than 80% of the world’s parliaments featured less than 20% women (IPU 2015). Calculating the parliamentary presence of ethnic and cultural minorities and Indigenous peoples has proved more difficult (Protsyk 2010). This is despite the adoption of two United Nations Declarations, on the Rights of Persons Belonging to National or Ethnic, Religious and Linguistic Minorities (1992) and on the Rights of Indigenous Peoples in 2007. In Aotearoa New Zealand, the representation of women and Māori (the Indigenous peoples) was comparatively better than global averages. In 1996, 29% of parliamentarians were women and 14% were Māori. By 2020, these figures had increased to 48% and 21%, respectively, while in the cabinet, women made up 40% of ministers and Māori accounted for 25%. Reported as the country’s historically most diverse parliament and cabinet (Curtin 2020), it appears that both new (proportional representation) and old (reserved seats for Māori) institutional mechanisms had achieved near proportionality, and a heterogeneity of experiences, potentially enhancing opportunities for deliberation.
Keywords: Identity; Representation; Voting; Parties; Parliament

Māori Linked Administrative Data: Te Hao Nui - A novel Indigenous Data Infrastructure and Longitudinal Study - Boulton, Amohia; Theodore, Reremoana; Sporle, Andrew (The International Indigenous Policy Journal, 2023)
Worldwide, large amounts of administrative data are collected within official statistics systems on Indigenous Peoples. These data are primarily used for government and state policy purposes as opposed to by Indigenous Peoples to support Indigenous agendas (Taylor & Kukutai, 2017). In Aotearoa me Te Waipounamu New Zealand, Māori need high quality data to develop evidence-based policies and programs and to monitor government policies that impact on Māori. In this methodological paper, we describe uses of administrative data for Māori and current barriers to its use. We outline the development of a novel administrative data infrastructure and future longitudinal study. By explicating our Indigenous initiated, designed and controlled data project, we make a methodological contribution to Indigenous Data Sovereignty and Kaupapa Māori (Māori worldview) epidemiology.
Keywords: Indigenous data sovereignty; Māori; administrative data; policy; wellbeing; youth

Reflections on the Use of a Māori Conceptual Framework to Evaluate Complex Health Policy: The Case of New Zealand's Healthy Eating, Healthy Action Strategy Evaluation - Boulton, Amohia; Kingi, Te Kani (Evaluation Journal of Australasia, 2011)
Obesity among M?ori is of growing concern in New Zealand with rates for M?ori being one-and-a-half times that of the total population. The New Zealand government's Healthy Eating?Healthy Action: Oranga Kai?Oranga Pumau (HEHA) Strategy has, in the past seven years, been a significant policy mechanism through which the health sector has been able to address the increasing prevalence of obesity and associated chronic diseases.

Implementing Working for Families: the impact of the policy on selected Māori whānau - Boulton, Amohia; Gifford, Heather (Kōtuitui (Online), 2011)
General Note: Includes note, references
Keywords: Families – Health and hygiene; Social policy – Evaluation; Whānau

Regionalization as an Opportunity for Meaningful Indigenous Participation in Healthcare: Comparing Canada and New Zealand - Boulton, Amohia Frances; Lavoie, Josée G.; Gervais, Laverne (International Indigenous Policy Journal, 2012)
In Canada and New Zealand, policies support Indigenous participation in the planning and delivery of community-based primary health services. However, these services represent only a fraction of the health services accessed by Indigenous peoples. In New Zealand, legislation enacted in 2000 introduced mechanisms to ensure that Māori have a voice in the decisions made by health boards. In Canada, neither policies nor legislation currently ensure that Aboriginal communities are represented in provincial health systems or regional health boards. The New Zealand experience shows that adding mechanisms of participation to legislation and policies creates opportunities for Māori and health boards to engage in discussions about how to best allocate resources to reduce disparities between Māori and non-Māori health outcomes. In Canada, this dialogue may not occur. Requiring that such mechanisms be created in all Canadian jurisdictions would establish meeting places for dialogue, and assist in closing policy and access gaps that remain.

Whanau Ora: A culturally-informed, social policy innovation - Boulton, Amohia (New Zealand Sociology, 2019)
Whanau Ora, a social policy initiative designed to build the capacity and capability of Maori families, has been variously described as: a 'revolutionary public-sector initiative', an 'Indigenous policy success story' and as having the transformative power to improve health and social outcomes for Maori. Since its launch in April 2010, Whanau Ora has positively impacted the lives of many of our nation's most vulnerable Maori families. Through a kaupapa Maori lens, this article provides a brief overview of the initiative, the key goals of Whanau Ora and the mechanisms by which these goals were to be attained. It is argued that it reflects a 'paradigm shift' by fundamentally reorienting government thinking about how to improve Maori outcomes through policy. The article examines the success of Whanau Ora by highlighting a number of innovative aspects the National-led government introduced which contributed towards the success of the initiative through the period 2008-2017, as well as areas of tension. The article then turns to explore the likelihood of the Whanau Ora initiative continuing in the future, building on its early success embedding its innovative, empowering and sustainable social policy approach to working with Maori whanau, hapu, Iwi and communities.
Keywords: Community development; Maori (New Zealand people)–Government relations; New Zealand; Public health administration–Evaluation; Public welfare

Hauora hinengaro o takatāpui: analysing the effectiveness of mental health policies in addressing the needs of Takatāpui in Aotearoa New Zealand - Benvie-Watson, Emma; Greaves, Lara M. (Culture, Health & Sexuality, 2024)
Many studies have documented the effect that colonisation has had on takatāpui, that is, Māori (the Indigenous peoples of New Zealand) with diverse gender identities, sex characteristics and sexualities. In this paper, we explore whether current Aotearoa New Zealand (hereafter Aotearoa) mental health policies meet the needs of takatāpui. We identified five mental health policy needs, informed by the literature. We then explored policy documents from government ministries, district health boards and non-government organisations to see the extent to which policy met these needs. Four themes were present in the literature analysed: an overall lack of acknowledgment of takatāpui and intersectionality; promising engagement with the needs of takatāpui by NGOs; symbolic commitment to Te Tiriti o Waitangi; and some limited engagement with Māori health models. The findings show promise in some areas but demonstrate a lack of engagement by policy to meet the needs of takatāpui.
Keywords: Identity & Intersectionality; Mental health; Māori; Policy; Takatāpui

Towards a fairer and more tika political science and politics: Are political science programs equipping students adequately for Aotearoa realities? - Te One, Annie; Bargh, Maria (Australian Journal of Indigenous Education (Online), 2023)
Social and political change is occurring in Aotearoa New Zealand and tikanga, matauranga, te reo Maori (the Maori language) and Te Tiriti o Waitangi (Treaty of Waitangi) are increasingly being recognised in diverse political and legal contexts. This article explores whether the political science discipline in Aotearoa New Zealand is keeping pace with these political changes, whether research and course content is adequately reflecting these new realities, and if students are appropriately equipped to participate. In particular, we examine the state of university politics programs and outline the form and quantity of Maori politics in the teaching and research of these programs. From the assessment of the current state of politics programs, we make some observations about what changes may be required to ensure politics programs, their students and academics are fully equipped to work in the unique political and legal landscape of Aotearoa New Zealand. From the collection of this data, we have found that approximately 1% of political science lecturers are Maori, 1% of content taught can be classified as Maori politics and approximately 1% of publications in the New Zealand Political Science journal can be classified as kaupapa Maori politics. This 1-1-1 crisis provides a bleak picture of the existing arrangements in politics programs in Aotearoa New Zealand and must change
Keywords: Indigenous peoples–Education; Māori (New Zealand people)–Education; Māori (New Zealand people)–Politics and government; New Zealand; Political science–Politics and government; Research–Evaluation

Kia aiō ngā ngaru, kia hora te marino: smoothing the waters in natural resource management to mitigate risk and uncertainty - Awatere, Shaun; Hyslop, Jade; Harcourt, Nikki; Hikuroa, Dan; Blackett, Paula; Heron, Richard Le (AlterNative: An International Journal of Indigenous Peoples, 2023)
Aotearoa (New Zealand) is undertaking reforms in natural resource management, and there are promising signals that Indigenous perspectives will be included alongside science for decision-making. Any resource management system is underpinned by worldviews, from which values stem and then risk and uncertainty derive. Māori (the Indigenous peoples of New Zealand) and Eurocentric notions of risk and uncertainty are fundamentally different because knowledge holders have different worldviews. Eurocentric concepts of risk and uncertainty continue to frame policy, making it challenging for Māori knowledge to shape policy that is relevant for decision-making in Aotearoa. We explore Māori perspectives of risk and uncertainty and literature, identifying common attributes across natural resource management frameworks, and identify issues of risk and uncertainty from the perspective of Māori experts. We conclude that a Māori approach to enhancing natural resources is more aligned to current environmental policy compared with standard approaches for risk assessment and reducing uncertainty.

The crisis of policy failure or the moral crisis of an idea: colonial politics in contemporary Australia and New Zealand - O’Sullivan, Dominic (Political Science, 2022)
When analysing Indigenous public policy, crisis is best seen as the moral crisis of an enduring idea rather than the crisis of sporadic and unconnected instances of policy failure. In Australia and New Zealand, states use manufactured crises of Indigenous personal deficiencies to justify colonial authority. A justification which may be countered by positioning colonialism itself as the point of crisis. From this perspective, the crisis in Indigenous public policy is not resolved by the state becoming better at policy-making or more attentive to the egalitarian distribution of public resources. Instead, it is in the non-colonial possibilities of Indigenous self-determination that paths beyond crisis may lie. In practical terms, by ensuring spaces of independent Indigenous authority alongside spaces of distinctive culturally framed participation in the public life of the state. The potential for such arrangements in Australia is discussed with reference to a proposed First Nations’ Voice to Parliament and possible treaties between First Nations and the state. For New Zealand, their potential is discussed with reference to te Tiriti o Waitangi’s affirmation of independent Māori authority (rangatiratanga) and substantive state citizenship.
Keywords: Aboriginal Australians; Authority; Citizenship; Colonialism; Crises; Crisis theory; Egalitarianism; Indigenous peoples; Justification; Legislatures; Maoris; Policy making; Positioning; Public life; Public policy; Self determination; State; Treaties; colonialism; indigenous politics; indigenous self-determination; māori politics; political crisis; treaty of waitangi

Weaving mātauranga into environmental decision-making - Jones, Doug; Hikuroa, Dan; Gregory, Erica; Ihaka-McLeod, Hana; Moko-Mead, Te Taiawatea (New Zealand Science Review, 2020)
-
Keywords: environment; mātauranga māori

Negotiating co-management of the Waikato River - Te Aho, Linda (Resource Management Journal, 2009)
Keywords: file

Hybrid identities: Māori Italians challenging racism and the Māori/Pākehā binary - Houkamau, Carla; Giorgio, Adalgsia (Social Identities, 2021)
New Zealand's indigenous Māori were colonized by the British (now referred to as Pākehā). Scant systematic investigation addresses bicultural/biracial identity for Māori who identify with ethnic groups other than Pākehā. Taking a narrative approach and applying thematic analysis, this paper explores interviews with forty-four Māori Italians, conducted in New Zealand in 2013. We show how Māori Italians negotiate the challenge of constructing positive ethnic identities in a milieu where ethnic hybridity has been defined primarily in relation to the Māori-Pākehā colonial encounter. Focusing on racism and stigma, we demonstrate that Māori Italians run a gauntlet of identity challenges shaped by socio-political contexts. Conversely, Māori Italians draw boundaries between themselves and the dominant Pākehā culture and draw from both Māori and Italian identities to buffer discrimination from Māori, Pākehā, and Italians. Our analysis reveals a multiplicity of interpretations of Māori-Italian identity not yet articulated in social psychology or New Zealand literature.
Keywords: ethnic identity; identity; māori identity; racism

‘Why would you give your children to something you don’t trust?’: Rangatahi health and social services and the pursuit of tino rangatiratanga - Lindsay Latimer, Cinnamon; Le Grice, Jade; Hamley, Logan; Greaves, Lara; Gillon, Ashlea; Groot, Shiloh; Manchi, Madhavi; Renfrew, Larissa; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
Persistent health inequities between rangatahi Māori (Indigenous young people) and other young people within Aotearoa New Zealand are incurred by a colonial machinery of institutions, service systems and sociocultural contexts that facilitates the marginalisation of Māori. Despite a skilled and dedicated Māori workforce, current service contexts severely limit the innovation of Māori practitioners working from a basis of mātauranga Māori (Māori ways of knowing and being), and curtail their ability to support rangatahi Māori and their whānau (community of related families). We report on an interview study with 13 Māori practitioners in youth development, exploring their struggles, strengths and strategies, as part of a larger project exploring rangatahi wellbeing and whanaungatanga (connectedness and relationality). Utilising reflexive thematic analysis, we describe three conceptual domains that participant accounts spoke into: mitigating system failures to embrace rangatahi and their whānau, sustainability and longevity of services for rangatahi Māori, and fostering rangatahi tino rangatiratanga. Participant accounts illustrate the need for bold reform within youth services, towards sustainable models premised upon tino rangatiratanga – services led by Māori, designed by Māori, and intended to cater for the unique needs and aspirations of rangatahi Māori.
_eprint: https://doi.org/10.1080/1177083X.2021.1993938
Keywords: crown policy; mātauranga māori; rangatahi; tino rangatiratanga; whanaungatanga

Transformations in Māori Women's Identity: Some Things Change, Some Stay the Same - Houkamau, Carla Anne (Qualitative Research in Psychology, 2011)
While Māori (the indigenous people of New Zealand) retain a strong collective identity, cultural heterogeneity renders traditional conceptualisations of Māori identity increasingly problematic. To demonstrate the diverse ways Māori define and express their own identities, this article reports research that uses life-story interviews to explore personal perceptions of identity among 35 Māori women ages 18–75. Content analysis revealed traditional cultural factors (particularly whānau/family commitment) were important for identity among all participants, although the expression of these factors differed along with age and background. Older women raised in rural communities expressed family commitment through participating in social and economic activities within their own tribal networks. Younger, urbanised Māori expressed their identities by choosing careers which advanced Māori interests, supporting Māori political aspirations, and forming close relationships with other urban Māori. Life-story excerpts are used to illustrate distinct intergenerational differences in expressions of Māori identity as well as descriptions of “Māoriness,” seldom articulated in literature on the topic. The need to expand current paradigms of Māori identity to incorporate the diversity of group members is emphasised.
Keywords: colonisation; ethnic identity; kaumātua; mana wāhine; māori identity; urbanisation

Identity construction and reconstruction: the role of socio-historical contexts in shaping Māori women's identity - Houkamau, Carla Anne (Social Identities, 2010)
This article discusses intergenerational transformations in personal identity for New Zealand's indigenous Māori and links these to macro-societal (political, economic and cultural) changes in New Zealand society. Data is drawn from the life stories of 35 Māori women aged 18 to 78. Women born prior to 1950 and raised in traditional Māori communities interpreted Māori identity as related to communal economics, resourcefulness and Māori spiritual beliefs. Those born after 1960, raised in urban (multi-cultural) communities struggled to form a positive sense of being Māori during their formative years and reported ‘dislocation’ from their Māori identities as adults. Those born after the 1970s expressed strong political views that reflected their early exposure to affirmative ideologies regarding Māori rights to equality. Marked differences in women's stories highlight the overarching influence of Māori identity politics at a collective level for personal interpretations of what it means to be Māori.
Keywords: identity; māori identity; political change; wāhine māori

Ngā Whakaaro a Puhiwahine: A Political Philosophy and Theory from the Mōteatea of Puhiwahine - Simon, Hemopereki (2020)
Mōteatea are the orally sung literature and one of its most famous composers was Ngāti Tuwharetoa and Ngāti Maniapoto’s Puhiwahine. This paper will explore the political philosophy and theory contained within Puhiwahine’s waiata pakanga (war song) ‘Mā Wai Rā’ written for Ngāti Toa relations particularly their war leader, Te Rangihaeata. The observations from these forms of indigenous oral literature are based in a form of emerging indigenous philosophy called whakaaro based philosophy and method. Additionally, the author introduces a Kaupapa Māori Research method Marae ā-Rorohiko which outlines how social media, in particular Facebook, can be used as a form of group validity or qualitative data gathering. The analysis of the moteatea will focus on building a first person understanding of Māori philosophy and undestandings of mōteatea settler colonialism, colonisation and the centrality of mana and aroha in Māori society. It will reveal the that Puhiwahine had a deep understanding of Māori philosophy and what was to come from her people. It will also provide new understandings around the white possessive doctrine and mana motuhake.
Keywords: iwi politics; moteatea; pre-colonisation

You’re Giving Me a Headache: A Political–Cultural Textual Critique of Alt/Far-Right Anti-indigenous Thought on Indigenous Issues in Aotearoa New Zealand - Simon, Hemopereki (Sites: a journal of social anthropology and cultural studies, 2021)
This paper will provide a critical critique of Alt/Far-Right Political Thought on Indigenous Issues and History in Aotearoa New Zealand. It examines the preface of the book, “One Treaty, One Nation” entitled, “Some of The Myths on Which The Treaty Industry is Based” by emerging Alt/Far-Right Publisher, Tross Publishing. The author examines supposed ‘myths’ put forward by the authors. An exploration of the relevance of Aboriginal academic Aileen Moreton-Robinson’s White Possesive Doctrine, Histographpobia and Veracini’s Commentary of “On Settling.” This piece ends by providing commentary on the collective future of Aotearoa New Zealand should be based on.
Keywords: racism; tiriti o waitangi/treaty of waitangi

The Critical Juncture in Aotearoa New Zealand and The Collective Future: Policy Issues in Settler/Invader Colonial Zombiism Found in “Biculturalism” - Simon, Hemopereki (International Journal of Critical Indigenous Studies, 2022)
This research examines the settler colonial legacy of Aotearoa New Zealand. It shows that biculturalism has emerged as a discursive byproduct of neoliberalism and settler colonialism. Simon’s recent work and the Te Paparahi o Te Raki Waitangi Tribunal decision aligns with the view of a significant paradigm shift since biculturalism suppresses affirmation of and mana motuhake. Biculturalism can be viewed through Moreton-Robinson’s white possessive lens as well as Beck's zombie concepts, which are used to prop up deteriorating and/or fictional social institutions. As a zombie concept in Aotearoa New Zealand, “biculturalism” supports settler/invader power structures. Indigenous communities disproportionately experience the destructive consequences of neoliberal policies and statecraft. Aotearoa New Zealand’s collective future requires abandoning biculturalism; to that end the author recommends revising common historiographic thought concerning Te Tiriti o Waitangi (Treaty of Waitangi) and the concept of “settling”.
Keywords: bicultural; colonisation; neoliberalism

Voting in Māori Governance Entities - Bargh, Maria; Rata, Arama (The International Indigenous Policy Journal, 2020)
Internationally, declining voter turnout is a topic of considerable concern in many liberal democracies. In this article, we investigate whether these similar trends can be discerned in the voter turnout for Māori governance entities. We first explore some of the demographic contexts within which Māori governance entities operate with a specific focus on population, residence, and age. We then provide a detailed descriptive analysis of voting data from one particular entity: Te Rūnanga o Ngāti Awa, with whom we worked to understand how their elections inform their aspirations for continuing connectedness with tribal members. In the final section of the article, we present findings from an analysis of publicly available tribal voting data to see whether the trend of declining voter turnout is observable and whether online voting is shown to impact turnout.
Keywords: iwi elections; kaupapa māori research; māori voting; online voting; post-settlement (waitangi tribunal); self-determination

Ngā Mātāpono e Rua: Stories of co-creation for bicultural spatial governance in Aotearoa New Zealand - de Jesus Dionisio, Maria Rita; Macfarlane, Angus H.; Walker, Dean P.; Macfarlane, Sonja L.; Derby, Melissa; Caldwell, Ruiha; Pani, Jude; Waru, Rawiri (New Zealand Geographer, 2021)
This article shares lessons for spatial governance in Aotearoa New Zealand in the context of the Treaty of Waitangi. It reports on research into co-creation pathways that supported bicultural spatial governance inclusive of whānau and local communities in the Waimakariri and Rotorua Districts. In alignment with three Treaty principles, local tikanga, unique to the two places, informed the methodological framework for bicultural spatial governance. Despite some commonalities, the two case studies reveal distinctive perspectives that resonate differently across Aotearoa New Zealand, underscoring the importance of co-creation for biculturalism. We consider the implications for biculturalism across a range of spatial contexts and for debates about decolonising governance.
Keywords: bicultural; co-governance; mātauranga māori; partnership; tikanga | indigenous law

Re-Imagining Wild Rivers in Aotearoa New Zealand - Brierley, Gary; Fuller, Ian; Williams, Gary; Hikuroa, Dan; Tilley, Alice (Land, 2022)
If wilderness is dead, do wild rivers exist and if so, in what form and in whose construction? This reflective article reviews perspectives on rivers in Aotearoa New Zealand as wild or tamed entities. A historical overview of the socio-cultural and institutional relationships with rivers examines the meanings of rivers in Aotearoa New Zealand through multiple lenses. This includes indigenous Māori knowledge, command-and-control mentalities of a settler society that assert human authority over rivers, the emergence of the environmental movement and associated legislation with a sustainability focus (the Resource Management Act), and recent movement towards co-governance arrangements that incorporate the original intent of Te Tiriti o Waitangi (1840). It is contended that management practices have disconnected society from rivers, and vice versa, creating a sense of environmental loss (solastalgia), especially for Māori. Using rivers in the Greater Wellington Region as examples, prospects to accommodate wild river behaviour in Aotearoa New Zealand are explored. Recognising that re-wilding is no longer a feasible option in most instances, further attempts to tame rivers are also considered to be unrealistic, especially in light of climate change and accentuated flood risk. Reconnecting with indigenous knowledge offers prospects to re-imagine wild rivers in Aotearoa, living generatively with rivers as dynamic and emergent entities.
Keywords: environmental management; mātauranga māori; river management

Why New Zealand’s Indigenous reconciliation process has failed to empower Māori fishers: Distributional, procedural, and recognition-based injustices - Bodwitch, Hekia; Song, Andrew M.; Temby, Owen; Reid, John; Bailey, Megan; Hickey, Gordon M. (World Development, 2022)
How is it that the New Zealand government’s process for re-establishing Indigenous fishing rights has failed to deliver thriving Māori fisheries? This paper examines why, at Te Waihora, a coastal lake, and site of one of the nation’s longest running and best-funded state-Māori co-governance agreements, Māori fishers have been unable to use their rights to support their fishery. As of 2018, the lake’s culturally and ecologically significant eel population was no longer commercially viable, a decline fishers have attributed to rampant dairy industry expansion upstream. Drawing on environmental justice literatures, we deploy a multi-dimensional framework to identify factors shaping possibilities for justice in the wake of rights reconciliation, as experienced by Māori fishers, scientists, and leaders. We engage theories of political economic relations to interpret the implications of these experiences for environmental justice theory and politics. Ethnographic accounts demonstrate that the New Zealand government’s process for re-establishing Māori rights falls short of achieving distributional, procedural, and recognition-based dimensions of environmental justice, and that these effects are interlinked. In particular: (i) downstream fishers are placed to bear disproportionate costs of runoff from upstream land use change; (ii) Māori fishers have little influence over governance decisions that affect land use; and (iii) government claims, including that Māori should, “move beyond grievance mode,” obscure logics for resistance. We suggest that the government’s support for dairy industry expansion represents an attempt to mitigate crises of overaccumulation, characteristic of competitive markets. Unlike those who identify persistent injustice as a logic for turning away from the state, we argue that the recurring nature of these crises, and the role state organizations play in directing responses, indicates a rationale for continued engagement with state governing bodies to advance justice.
Keywords: co-governance; economic aspects; environmental justice; equity; fisheries

Mātauranga Māori, tino rangatiratanga and the future of New Zealand science - Broughton, D; McBreen, K (Journal of the Royal Society of New Zealand, 2015)
All peoples develop their own academic traditions: philosophies grounded in their experiences over successive generations, and theories for growing knowledge and wisdom. Mātauranga Māori (mātauranga) is the Indigenous knowledge system of these lands. It is dynamic, innovative and generative. The mātauranga continuum is the knowledge accumulated through this system. Government policies and systems have marginalised mātauranga and prioritised Western science, and the past 100 years have seen a slowing in the expansion of the mātauranga continuum. Unless the survival of mātauranga is prioritised, it will cease to flourish. Māori have discussed and written extensively about the ongoing impact of colonisation on mātauranga and tikanga Māori. This paper builds on those discussions, arguing for tino rangatiratanga, including Māori ownership of mātauranga, fulfilment of the government's obligations to Māori, and the reinstitution of mātauranga as a primary knowledge system in Aotearoa. It explains why mātauranga revitalisation is important and outlines some of the steps towards this goal. We are calling for Western academics to support mātauranga revitalisation, with the vision of two functional knowledge systems operating that are unique to New Zealand.
Keywords: mātauranga māori; self-determination; tino rangatiratanga

Tikanga rua: Bicultural spatial governance in Aotearoa New Zealand - Dionisio, Rita; Macfarlane, Angus Hikairo (New Zealand Geographer, 2021)
This editorial introduction outlines the political and intellectual territory for a Special Issue on Tikanga rua: bicultural spatial governance in Aotearoa New Zealand. The term ‘spatial governance’ refers to deliberative systems with an impact on social and spatial outcomes, including environmental management, town planning, urban design and city-making. Authentic tikanga rua bicultural spatial governance delivers processes and outcomes aligned with the perspectives, values and knowledge of both tangata whenua (people of the land) and tangata Tiriti (people of the Treaty). The research discussed in the Special Issue traverses multiple geographies and contexts and demonstrates the manifold possibilities for biculturalism in contemporary spatial governance. This introduction summarises the contents of each of the substantive papers and provides a Māori-English glossary to assist readers with the key terms used within the issue.
Keywords: bicultural; governance; tikanga | indigenous law

Options for Constitutional Change - Wickliffe, Caren; Dixon, Matiu (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: constitutional transformation; mātauranga māori; social life and customs; sovereignty; tino rangatiratanga; tāngata whenua

The Politics of Māori Image and Design - Jahnke, Robert; Jahnke, Huia Tomlins (He Pukenga Korero: a journal of Māori studies, 2003)
Keywords: cultural appropriation; indigenous data sovereignty; intellectual property; mātauranga māori; rangatiratanga; social life and customs; tāngata whenua

Te Hoe Nuku Roa: A Measure of Māori Cultural Identity - Stevenson, Brendan (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: ethnic identity; identity; mātauranga māori; tāngata whenua

Millenial Thoughts on Māori Development - Henare, Denese (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: crown; development; mātauranga māori; rangatiratanga; social life and customs; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua

Self-Governance - Turia, Tariana (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: mātauranga māori; rangatiratanga; self-governance; social life and customs; tāngata whenua; whangānui iwi

A Traditionalist Approach to Iwi Government - Potiki, Tahu (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: iwi; mātauranga māori; self-governance; social life and customs; te reo māori; tino rangatiratanga; treaty settlements; tāngata whenua

Restoration of the Tribal Collective: Rebuilding Tribal Capacity Alongside Economic Development - White, Paul (He Pukenga Korero: a journal of Māori studies, 2000)
Keywords: development; economic development; mātauranga māori; social life and customs; treaty settlements; tāngata whenua

"Like, if it's really important, they should be saying!" Research with Rangatahi Māori about Local Political Participation - Tawhai, Veronica; Cheyne, Christine (He Pukenga Korero: a journal of Māori studies, 2009)
Keywords: local government; mātauranga māori; political participation; rangatahi; social life and customs; tāngata whenua

Governance and Legitimacy: Indigenous Development in Aotearoa - Dodd, Materoa (He Puna Korero: Journal of Maori & Pacific Development, 2001)
Keywords: hapū; iwi; mana wāhine; post-settlement (waitangi tribunal); rangatiratanga; sexism; tiriti o waitangi/treaty of waitangi

Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

The concept of partnership and The Treaty of Waitangi: three case studies - Morrison, Sandy (He Puna Korero: Journal of Maori & Pacific Development, 2005)
Keywords: co-governance; partnership; tiriti o waitangi/treaty of waitangi; treaty principles

Te Arewhana Kei Roto i Te Rūma: An Indigenous Neo-Disputatio on Settler Society, Nullifying Te Tiriti, ‘Natural Resources’ and Our Collective Future in Aotearoa New Zealand - Simon, Hemopereki (Te Kaharoa, 2016)
This practice-research based article explores the relationship between mana motuhake and white patriarchal sovereignty in Aotearoa New Zealand, focusing on Ngāti Tūwharetoa as a case study. It seeks to find the relevance of Aboriginal academic Aileen Moreton-Robinson’s white possessive doctrine to the Aotearoa New Zealand context. In particular, it highlights the racist nature of the law and planning systems and their inadequacies to provide for hapū and iwi. It provides a key theoretical analysis regarding the nature of white patriarchal sovereignty in Aotearoa and the need of the state to appear virtuous, to continue the legacy that started with the Treaty of Waitangi to maintain this whenua as a white possessive. Lastly, the piece questions the position of Britishness within Aotearoa New Zealand and asks key philosophical questions for all about the need to find common understandings or māramatanga about our collective future as a society.

What can the Māori-led COVID Roadblocks tell us about a Bicultural Future Legal System in Aotearoa New Zealand? - Fitzmaurice, Luke (Legalities, 2021)
Keywords: covid checkpoints; law; rangatiratanga; sovereignty; tikanga | indigenous law

Mana whenua engagement in Crown and Local Authority‐initiated environmental planning processes: A critique based on the perspectives of Ngāi Tahu environmental kaitiaki - Bennett, Courtney; Matunga, Hirini; Steyl, Steven; Borell, Phillip; Dionisio, Maria Rita; Hapuku, Aaron (New Zealand Geographer, 2021)
In New Zealand, the Crown and Local Authorities are required to engage with iwi in resource management matters, yet iwi engagement is a widely recognised weakness in many resource management professionals' skillsets. Coloniality permeates many interactions with iwi, and reflects a profession where practitioners' skillsets have not kept pace with developments in resource management legislation that better recognise the rights and interests of mana whenua. This article explores the real‐life impacts of this skill paucity on Ngāi Tahu environmental kaitiaki, and, through a Braided River methodological approach comprised of Kaupapa Māori research and Narrative Inquiry, offers recommendations for best practice mana whenua engagement. The article concludes by discussing the coloniality of planning, and how this impacts practitioners' ability to implement these best practice recommendations.
Keywords: co-governance; iwi; kaitiakitanga; kāi tahu; local government

Colonization, whenua and capitalism: experiences from Aotearoa New Zealand - Moewaka Barnes, Helen; Eich, E.; Yessilth, S. (Continuum, 2018)
The English Laws Act, passed in 1858, declared the Laws of England applicable in New Zealand and cemented the hitherto alien ideology of land as property. Part of this ideology was the separation of tangata from whenua along with the separation of ownership of land from ownership of water. Māori, as tangata whenua – people of the land, made no such distinctions. Ownership affects how people ‘manage’ whenua (land), make decisions and account to the legal system. Under English law, financial considerations are at the forefront. In contrast, Māori kaitiakitanga values are concerned with the interests of land, understanding that the best interests of people will follow. Despite stark contrasts between the ideology of land as property and the ethics of kaitiakitanga – obligation, sustainability and nurture – Māori engage with mainstream agencies and lead by example in efforts to promote the wellbeing of people and environments in a unified approach. This paper outlines competing paradigms, changing relationships and challenges faced by communities who seek to nurture and respect whenua in the face of colonization. Interview data from Māori involved in community land-based initiatives illustrates past and present struggles and what some possibilities might be for the future.
Keywords: capitalism; colonisation; crown law; kaitiakitanga; whenua

Tension without tikanga: the damaging face of the treaty claims settlement system - Taiapa, Ken; Moewaka Barnes, Helen; McCreanor, Tim (AlterNative: An International Journal of Indigenous Peoples, 2021)
In Aotearoa New Zealand, the arrival of imperial ideologies in the 19th century led to devastating land-loss and cultural marginalisation for M?ori at the hands of settlers and successive governments. This article examines the damaging effects of a Crown-imposed treaty claims settlement system designed to address injustices inflicted on M?ori. Interview data from a Taranaki-based (a West Coast region, central North Island of Aotearoa New Zealand) hap? (sub-tribe) that engaged with this system foreground the adversarial nature of this system and its continuation of trauma. We argue that, while the process provides voice to M?ori, it does so within a paradigm that pits kin-groups against each other, unjustly limits redress and fails to resolve tension. A tikanga framing provides insights into how tensions are set up and ways tikanga (underlying values and principles that guide practice) can be used outside the redress system to seek healing and resolution.
Keywords: colonial structures; colonisation; crown; hapū; kāwanatanga; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Mātauranga Māori: shaping marine and freshwater futures - Clapcott, Joanne; Ataria, Jamie; Hepburn, Chris; Hikuroa, Dan; Jackson, Anne-Marie; Kirikiri, Rauru; Williams, Erica (New Zealand Journal of Marine and Freshwater Research, 2018)
Keywords: freshwater futures; marine futures; mātauranga māori; policy making; resource development

Politics and knowledge: Kaupapa Maori and matauranga Maori - Royal, Te Ahukaramu Charles (New Zealand Journal of Educational Studies, 2012)
In the past two decades, the terms 'kaupapa Maori' and 'matauranga Maori' have come to prominence in Maori education and research circles. They appear in a wide variety of contexts to articulate and advance certain aspects of Maori education and development. The two terms are generally utilised to support activities designed to generate benefits for Maori and to give expression to Maori ways of doing things, aspects of Maori knowledge and the Maori world view. Interestingly, there are a number of perspectives on the two terms and whilst meanings for both overlap, they are not synonymous. In this article, I present my view of the meaning of kaupapa Maori and matauranga Maori. My background is as a researcher of matauranga Maori, hence my views are presented from this perspective.
Keywords: kaupapa māori; mātauranga māori; tikanga | indigenous law

Whakamanahia Te mātauranga o te Māori: empowering Māori knowledge to support Aotearoa’s aquatic biological heritage - Ataria, James; Mark-Shadbolt, Melanie; Mead, Aroha Te Pareake; Prime, Kevin; Doherty, Jim; Waiwai, James; Ashby, Tohe; Lambert, Simon; Garner, Gary Owen (New Zealand Journal of Marine and Freshwater Research, 2018)
As Aotearoa New Zealand grapples with developing solutions to complex issues surrounding its unique freshwater and marine biological heritage, there is a growing recognition that mātauranga Māori can be ‘unlocked’ and used with great effect alongside western science. Examples where appropriate consideration and development of robust methodologies for the application of mātauranga Māori coexisting alongside western science are increasing. Unfortunately, despite the benefits that can be derived from this collaboration, the quality of engagement is not always satisfactory often due to poor interpersonal relationships and misidentification of the knowledge holders. By providing an appropriately historical context, this article is able to consider the critical issues now facing mātauranga and the Māori knowledge holders today, and fundamental requirements that will empower application of this knowledge within bio-heritage management. We consider how the development of a methodology between mātauranga Māori holders and potential end-users might contribute to improved outcomes for Aotearoa’s biological heritage.
Keywords: environmental management; indigenous rights; mātauranga māori; sovereignty; tiriti o waitangi/treaty of waitangi; whakapapa

Panic on the beach - Jackson, Moana (Mana Magazine, 2003)
Keywords: foreshore and seabed act 2004; racism

Māori Academic Challenges: Delivering Mātauranga Māori During COVID-19 - Te Momo, Fiona (Journal of Contemporary Issues in Education, 2022)
In March 2020, the COVID-19 pandemic disrupted academic educational programmes in universities across the world, including Aotearoa New Zealand. For Māori academics who implement mātauranga Māori as a pedagogy, it became theoretically and practically challenging teaching virtually and online. The Te Taha Tinana, of Te Whare Tapa Wha model, created by aDurie in 1984 (Health Navigator, 2022) regarding the four dimensions of well-being, focuses on the physical presence, physical embodiment, and physical behaviour. This could not be easily taught virtuality through a computer screen during COVID-19 lockdown. For Māori academics transitioning from teaching Mātauranga Māori in person to an online environment brought forth these challenges. The challenges re-emerged in August 2021 when New Zealand went into Level 4 lockdown overnight because of the new COVID-19 Delta Virus variant. In 2022, the Omicron variant caused many universities in Aotearoa New Zealand to continue their first semester teaching online.
Keywords: covid-19; education; mātauranga māori; political development; social development; whanaungatanga

The Misappropriation of the Haka: Are the Current Legal Protections Around Matauranga Maori in Aotearoa New Zealand Sufficient? - Wilson, Isabella Tekaumarua (Victoria University of Wellington Law Review, 2020)
Gale Academic OneFile includes THE MISAPPROPRIATION OF THE HAKA: ARE THE CURRENT LEGAL by Isabella Tekaumarua Wilson. Click to explore.
Keywords: intellectual property; kaitiakitanga; mātauranga māori; taonga; tiriti o waitangi/treaty of waitangi

Kia Tawharautia Te Matauranga Maori: Decolonising the Intellectual Property Regime in Aotearoa New Zealand - Kapa-Kingi, Eru (Victoria University of Wellington Law Review, 2020)
Gale Academic OneFile includes KIA TAWHARAUTIA TE MATAURANGA MAORI: DECOLONISING THE I by Eru Kapa-Kingi. Click to explore.
Keywords: decolonisation; intellectual property; mātauranga māori; tikanga | indigenous law; tino rangatiratanga; waitangi tribunal

Mātauranga Māori in geomorphology: existing frameworks, case studies, and recommendations for incorporating Indigenous knowledge in Earth science - Wilkinson, Clare; Hikuroa, Dan; Macfarlane, Angus; Hughes, Matthew (Earth Surface Dynamics, 2020)
Mixed-method bicultural research in Aotearoa New Zealand, including the weaving of Indigenous and other knowledge, is emerging within many academic disciplines. However, mātauranga Māori (the knowledge, culture, values, and world view of the Indigenous peoples of Aotearoa New Zealand) and Te Ao Māori (the Māori world) is poorly represented within geomorphological investigations. Here, we review international efforts to include Indigenous knowledge in geologic and geomorphic studies and provide an overview of the current state of mātauranga Māori within research endeavours in Aotearoa New Zealand. We review three theoretical frameworks (i.e. methodologies) for including mātauranga Māori in research projects and three models (i.e. methods) for including Māori values within research. We identify direct benefits to geomorphology and discuss how these frameworks and models can be adapted for use with Indigenous knowledge systems outside of Aotearoa New Zealand. The aim of this review is to encourage geomorphologists around the world to engage with local Indigenous peoples to develop new approaches to geomorphic research. In Aotearoa New Zealand, we hope to inspire geomorphologists to embark on research journeys in genuine partnership with Māori that promote toitū te mātauranga – the enduring protection, promotion and respect of mātauranga Māori.
Keywords: iwi governance; mātauranga māori; te ao Māori

Environmental and spatial planning with ngā Atua kaitiaki: A mātauranga Māori framework - Walker, Dean P.; Ataria, James M.; Hughey, Kenneth F. D.; Park, Patrick T.; Katene, John P. (New Zealand Geographer, 2021)
Internationally, Eurocentric hegemonies rooted in coloniality dominate the discourse on environmental wellbeing and sustainable development. Māori frameworks are being used and developed in Aotearoa New Zealand to support bicultural approaches to the management of natural resources and built environments. This paper reports on an Atua (Māori gods and spirits) framework that was found to be valuable as a cultural lens for the co-creation of a toolkit for assessing the wellbeing of indigenous forests. This article provides guidance on the development and application of kaupapa Māori frameworks, particularly Atua frameworks, in wider geographical contexts including urban design and spatial planning.
Keywords: bicultural; kaupapa māori; resource management; sustainable development

Reanimating the strangled rivers of Aotearoa New Zealand - Brierley, Gary J.; Hikuroa, Daniel; Fuller, Ian C.; Tunnicliffe, Jon; Allen, Kristiann; Brasington, James; Friedrich, Heide; Hoyle, Jo; Measures, Richard (WIREs Water, 2022)
Contemporary management practices have artificially confined (strangled) river systems in Aotearoa New Zealand to support intensified land use in riparian areas. These practices work against nature, diminishing the functionality and biodiversity values of living rivers, and associated socio-cultural relations with rivers. River confinement can accentuate flood risk by promoting development in vulnerable locations and limiting the flexibility to adapt to changing climate, prospectively accentuating future disasters. To date, uptake of space-to-move management interventions that seek to address such shortcomings is yet to happen in Aotearoa New Zealand. This is despite the fact that such practices directly align with Māori (indigenous) conceptualizations of rivers as indivisible, living entities. Treaty of Waitangi obligations that assert Māori rights alongside colonial rights of a settler society provide an additional driver for uptake of space-to-move initiatives. This article outlines a biophysical prioritization framework to support the development and roll out of space-to-move interventions in ways that work with the character, behavior, condition, and evolutionary trajectory (recovery potential) of each river system in Aotearoa. This article is categorized under: Water and Life > Conservation, Management, and Awareness Science of Water > Water and Environmental Change
Keywords: environment; environmental protection; mana moana; mana tupuna; mana whenua; mātauranga māori; tikanga | indigenous law; water management

Effecting Change Through Electoral Politics: Cutlural Identity and the Māori Franchise - Sullivan, Ann (Journal of the Polynesian Society, 2012)
Keywords: economic development; māori seats; social development; tino rangatiratanga; voting

Maori seeking self-determination or Tino Rangatiratanga? A note - Toki, Valmaine (2017)
Dr Nin Tomas wrote a considered and substantial piece entitled “Indigenous Peoples and the Māori: The Right to Self-Determination in International Law - From Woe to Go” for the New Zealand Law Review published in 2008.² In her conclusion she notes two ways in which self-determination has been implemented by the state: first, by “greater tolerance and benevolence along a series of principled guidelines”,³ and, second, as a “peoples-centred, enabling principle that allows Indigenous peoples to re-establish their social, economic and political institutions”.⁴ In 2010, New Zealand reversed its position and supported the United Nations Declaration on the Rights of Indigenous Peoples (the Declaration).5 With this in mind, this short piece revisits the notion of self-determination by examining the differing dynamics of concepts of external and internal self-determination before a short discussion on pluralism and the relationship between tino rangatiratanga and self-determination. In conclusion some thoughts are offered on a potential form of self-determination that could be consistent with the exercise of tino rangatiratanga.
Keywords: UNDRIP; autonomy; crown; sovereignty; tino rangatiratanga

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

The predictors of Māori electoral roll choice and knowledge: rangatahi Māori voter enrolment in a representative New Zealand youth survey - Greaves, Lara M.; Hayward, Janine; Barnett, Daniel; Crengle, Sue; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2023)
Every five years and when initially enrolling to vote, Māori have the choice between the Māori roll or the general roll. Research has explored the predictors of roll choice for older adults, but this paper presents the first exploration of roll choice for rangatahi Māori (Māori youth; aged 13–18), and the predictors of rangatahi not understanding the difference between rolls. We draw on Māori data (n = 1528) from Youth19 which surveyed students from a random sample of schools from Tai Tokerau, Tāmaki Makaurau, and Waikato. We find those Māori who also identify as Pākehā (New Zealand European) are less likely to opt for the Māori roll, but those who know their Iwi, are comfortable in Māori social surroundings, feel a spiritual connection to land and the presence of their ancestors in their lives, or feel the drive to be respected as Indigenous, are more likely to choose the Māori roll. Older rangatahi are more likely to say they understand the question, as are those with study plans post-secondary school, and who say they are comfortable in Māori social settings. These results contribute to a body of knowledge valuable for those seeking to increase voter enrolment and enrolment on the Māori roll.Glossary of Māori words: Hapū: kinship group, generally smaller than Iwi; sometimes translated to sub-tribe; hui: meeting; Iwi: broader tribal unit or grouping; nation; kaitiaki: guardian, steward, trustee; kanohi-ki-te-kanohi: face to face/in person; kapa haka: Māori performing arts; traditional performance; Kura Kaupapa Māori: Māori language/Māori medium schools; mana whenua: Māori group(s) who have authority, power, or rights over a certain area of land; marae: meeting house and the area surrounding it; mātauranga Māori: Māori ways of knowing/knowledge; Pākehā: New Zealanders of European descent; rangatahi: youth; rohe: area, region; tangata whenua: Indigenous peoples of Aotearoa New Zealand; people(s) of the land; te reo Māori: the Māori language; te Tiriti o Waitangi: the Māori language version of the Treaty of Waitangi; tīpuna/tupuna: ancestors; waka ama: canoe sport; wānanga: meetings for discussion, deliberation, forums; whanau: family, extended family, or family-like group; whanaungatanga relationship, kinship, sense of family-like connections between people.
Keywords: māori roll; political participation; rangatahi; tūpuna; voter enrolment; voting

Māori parliamentary seats - is their time up? - Kamo, Ward (Te Karaka: The Ngai Tahu Magazine, 2019)
Keywords: legislation; māori seats; māori voting; politicians

Dynamic and Interesting Events: The Nineteenth-Century Māori Elections - Warbrick, Paerau (New Zealand Journal of History, 2019)
The article discusses the history of the political participation of the Maori people of New Zealand in the 19th century which started with the creation of the Maori seats of Parliament under the Maori Representation Act 1867 (MRA). Topics discussed include the incorporation of MRA into the Electoral Act of 1893, the history of their voting rights, practices and election participation, and the issue of giving fair representation to Maori in the House of Parliament in 1862.
Keywords: government relations; history; māori seats; voting

The rights of indigenous peoples - Charters, Claire (New Zealand Law Journal, 2006)
Keywords: UNDRIP; māori rights; self-determination; tino rangatiratanga

Politics, Indigenous Rights and Resource Ownership: Māori Customary Rights to the Foreshore, Seabed and Fresh Water in New Zealand - Sullivan, Ann (Studies in arts and humanities, 2017)
Māori customary rights to natural resources are a contentious issue between Māori and the New Zealand government and between Maori and non-Māori. The values and principles inherent in a treaty signed in 1840 between Māori and the British Crown have been undermined by the government’s refusal to allow Māori the right to go to the courts to determine proprietary rights to the foreshore, seabed and fresh water. Discriminatory Crown actions highlight the argument that when an injustice occurs then reparations should be made. The United Nations has chided the New Zealand government for its discriminatory behaviour and failure to provide guaranteed redress but it has had little effect.
Keywords: civil Rights; crown policy; discrimination; environment; land rights; māori rights

Developments in Indigenous Peoples' Rights under International Law and their Domestic Implications - Charters, Claire (New Zealand Universities Law Review, 2005)

Indigenous peoples rights under international law - Adcock, Fleur; Charters, Claire (The New Zealand Yearbook of International Law, 2010)
In 2010 Indigenous peoples' rights continued to feature in discussions in a variety of international fora. Indigenous peoples' traditional knowledge (TK) associated with genetic resources (GR) were discussed under the Convention on Biological Diversity (CBD); under the auspices of the World Intellectual Property Office (WIPO) and within the World Trade Office (WTO). The United Nations (UN) General Assembly's Declaration on the Rights of Indigenous Peoples (Indigenous Peoples' Declaration) featured in debate under the UN Framework Convention on Climate Change (UNFCCC); the UN General Assembly's Third Committee; the work of the UN mechanisms with a specific mandate concerning Indigenous peoples; and, in a landmark ruling of the African Commission on Human and People's Rights (African Commission), was adopted by the African Union. International human rights monitoring bodies also advanced their jurisprudence on the rights of Indigenous peoples.
Keywords: UNDRIP; civil Rights; crown policy; discrimination; takutai moana; tiriti o waitangi/treaty of waitangi; united nations

Practicing Democracy from Childhood: Democratic Praxis in Te Ao Māori - Smith, Kylie; Napan, Ksenija; Perkinson, Raewyn; Hunter, Roberta (Democratic Theory, 2021)
Abstract Democracy manifests itself in a range of ways and is an imperfect, dynamic struggle for collective decision-making. This article discusses the multifaceted processes of deliberative democratic praxis found in traditional Māori society. Central to decision-making in te ao Māori, hui provide formal and informal structures for deliberative democracy, precedent setting, learning, and transformation through consensus making, inclusive debate, and discussion across all levels of society. Rather than coercion and voting, rangatira relied on a complex mix of customary values and accomplished oratory skills to explore issues in family and community meetings and in public assemblies. Decisions made through inclusive deliberative processes practiced in hui established evident reasoning and responsibility for all community members to uphold the reached consensus. This article claims that practicing deliberative democracy as a fundamental way of life, learned through ongoing active and meaningful participation throughout childhood, improves the integrity of democratic decision-making.
Keywords: democracy; purakau; rangatiratanga; tamariki

The Sweet Spot Between Formalism and Fairness: Indigenous Peoples’ Contribution to International Law - Charters, Claire (AJIL Unbound, 2021)
Standing back, the greatest influence of Indigenous Peoples on international law is our contribution to a pragmatically-driven yet conscious reframing of its foundations. Partly as a result of our participation in international law, it is changing its nineteenth and twentieth century state-centric, colonial, and positivist character to a more informal, flexible, and partially decolonizing system of law. In this way, Indigenous Peoples are crafting a legal system that achieves the “sweet-spot.” It has sufficient “hard-law” quality to restrain the self-interested instincts of powerful states—much needed by Indigenous Peoples seeking to realize their claims against states—and systemic inclusion and justice.
Keywords: co-governance; international law; kāwanatanga; rangatiratanga

An Imbalance of Powers: Maori Land Claims and an Unchecked Parliament - Charters, Claire (Cultural Survival, 2010)
Aotearoa/New Zealand is not known for egregious breaches of indigenous peoples’ rights. Nonetheless, New Zealand’s legal system is ineffective at implementing international and domestic laws that protect the rights of Maori. This has been seen most starkly in the Foreshore and Seabed Act of 2004, which had the effect of extinguishing Maori aboriginal title to the foreshore and seabed areas and was passed despite almost universal Maori opposition.
Keywords: civil Rights; constitution; crown policy; foreshore and seabed act 2004; parliament; tiriti o waitangi/treaty of waitangi; treaty settlements

Shaky Foundations: The fundamental flaw at the heart of a “model” treaty involving New Zealand and the Indigenous Māori community - Charters, Claire; Whare, Tracey (World Policy Journal, 2017)
In 1840, English officials on behalf of the British crown signed the Treaty of Waitangi—also known as Te Tiriti o Waitangi—with the Indigenous Māori population, affirming Māori sovereignty and guaranteeing their collective rights to the country’s land and resources. Since the 1700s, English settlers had been arriving in Aotearoa (the Māori name for New Zealand) to capitalize on the seal and whale trade. As the number of settlers increased, reports flowed back to Britain of general lawlessness and dubious private land deals, and the crown was forced to consider how best to control its citizens. A treaty with the Māori, officials decided, was the way to do so. The agreement, which established the basis for the relationship between the Māori and the British, is commonly cited as a shining example of how a treaty can recognize and protect Indigenous peoples’ rights by curtailing the reach of the state. But does te Tiriti live up to its sterling reputation? The answer, of course, is complicated.
Keywords: colonisation; crown policy; governance; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

The Rights of Indigenous Peoples Under International Law and Their Domestic Relevance in Aotearoa/New Zealand - Charters, Claire (SSRN Electronic Journal, 2016)

Maori rights: legal or political? - Charters, Claire (Public law review (North Ryde, N.S.W.), 2015)
Willingness of New Zealand courts to enforce legal rights where a political mechanism to address Maori rights exists - land rights - human rights - political rights - principles of the Treaty of Waitangi - takanga.
Keywords: crown law; human rights; land rights

Whakawhanaungatanga as a Māori Approach to Indigenous–Settler of Colour Relationship Building - Rata, Arama; Al-Asaad, Faisal (New Zealand Population Review, 2019)
Communities of colour are racialised and oppressed differentially by settler colonial states (Saranillio, 2013), yet the discourse of diversity and inclusion that dominates state interactions with communities of colour tends to conflate marginalised groups as equivalent and interchangeable to the detriment of intergroup relations. An approach to community building that recognises racial difference in general and the irreducibility of indigeneity in particular is needed if racialised communities are to create solidarities for transformative change. We engage Indigenous and settler colonial theories to address these imperatives, while noting the distinct character of these frameworks. In particular, we seek to highlight the specificity of indigeneity in settler colonial contexts, such as Aotearoa New Zealand, and to generate a model for relationship building that is not founded on settler colonial ideologies, by drawing on Indigenous concepts. Through thematic analysis of interviews with Māori community leaders, we explore Māori-–tauiwi (settler) of colour (ToC) relations. The results of our qualitative analysis provide evidence for Māori–ToC relations that are consistent with whanaungatanga (good relationships characterised as family-like, based on similar experiences, and bound in conditional solidarity; see Benton, Frame, and Meredith, 2013). Furthermore, we identify the following four aspects of whakawhanaungatanga (relationship building): positioning, power sharing, dialogue and cultural practice. Thus, we suggest whakawhanaungatanga as a Māori approach to relationship building with the potential to generate Indigenous–settler of colour solidarities towards transformative change.
Keywords: colonisation; diversity; relationship building; whanaungatanga

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Report from the inside: the CERD Committee's review of the Foreshore and Seabed Act 2004 - Charters, Claire; Erueti, Andrew (Law review (Wellington), 2005)
Describes, from the perspective of the advocates for Maori claimants, the substance of submissions to and process followed by the United Nations committee on the Elimination of Racial Discrimination (CERD) in determining that the Foreshore and Seabed Act 2004 discriminates against Maori. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: civil Rights; crown law; foreshore and seabed act 2004; human rights; international law; international organization; land rights; land tenure; racism

The Colonising Environment: an Aetiology of the Trauma of Settler Colonisation and Land Alienation on Ngāi Tahu Whanau - Reid, John; Rout, Matthew; Tau, Maire; Smith, Cherryl (UC Ngāi Tahu Research Centre, 2017)
Keywords: colonisation; crown policy; intergenerational trauma; land loss; racism

Whānau, Tikanga and Tino Rangatiratanga: What is at stake in the debate over the Ministry for Children? - Fitzmaurice, Luke (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: crown policy; crown violence; discrimination; rangatiratanga; self-determination; tamariki; tikanga | indigenous law; waitangi tribunal

Sport, Tribes, and Technology: The New Zealand All Blacks Haka and the Politics of Identity - Jackson, Steve; Hokowhitu, Brendan (Journal of Sport & Social Issues - J SPORT SOC ISSUES, 2002)
This study examines how global forces are shaping local indigenous cultures with a particular focus on the relationship between global capitalism, new media technologies, and transnational advertising. Concentrating on Mäori culture and identity in Aotearoa/New Zealand, the authors examine a contemporary political debate related to indigenous culture and intellectual property rights. Specifically, the study explores the politics of identity associated with global sports company Adidas and its use of the traditional New Zealand All Blacks haka as part of a global advertising campaign. A key feature of the analysis is the controversy surrounding a lawsuit filed by a Mäori tribe claiming compensation for the commercial use of its culture. Overall, the study highlights the problem of maintaining and protecting cultural spaces where indigenous identities can be constructed and affirmed.
Keywords: cultural appropriation; identity; intellectual property

Authenticating Mäori Physicality: Translations of ‘Games’ and ‘Pastimes’ by Early Travellers and Missionaries to New Zealand - Hokowhitu, Brendan (The International Journal of the History of Sport, 2008)
This paper theorizes how knowledge of indigenous tribal epistemologies was made ‘knowable’ through Enlightenment rationalism in an early colonial context. Specifically, the paper determines how and what knowledge of Mäori tribal physical activities was interpreted and authenticated through early travellers' tales and missionaries’ accounts in New Zealand. The central thesis argues that what was established as authentic and truthful aligned with Enlightenment rationalism, while those Mäori physical practices incomprehensible to Western understandings were deemed inauthentic and, consequently, were obscured and/or discarded. Throughout, the article theorizes the translation of knowledge into meaningful Western discourses and how these translations came to be crystallized in the colonial imagination.
Keywords: colonisation; cultural practices

Rangatiratanga and Ōritetanga: responses to the Treaty of Waitangi in a New Zealand study - Wyeth, Emma H.; Derrett, Sarah; Hokowhitu, Brendan; Hall, Craig; Langley, John (Ethnicity & Health, 2010)
Introduction. Although opportunities exist for positive experiences in research, Māori in New Zealand, like other indigenous people colonised by Europeans in the nineteenth century, have also been subject to research and associated policies that have had long-lasting negative consequences. Researchers have subsequently been challenged by Māori to conduct research that is acceptable, accountable and relevant. Much of this debate has taken place within the framework of the Treaty of Waitangi, a treaty of cession signed between Māori and British Crown representatives in 1840. Nowadays, health and health research statutes exist that require researchers to respond to the ‘principles’ of the Treaty. Few practical examples of how health researchers have undertaken this have been published. Aims. We examine how, in developing a national study of injury outcomes, we responded to the Treaty. Our study, the Prospective Outcomes of Injury Study, aims to quantitatively identify predictors of disability following injury and to qualitatively explore experiences and perceptions of injury outcomes. Discussion. Responses to the Treaty included: consultation with Māori groups, translation of the questionnaire into te reo Māori, appointment of interviewers fluent in te reo Māori, sufficient numbers of Māori participants to allow Māori-specific analyses and the inclusion of a Māori-specific qualitative component. While this article is located within the New Zealand context, we believe it will resonate with, and be of relevance to, health researchers in other former settler societies. We do not contend this project represents an ‘ideal’ model for undertaking population-based research. Instead, we hope that by describing our efforts at responding to the Treaty, we can prompt wider debate of the complex realities of the research environment, one which is scientifically, ethically and culturally located.
Keywords: bicultural; policy; power; rangatiratanga; research policy; tiriti o waitangi/treaty of waitangi

Producing Elite Indigenous Masculinities - Hokowhitu, Brendan (Settler Colonial Studies, 2012)
Keywords: colonisation; gender; identity; masculinity; sovereignty; tiriti o waitangi/treaty of waitangi

Seeing the unseen: evidence of kaupapa Māori health interventions - Rolleston, Anna K; Cassim, Shemana; Kidd, Jacquie; Lawrenson, Ross; Keenan, Rawiri; Hokowhitu, Brendan (AlterNative: An International Journal of Indigenous Peoples, 2020)
M?ori in Aotearoa have higher incidence, prevalence and mortality from chronic disease. The dominant narrative in Aotearoa about the reasons for M?ori ill health neglects to acknowledge the history of colonisation and failures of the health system, alongside the holistic view of health taken by M?ori focusing on collective, wh?nau-based outcomes. In this article, we review health interventions for chronic disease that have a kaupapa M?ori philosophical basis. Our findings demonstrate that there is no clear process in health service design, delivery, research and funding that values and understands m?tauranga M?ori. Western knowledge systems are inadequate for collecting and presenting M?ori knowledge. Overall, we highlight that the tension between acknowledging that a ?by M?ori, for M?ori? approach is best, and the difficulty in defining appropriate evidence collection methodology and outcome measures when funders and policy makers continue to require Western-centric interventions is an obstacle to improving M?ori health outcomes.
Keywords: health; health equity; kaupapa māori

Hā Ora: Reflecting on a Kaupapa Māori community engaged co-design approach to lung cancer research - Kidd, Jacquie; Cassim, Shemana; Rolleston, Anna; Keenan, Rawiri; Lawrenson, Ross; Sheridan, Nicolette; Warbrick, Isaac; Ngaheu, Janette; Hokowhitu, Brendan (2021)
Co-designed research is gaining prominence within the health care space. Community engagement is a key premise of co-design and is also particularly vital when carrying out kaupapa Māori research. Kaupapa Māori describes a “by Māori, for Māori” approach to research in Aotearoa/New Zealand. This article discusses the research process of Hā Ora: a co-design project underpinned by a kaupapa Māori approach. The objective was to explore the barriers to early presentation and diagnosis of lung cancer, barriers identified by Māori. The team worked with four rural Māori communities, with whom we aimed to co-design local interventions that would promote earlier diagnosis of lung cancer. This article highlights and unpacks the complexities of carrying out community- engaged co-design with Māori who live in rural communities. In particular, we draw attention to the importance of flexibility and adaptability in the research process. We highlight issues pertaining to timelines and budgets, and also the intricacies of involving co-governance and advisory groups. Overall, through this article, we argue that health researchers need to prioritise working with and for participants, rather than on them, especially when working with Māori communities.
Keywords: co-governance; health inequity; kaupapa māori; research

Mana motuhake, Indigenous biopolitics and health - Hokowhitu, Brendan; Oetzel, John; Jackson, Anne-marie; Simpson, Mary; Ruru, Stacey; Cameron, Michael; Zhang, Yingsha; Erueti, Bevan; Rewi, Poia; Nock, Sophie; Warbrick, Isaac (AlterNative: An International Journal of Indigenous Peoples, 2022)
The majority of Indigenous health models do not directly acknowledge that health is a contested political space. Providing a Foucauldian analysis, this article suggests a function of biopower is to naturalise discourses such as the poor M?ori health statistic to appear based on factual evidence and thus are apolitical. Employing Foucault?s triad of power?sovereign, disciplinary and biopower?to understand the genealogy of M?ori health, this article proffers mana motuhake (M?ori political self-governance) as an appropriate health analytic because it, first, identifies Indigenous health as political and, second, because it recognises the disempowering role that colonialism has played in relation to M?ori biopolitical self-governance. Hence, we suggest M?ori health will be enhanced by mana motuhake and that research underpinned by Indigenous agency and self-governance resists biopower. The article references two Ageing Well National Science Challenge?funded research projects because they innovatively fundamentalise mana motuhake and politics to Indigenous health.
Keywords: mana motuhake; māori health

Adaptation and implementation processes of a culture-centred community-based peer-education programme for older Māori - Simpson, Mary Louisa; Ruru, Stacey; Oetzel, John; Meha, Pare; Nock, Sophie; Holmes, Kathrine; Adams, Hariata; Akapita, Ngapera; Clark, Marama; Ngaia, Kawarau; Moses, Reuben; Reddy, Rangimahora; et al. (Implementation Science Communications, 2022)
Health inequities experienced by kaumātua (older Māori) in Aotearoa, New Zealand, are well documented. Examples of translating and adapting research into practice that identifies ways to help address such inequities are less evident. The study used the He Pikinga Waiora (HPW) implementation framework and the Consolidated Framework for Implementation Research (CFIR) to explore promising co-design and implementation practices in translating an evidence-based peer-education programme for older Māori to new communities.
Keywords: health inequity; research

Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management

Using mātauranga Māori to inform freshwater management - Harmsworth, Garth; Awatere, S.; Pauling, C. (Landcare Research Policy Brief, 2013)
Keywords: co-governance; environment; governance; hapū; iwi; kāwanatanga; local government; water management

What Is the Degree of Matauranga Maori Expressed through Measures of Ethnicity? - Awatere, Shaun (AlterNative: An International Journal of Indigenous Peoples, 2010)
This research hypothesized that respondents who have a good understanding of Matauranga Maori (Maori knowledge) are those with a secure cultural identity and are more likely to be concerned with the environment. A quantitative survey was carried out using two separate samples drawn from the Maori population; one from the general Maori population (N=331) in the city of Auckland and the other from a sub-tribe (N=61) whose traditional land has been encompassed by Auckland City. The responses from the survey presented a consistent environmental concern attitude across both samples and challenge a priori assumptions. The meaningfulness of a Maori cultural identity (MCI) measure to represent Matauranga Maori perspectives of the environment is discussed. The conclusion from the findings is that cultural identity is much more complex than an ordinal number and that caution should be used when employing the MCI measure.
Keywords: ethnic identity; identity; mātauranga māori

Integrating Indigenous Knowledge and Freshwater Management: An Aotearoa/New Zealand Case Study - Hudson, Maui; Watene-Rawiri, Erina; Robb, Mahuru; Collier, Kevin; Awatere, Shaun; Harmsworth, Garth; Henry, Jacqueline; Quinn, John; Death, Russell; Hamilton, David; Maru, John (The International Journal of Science in Society, 2016)
Keywords: governance; iwi; kāwanatanga; local government; treaty settlements; water management

A cause for nervousness: The proposed Māori land reforms in New Zealand - Warbrick, Paerau (AlterNative: An International Journal of Indigenous Peoples, 2016)
This commentary reflects upon the major Māori land reforms in te Ture Whenua Māori Bill (2016). The reforms implement more bureaucracy and replace some mechanisms used by the Māori Land Court to protect against Māori land loss. The Waitangi Tribunal, which has dealt with Māori grievances over land loss for over 30 years, issued a critical report in March 2016 along with recommendations about the reforms. That report was largely ignored by the New Zealand Government. This commentary contains a review of the literature on Māori land to date, as it helps to understand the ideas behind the Tribunal's report as well as the reforms. There is also an examination of the main points made by the Waitangi Tribunal, as well as aspects of te Ture Whenua Māori Bill (2016). The overall conclusion is that the Māori people should be very nervous about the reforms for their lands.
Keywords: land; land loss; land reforms

Price of citizenship for Maori: A matter of historical and legal context - Warbrick, Paerau (Law & History, 2021)
This article explains that the concept of citizenship for Maori in New Zealand has evolved. The 'Native Rights Act 1865' declared all Maori to be subjects of the Crown. This implication then justified the confiscation of lands in the 1860s from those Maori deemed to be disloyal to the Crown. By the beginning of the twentieth century, politicians began to use the concept of citizenship to force Maori to fight in World War I. In the mid-twentieth century, the Maori politician Apirana Ngata used the term 'price of citizenship' to gain social and political rights for all Maori, as a result of the efforts of Maori soldiers fighting as New Zealand citizens in World War II.
Keywords: citizenship; civil Rights; colonisation; military

Tracking Patterns of Tribal Identification in the New Zealand Census, 1991 to 2006 - Kukutai, Tahu; Rarere, Moana (New Zealand Population Review, 2013)
Keywords: census; identification; iwi; population

Reflections on Indigenous sovereignty - Kukutai, Tahu (Journal of Indigenous Wellbeing, 2019)
Keywords: data; data sovereignty; indigenous data sovereignty

Ngā kare ā-roto o ngā Kaipupuri Whenua - Dell, Kiri; Dell, Hinetu (MAI Journal, 2021)
Keywords: land loss; land ownership; te reo maori sources

Covenants, Treaties and the Politics of Reconciliation - O'Sullivan, Dominic (Uniting Church Studies, 2010)

Behind the wire: Māori women and prison - McIntosh, Tracey (Women’s Studies Journal, 2017)
Keywords: colonisation; crown policy; incarceration; prison; wāhine māori

The Orewa Speech - Crengle, Sue; Pelkowitz, Allan (THE NEW ZEALAND MEDICAL JOURNAL, 2004)

Ethnic Diversity in a Global Economy: A Case - Study of Māori Self Determination - Margaritis, Dimitris; Sullivan, Ann (The International Journal of the Humanities: Annual Review, 2005)
Keywords: sovereignty; tino rangatiratanga

Māori Issues, 2014-2015 - Mutu, Margaret (2016)
VoR - Version of Record

Māori issues 2015-2016 - Mutu, Margaret (2017)
https://muse-jhu-edu.ezproxy.auckland.ac.nz/article/646637

Māori Issues 2020-2021 - Mutu, Margaret (The Contemporary Pacific, 2022)

Behind the smoke and mirrors of the Treaty of Waitangi claims settlement process in New Zealand: no prospect for justice and reconciliation for Māori without constitutional transformation - Mutu, Margaret (Journal of Global Ethics, 2018)
Governments in New Zealand have legislated a large number of settlements extinguishing many hundreds of claims taken by Māori against the Crown for breaches of the country’s founding document, Te Tiriti o Waitangi. They portray settlements as a great success for Māori and the Crown. Māori disagree. Settlements are government-determined and imposed on Māori using a smoke and mirrors approach that masks successive governments’ true intentions: to claw back Māori legal rights; to extinguish all claims; and to maintain White control over Māori. In short, to uphold the Doctrine of Discovery in further breach of Te Tiriti o Waitangi. Māori claimants and negotiators report being enticed into the process by false promises only to become traumatised and disenchanted. Yet many take a pragmatic stance and sign settlements, making the best they can out of a bad deal that goes nowhere near compensating for their actual loss. They know that despite what legislation may say, the settlements are not full, not fair and not final and that, like all previous settlements, they will be revisited. They also know that unless fundamental changes are made to the constitutional makeup of the country, there is no prospect of justice and reconciliation for Māori.
Keywords: colonisation; constitutional transformation; doctrine of discovery; kāwanatanga; tiriti o waitangi/treaty of waitangi; trauma; treaty settlements; waitangi tribunal

Māori issues 2016-2017 - Mutu, Margaret (2018)
https://catalogue.library.auckland.ac.nz/primo-explore/fulldisplay?docid=uoa_alma21140132640002091&context=L&vid=NEWUI&search_scope=Combined_All&tab=combined&lang=en_US

The treaty claims settlement process in New Zealand and its impact on Māori - Mutu, Margaret (2019)
This article considers research conducted on the impact of the Crown’s treaty claims settlement policy on Māori in New Zealand. It provides a brief background to the Treaty of Waitangi and the subsequent British colonisation process that relied on the Doctrine of Discovery in breach of the treaty. It outlines how colonisation dispossessed Māori of 95 percent of their lands and resources, usurped Māori power and authority and left them in a state of poverty, deprivation and marginalisation while procuring considerable wealth, prosperity and privilege for British settlers. The work of the Waitangi Tribunal, the commission of inquiry set up to investigate those breaches, is considered, as is the Crown’s reaction to the 1987 Lands case in developing its treaty claims settlement policy. The Crown unilaterally imposed the policy despite vehement opposition from Māori. Since 1992, it has legislated more than seventy ‘settlements’. The research shows that overall, the process has traumatised claimants, divided their communities, and returned on average less than one percent of their stolen lands. Proposals for constitutional transformation have drawn widespread support from Māori as a solution to British colonisation. United Nations treaty-monitoring bodies have recommended that the government discuss this with Māori
Keywords: colonisation; constitutional transformation; crown policy; law; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Māori Issues 2017-2018 - Mutu, Margaret (2019)

Māori Issues - Mutu, Margaret (The Contemporary Pacific, 2021)
Keywords: covid-19; distribution; public health administration; safety and security measures; social sciences; statistics; tino rangatiratanga

‘To honour the treaty, we must first settle colonisation’ (Moana Jackson 2015): the long road from colonial devastation to balance, peace and harmony - Mutu, Margaret (Journal of the Royal Society of New Zealand, 2019)
Māori leaders in New Zealand continue the battle to end British colonisation. The aim is to restore the balance between Māori and the Crown guaranteed in the treaty that Māori and the British Crown agreed to in 1840 so that we can live in peace and harmony. Early European visitors subjected our ancestors to numerous atrocities. Relying on the Doctrine of Discovery, they illegitimately usurped our power and dispossessed us, leaving us in a state of poverty, deprivation and marginalisation. They fabricated myths to justify their criminal activities, set up an illegitimate parliament with unfettered powers, passed laws legalising their crimes and then covered it up with amnesia. They established the Waitangi Tribunal in 1975 to inquire into breaches of the treaty, not realising that it would dismantle the myths and look beneath the amnesia. Governments then instigated the ‘treaty claims settlement’ process to extinguish all Māori claims, remove Māori rights and entrench colonisation. Research undertaken has shown that Māori loathe this process and do not accept that settlements are full and final. Research on constitutional transformation has identified a possible solution. The first step towards that goal involves implementing the United Nations Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; colonisation; colonisation myths; constitutional transformation; crown; kāwanatanga; māori rights; oral history; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; treaty breaches; treaty settlements; waitangi tribunal

Neo-Liberal Settlements: From Adam Smith to Treaty Settlements - Tau, Te Maire (NZ Journal of History, 2015)
Keywords: kāwanatanga; sovereignty; treaty settlements

‘Ka Hoki A Kupe?’: The Political Career of Matiu Rata, 1963–1979 - McDowell, Tiopira (New Zealand Journal of History, 2015)

Diverting the Sword of Damocles: Why Did the Crown Choose to Settle Māori Historical Treaty Claims? - McDowell, Tiopira (Australian Journal of Politics & History, 2018)
Keywords: crown; treaty settlements

Taua nakahi nui: Maori, liquor and land loss in the 19th century - McDowell, Tiopira (AlterNative : an international journal of indigenous peoples, 2015)
This article outlines the fraudulent practices of settler traders and land agents who employed alcohol to facilitate the alienation of Maori lands, highlighting the close relationship between Maori, liquor and land loss in 19th century New Zealand. Traders and agents developed a range of strategies, forged in Britain, tempered by colonial experience and wielded with deft precision in New Zealand to defraud Maori of their lands. Government efforts to pre-empt and prevent the worst excesses of settler crime proved ineffectual, self-defeating, paternalistic and ultimately unenforceable. Maori came to regard settler practices, the successive failure of legislation to alleviate the problem, and state connections with the liquor industry to be part of a thinly veiled conspiracy to destabilize their communities and alienate their lands. While this conclusion is highly problematic, it is likely that traders and agents had witnessed or were aware of similar practices in the settler colonies of Australia, Canada and North America, and made good use of them in New Zealand to access Maori lands.
Keywords: alcohol; colonies; crown policy; government relations; land loss; land tenure; race relations

Teaching Diversity, Advancing Democracy: Challenges for Citizenship Education in Aotearoa New Zealand - Tawhai, Veronica M.H. (The International Journal of Diversity in Organizations, Communities, and Nations: Annual Review, 2008)
The presence of diverse needs, interests and perspectives in society is a key measure of a healthy representative democracy. Learning about diversity, and how society provides for diversity, is therefore a valuable characteristic of citizenship education (Arthur and Davison, 2000; Berding and Miedema, 1998; Feinberg, Fields and Roberts, 1997). This paper presents the findings of recent research about citizenship education in Aotearoa (New Zealand). In particular, it explores what presence the notion of diversity has in New Zealand’s citizenship education programme (social studies). In New Zealand, the provisions for diversity are under constant political debate. This includes the provisions for indigenous political representation, such as the Maori parliamentary seats. The research utilized critical discourse analysis and content analysis methods. A review of the social studies curriculum revealed a strong focus on identity, culture and heritage in New Zealand, but an absence of material about how diversity is provided for in society. This includes the socio-political provisions for diversity in New Zealand’s democratic arrangements, such as guaranteed indigenous representation. The implications of this absence are discussed in terms of citizens’ understandings of democracy, equality, and the preparation of citizens to discuss these issues further.
Keywords: citizenship; civics; diversity; education; equality

Civics and citizenship education in Aotearoa New Zealand : multidimensional challenges. - Tawhai, V. M. H. (Social Educator, 2008)
This paper presents the findings of research about civics and citizenship education in Aotearoa New Zealand. Aspects of New Zealand's electoral system, such as the Maori representation, have long been the focus of political debate. This paper identifies the civics and citizenship education provided to New Zealand citizens about this debate. In New Zealand, civics and citizenship education is taught through the social studies curriculum. A review of the teaching units for social studies showed a considerable focus in New Zealand on aspects of citizenship such as identity, but an absence of material for civic knowledge such as the make-up of the electoral system. This absence includes a lack of material on the Maori electoral representation. These challenges are considered in context of the multidimensional citizenship model arising from the international Citizenship Education Policy Study (CEPS).
Keywords: civics; curriculum; education; māori electorates; political parties; political power; political socialisation

Tino rangatiratanga : water under the bridge? - Bargh, Maria (He pūkenga kōrero: a journal of Māori studies, 2007)
Argues that Māori have been actively engaged in practising tino rangatiratanga in various forms even since before the Declaration of Independence ...
Keywords: colonisation; constitution; government; international relations; iwi; kaitiakitanga; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

The Māori Electoral Option: How can trends in roll choices be explained? - Bargh, Maria (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
The Mäori Electoral Option is a period of 4 months, every 5 years, when Mäori electors can choose whether to be on the Mäori or the General Electoral Roll. The outcome of the Mäori Electoral Option is a key factor in determining the number of Mäori seats in the New Zealand Parliament. The Electoral Commission estimates that approximately 6,000 Mäori voters each year request to change electoral roll, but in 2017 over 19,000 voters applied to change. Why were so many more Mäori wanting to change and why did they not know they could only change during the Mäori Electoral Option held every 5 years? The following year, the 2018 Mäori Electoral Option saw the first net increase of Mäori changing to the general roll since 1996. This article uses data gathered from the results of Mäori Electoral Options 1991–2018, an anonymous survey, and evaluations of Mäori Electoral Option campaigns to consider how the shifting trends in roll choices might be explained.
Keywords: elections; kāwanatanga; māori electorates; māori seats; voting

Indigenous Forms of Organization: Transforming Economies and Economics - Ruwhiu, Diane Rongo; Carter, Lynette; Amoamo, Maria; Bargh, Maria; Ruckstuhl, Katharina; Carr, Anna; Awatere, Shaun (Academy of Management Proceedings, 2019)
In this paper, we emphasis a critical perspective on inclusive organizations by taking an Indigenous perspective. The diverse economies framework, which acknowledges economic and non-economic activity, provides a lens through which we counter the dominant Western construction of organization and economy, bringing to the fore forms of organization and practice all too often hidden, viewed as alternative and therefore deemed inferior. In this paper we present the notion of alternative economic and organizational forms drawn from Indigenous Maori theories, models and mechanisms of practice. This paper presents preliminary findings from a study that explored the diversity of Maori organizational forms, in this instance a case study on Maori weavers, who use traditional knowledge, to support social, cultural, environmental and economic outcomes for themselves and their communities. Our contribution is two-fold: First we offer insight into the theorisation and practice of organization studies in general by giving weight to the processes and relations of socio-cultural exchange that occur in localised settings. Second, we suggest that socio-cultural system of knowledge and values, offers insight into forms of organization that could be considered to be reflective of inclusive organizations.

Reflections: Land is Never Just Land - Bargh, Maria; Weavers, Lydia (Women Talking Politics 2019, 2019)
Keywords: land; resource management; te ao Māori

Participation as exclusion: Māori engagement with the Crown Minerals Act 1991 Block Offer process - Bargh, Maria; Wagner, Estair Van (Journal of Human Rights and the Environment, 2019)
Land and natural resources are at the core of conflicts between Indigenous peoples and Settlers in settler-colonial nations. This article explores the coloniality of natural resource law in the context of the New Zealand Crown Minerals Act 1991 (CMA) Block Offer process; the annual tender process for mineral prospecting and exploration. While there is often strong Māori participation, we will argue that Aotearoa New Zealand settler-colonial mining law is structured in such a way that Māori views rarely influence the substantive outcomes of mineral exploration decisions. Through a case study of the 2013 Epithermal Gold Block Offer in the Central North Island, we will explore the factors that might contribute to the mismatch between the level of Māori participation and the influence of Māori views on final decisions in the Block Offer process. We examine how different views are valued by bureaucrats within New Zealand Petroleum and Minerals, a government agency within the Ministry of Business, Innovation and Employment, and explore whether the criteria applied to Māori submissions genuinely and appropriately reflect the full range of interests, aspirations and concerns raised by Māori participants. In particular, we consider how mining regulation is structured to exclude Māori law and jurisdiction in order to uphold settler-colonial authority over key natural resources and extractivist economies. Finally, we consider alternatives to the CMA process and explore the potential to ensure substantive outcomes that better reflect the Māori views and interests. In doing so we point to the need to shift from colonial extractivist models of natural resources law towards Settler-Indigenous partnerships in relation to environmental planning in settler-colonial states.
Keywords: crown policy; land policy

The political constitution: from Westminster to Waitangi - Godfery, Morgan (Political Science, 2016)
Drawing on the work of Matike Mai Aotearoa: The Independent Iwi Working Group on Constitutional Transformation (the Working Group), this article argues that there is an evolving New Zealand constitutionalism, one that offers a constitutional understanding grounded in the Māori constitutional system. The article opens with a descriptive analysis of the Māori constitutional system, explains the key features of New Zealand’s existing constitution and concludes with an argument that the existing constitution can evolve – and, through the political process, ought to evolve – according to the constitutional models that the Working Group recommends. This article deploys legal research methods, primarily doctrinal research and applied doctrinal research.1
Keywords: constitution; kāwanatanga; rangatiratanga; tikanga | indigenous law

The Crown: Is It Still ‘White’ and ‘English-Speaking’? - Godfery, Morgan (The Round Table, 2018)
‘There is a need for a mindset shift away from the pervasive assumption that the Crown is Pākehā, English-speaking, and distinct from Māori’, wrote the permanent commission of inquiry investigating breaches of New Zealand’s founding document, the Treaty of Waitangi. ‘Increasingly, in the twenty-first century, the Crown is also Māori.’ This paper argues that ‘the Crown in right of New Zealand’ is in need of redefining. In the 19th and parts of the 20th century Māori leaders and institutions were often understood as separate from the Crown. But that understanding is shifting, and this paper argues the shift is leading to a new understanding of the Crown in right of New Zealand.
Keywords: crown; kāwanatanga; kīngitanga; rangatiratanga

Disaster? No surprise - Winter, Christine J. (Environmental Politics, 2022)
I argue environmental disasters are an inevitable outcome of the underdevelopment of Western philosophy. Human induced environmental disasters are unfortunate, an unintended consequence of focusing on economic maximization in a culture without comprehensive, clearly accepted, and operationalized frameworks for environmental and intergenerational justice. However, they are of no surprise to Indigenous Peoples relegated to margins of political influence. Grounding this claim, I examine the New Zealand High Court case Greenpeace and Te Whanau-ā-Apanui vs the Minister for Energy. Case documents afford comparisons between the complex philosophic, legal, and cultural framework of Māori, that protect human and nonhuman from human-induced environmental disaster, and the dominant Anglo framings. I observe a philosophical deficit underpinning the legal and political system of Aotearoa that impedes environmental intergenerational justice. These philosophic foundations, intentionally or not, promote environmental disaster and – nationally and internationally – claim a dominant position over Indigenous systems.
_eprint: https://doi.org/10.1080/09644016.2020.1865726
Keywords: disasters; environment; environmental justice; liberalism

Māori News is Bad News : That's certainly so on television - Moewaka Barnes, Helen; Nairn, Ray; Borell, Belinda; Gregory, Amanda; McCREANOR, TIMOTHY (MAI Journal, 2012)
A television news bulletin tells us, in effect, what we should think about and the preferred way in which we should think about it. Analyses of New Zealand media have consistently shown that news about Māori is both relatively rare and that it prioritises violence and criminality. Researchers conclude this encourages New Zealanders to see Māori as threatening the social order and burdening our society. We examined the few Māori stories broadcast in a large representative sample of English-language television news bulletins and found the same negativity. As our sample included Māori-language news bulletins from the same days we know there were other Māori news stories available, so we conclude that the prioritising of negative stories about Māori in English-language media is a matter of choice. Focus groups with Māori and non-Māori media consumers demonstrate the impact of the relentlessly negative portrayals of Māori in New Zealand media.

Tiers of Confusion and Blurring Boundaries: Maori, the Local Government Act 2002 and the General Agreement On Trade in Services (Gats) - Bargh, Maria (Political Science, 2004)
In December 2002 a new Local Government Act was passed into statute. Much of the literature, submissions, articles and commentaries leading up to the passing of the Act indicated that a new Act had to clarify the relationships and obligations between local government, the Crown, Maori and the Treaty of Waitangi. In this paper I argue that the new Act has not adequately clarified these relationships and obligations, and that there are particular reasons and consequences arising from this situation. The reasons surround denials from local government that they are the Crown and central government's vested interest in allowing slippage to continue. If we examine the example of the General Agreement on Trade in Services we can see that a failure to clarify the relationships may have detrimental consequences for Maori to protect their rights.
Keywords: crown policy; kāwanatanga; local government; tiriti o waitangi/treaty of waitangi

Changing the game plan: The Foreshore and Seabed Act and constitutional change - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2006)
The Foreshore and Seabed Act 2004 caused many New Zealanders grave concern. In this article I suggest that a number of the Government's actions since the passing of the Foreshore and Seabed Act bring into question several of its central claims for legislating and the subsequent overriding of Tiriti o Waitangi and human rights laws. As a result, I argue that the inadequacy in our constitutional arrangements requires a change of approach—a new game plan: constitutional change. The second part of the article examines the work of the Maori Party. Its actions in encouraging an increasing level of Maori politicisation away from expression outside the State and towards the electoral process, arising out of opposition to the Foreshore and Seabed Act, constitute another changing of game plans. The article concludes by emphasising how the Foreshore and Seabed Act has encouraged us to take a longer term vision in order to foster more positive relations, a vision that encompasses the need for genuine constitutional change based on respect for human rights and Te Tiriti o Waitangi.
Keywords: constitutional transformation; crown policy; foreshore and seabed act 2004; institutional racism; kāwanatanga; political activity; te pāti māori; treaty obligations

Multiple sites of Māori political participation - Bargh, Maria (Australian Journal of Political Science, 2013)
This article examines what might be included in a definition of Māori political participation that moves beyond a predominant focus on voting in New Zealand general elections. I suggest that the proliferation of Māori governance organisations in recent years means that Māori participation within these organisations must also be considered as part of wider political participation. In addition, I argue that Māori engagement with local authorities deserves further close examination to explore the multiple ways in which political participation occurs. Using a broader definition of Māori political participation and highlighting its many facets indicate that Māori engage in more varied ways in New Zealand politics than previously recognised
Keywords: kāwanatanga; local government; local politics; political participation; tino rangatiratanga; voting

Māori Experiences and Responses to Racism in Aotearoa New Zealand - Moewaka Barnes, Angela; Taiapa, Ken; Borell, Belinda; McCreanor, Tim (MAI Journal, 2013)
When racism is promulgated on a number of fronts, including the media, it becomes a powerful and pervasive force in society, detrimentally impacting on the lives of those who are its object. This paper analyses Mäori focus group interviews that traversed a wide range of sites where racism occurred, including print and broadcast media. We utilised a framework for understanding racism that is in line with key racism theorists and identiﬁes four primary levels through which it operates: internal, interpersonal, institutional and societal. The core themes to emerge in the ﬁndings reinforce this framework and have been grouped accordingly: Internalised Racism, Interpersonal Racism, Institutional Racism and Societal Racism. Negative effects on health and wellbeing were articulated by participants as was the call for transformative, counter hegemonic representations of Mäori.

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting

Special issue: decolonising the discipline: rethinking political science in Aotearoa New Zealand - Bargh, Maria (Political Science, 2017)

Māori as “Warriors” and “Locals” in the Private Military Industry - Bargh, Maria; Whanau, Quentin (Wicazo Sa Review, 2017)
Keywords: identity; international relations; military

How should we teach about Te Tiriti o Waitangi? Issues for raraunga (citizenship) education - Bargh, Maria; Macfarlane, Angus (Our Civic Future, 2018)
Keywords: colonisation; policy; tiriti o waitangi/treaty of waitangi

Māori political and economic recognition in a diverse economy - Bargh, Maria (The Neoliberal State, Recognition and Indigenous Rights, 2018)
Keywords: iwi enterprises; tino rangatiratanga

Theorising the structural dynamics of ethnic privilege in Aotearoa: Unpacking “this breeze at my back” - Moewaka Barnes, Helen; Borell, Belinda; Mccreanor, Tim (International Journal of Critical Indigenous Studies, 2014)
Colonial praxis has been imposed on the culture, epistemologies and praxis of indigenous Maori in Aotearoa, entrenching the settler cultural project that ensures the continuation of the colonial state, producing damaging disparities. This article theorises ways in which settler privilege works at multiple levels supporting settler interests, aspirations and sensibilities. In institutions, myriad mundane processes operate through commerce, law, media, education, health services, environment, religion and international relations constituting settler culture, values and norms. Among individuals, settler discursive/ideological frameworks are hegemonic, powerfully influencing interactions with Maori to produce outcomes that routinely suit settlers. In the internalised domain, there is a symbiotic sense of belonging, rightness, entitlement and confidence that the established social hierarchies will serve settler interests. This structure of privilege works together with overt and implicit acts of racism to reproduce a collective sense of superiority. It requires progressive de-mobilising together with anti-racism efforts to enable our society to move toward social justice.
Keywords: belonging; health; inequity; privilege; racism; wellbeing

The Association of Crime Stories and Maori in Aotearoa New Zealand Print Media - McCreanor, Timothy; Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; Nairn, Raymond; McManus, Anna-Lyse (Sites: A Journal of Social Anthropology and Cultural Studies, 2014)
This paper explores associations between crime reporting and Maori ethnicity in a large representative sample of newspaper items gathered in Aotearoa New Zealand between November 2007 and April 2008, using content, thematic and discursive analyses and audience interpretations. The association of Maori and crime was prominent in these newspapers and Maori were frequently labelled as possible or actual perpetrators of crime on superficial judgements, often by victims. This practice associates Maori with all accounts of crime and embeds crime as a background for all other items about Maori. In contrast, newspaper coverage of Pakeha perpetrators of a crime against a Maori organisation worked to valorise the convicted thieves. This embedding of crime as a background to other stories about Maori, the pervasive but unacknowledged Pakeha1 norms, and media positioning of Maori as a threat in non-crime stories, is central to hegemonic discourses of Maori-Pakeha relations. Focus groups participants indicated that these discourses support real-world marginalisation and discrimination against Maori in Aotearoa New Zealand.
Keywords: crime; news media; racism

Who are the Māori “in-between”? Indigenous diversity and inequity across descent, ethnicity and Iwi knowledge - Greaves, Lara M.; Lindsay Latimer, Cinnamon; Li, Eileen; Hamley, Logan; Renfrew, Larissa; Sporle, Andrew; Milne, Barry (Ethnic and Racial Studies, 2023)
Policies increasingly reinforce the self-determination of Indigenous peoples, but issues remain around group definitions. Colonization has led to (de)identification with Māori (New Zealand's Indigenous peoples) identity markers. We explore differences between Māori on combinations of descent, ethnicity and Iwi (extended kinship group) knowledge in the 2013 Census, and self-reported discrimination. There were six groups within the Māori descent population: two did not know their Iwi – some identified solely as Māori ethnicity (2.8 per cent) – or Māori plus another ethnicity(-ies; 6.8 per cent); two did not identify as Māori ethnicity: more named their Iwi (7.2 per cent), than not (6.9 per cent); the largest groups knew their Iwi and identified as Māori ethnicity, either solely (30.8 per cent), or alongside another ethnicity(-ies; 34.3 per cent). We found a pattern of differences across demographics and discrimination, highlighting the complexity of Māori identity and the need to account for differences within Indigenous groups.
Keywords: crown policy; discrimination; ethnic identity; identity; whakapapa

Suburban Newspapers’ reporting of Māori news - Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; McCreanor, Tim; Nairn, Raymond; Gregory, Amanda (Pacific Journalism Review : Te Koakoa, 2011)
A content analysis of editorial items about Māori issues and the Treaty of Waitangi in 14 Suburban Newspaper publications in Auckland and Northland found a low proportion of articles about these issues, despite high proportions of Māori resident in several areas served by these publications. Stories included a higher proportion of apparent news releases compared to a national sample of non-daily papers. Māori perspectives came largely from sources representing pan-Māori non-government organisations; Suburban Newspapers used a low proportion of iwi and hapū sources compared with other community papers. Use of te reo Māori was low, and there were no signs of attempts to support readers in learning or increasing their understanding of te reo Māori. This article concludes that Māori and non-Māori readers are poorly served by the poverty of Suburban Newspapers’ reporting of Treaty and Māori issues.
Keywords: media; representation; te reo māori

Identity and demographics predict voter enrolment on the Māori electoral roll: Findings from a national sample - Greaves, Lara; Osborne, Danny (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
Keywords: identity; māori electorates; voting; voting enrolment

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori

Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination

The Treaty of Waitangi in Contemporary New Zealand Politics - O'Sullivan, Dominic (Australian Journal of Political Science, 2008)
This paper identifies three discourses that are prominent in contemporary Treaty of Waitangi policy debate, each with significantly different implications for Maori political status within the modern nation-state. At one extreme the Treaty's significance is exaggerated by overemphasis on partnership as an implicit Treaty principle. At another extreme the Treaty's significance is understated by an assimilationist position that denies the Treaty's relevance to Indigenous rights which, in turn, imposes serious constraint on the extent to which partnership can actually develop into comprehensive policy practice. An alternative position is one that sees the Treaty, which is supported in international law, as affirming a twofold conception of citizenship as the basis of both individual and collective Maori rights.
Keywords: māori rights; partnership; tiriti o waitangi/treaty of waitangi; treaty obligations

Needs, Rights and "One Law for All": Contemporary Debates in New Zealand Maori Politics - O'Sullivan, Dominic (Canadian Journal of Political Science / Revue canadienne de science politique, 2008)
This paper examines contemporary debates in Maori politics by responding to the argument of the former leader of the opposition National party, Don Brash, that Maori public policy is most properly based on "need" alone because indigenous status offers no "rights" beyond those of common national citizenship. The paper's alternative argument is that the politics of indigeneity and associated theories of self-determination provide a way of avoiding a general belief that addressing need is all that is required to include Maori fairly in the national polity. It is argued that Maori ought to enjoy rights of indigeneity as the basis of an inclusive, cohesive and fair society. /// Cette étude examine certains débats dans le domaine de la politique maorie en répondant aux propos de l'ancien chef du parti National, Don Brash, selon qui la politique publique maorie se baserait le plus aptement sur la notion du seul 'besoin', le statut de peuple indigène ne conférant aucun 'droit' au-delà de ceux qu'accorde la citoyennenté nationale régulière. Nous proposons par contre que la politique de l'indigénéité et les théories de l'auto-détermination qui y sont associées constituent un moyen de parer à une croyance généralisée qu'il suffirait de suppléer au besoin pour inclure avec justice les Maoris dans la politique nationale. Nous démontrerons que dans une société inclusive, cohésive et juste, les Maoris devraient jouir des droits accordés par l'indigénéité.
Keywords: māori rights; protest; racism; ōrewa speech

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements

Globalization and the Politics of Indigeneity - O'Sullivan, Dominic (Globalizations, 2012)
Indigenous peoples inevitably associate globalization with imperial expansion and the colonization of their territories. One associated scholarly view is that globalization's focus on capital accumulation sets aside indigenous cultural priorities to undermine self-determining authority over lands and resources (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a, 2005b; Stewart-Harawira, 2005). Alternatively, globalization is an ambiguous paradox also providing significant benefits to indigenous peoples. In two very different Pacific countries, Fiji and New Zealand, the globalization of political and jurisprudential thought on the rights of indigeneity provides a significant counter to state assertions of absolute sovereignty. Globalization creates economic opportunities to reduce indigenous dependence on the state and in its contemporary expression is less significant than domestic factors in inhibiting indigenous aspirations. Inevitablemente, la población indígena asocia a la globalización con la expansión imperial y la colonización de sus territorios. Una visión académica asociada es que el enfoque de la globalización en la acumulación de capital, desestima las prioridades culturales indígenas para entorpecer la autoridad autodeterminante sobre la tierra y los recursos. (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). Por otro lado, la globalización es una paradoja ambigua que también provee beneficios a las poblaciones indígenas. En dos países diferentes del Pacífico, Fiyi y Nueva Zelanda, la globalización del pensamiento político o jurisprudencial sobre los derechos del indigenismo, provee una lucha importante contra las afirmaciones estatales de una soberanía absoluta. La globalización crea oportunidades económicas para reducir la dependencia indígena del estado y su expresión contemporánea es menos importante que los factores domésticos que inhiben las aspiraciones indígenas. 伴随着帝国的扩张和其领土的被殖民化，土著居民无可避免地被卷入全球化中。一种相关学术观点认为，全球化对资本积累的关注不顾土著民的文化优先权，损害了土著民对土地和资源的自决权力。（Fenelon 和 Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005）另一种观点认为，全球化是一种不确定的悖论, 也为土著民带来了巨大利益。在两个截然不同的太平洋国家———斐济和新西兰，关于土著民权利的政治和法律思考的全球化对国家声称的绝对主权提出了挑战。全球化为土著民减少对国家的依赖创造了经济机遇；而且在抑制土著民的权利主张方面，其当今表现作用不及国内因素显著。 원주민들은 불가피하게 세계화를 제국주의적 팽창과 영토의 식민화와 연계시킨다. 관련된 학술적 견해는 자본축적에 초점을 맞춘 세계화가 토지와 자원에 대해서 자결 권위를 약화시키 위하여 원주민들이 문화적으로 우선시 하는 사항을 제켜 놓는다는 것이다 (Fenelon and Hall, 2008; Friedman, 1999; Kelsey, 2005a; 2005b; Stewart-Harawira, 2005). 대안적으로 세계화는 원주민들에게 상당한 이익을 가져다 주는 애모보호한 패러독스이다. 서로 다른 두 태평양 국가인 피지와 뉴질란드에서 원주민의 권리에 대한 정치적, 법률적 사유의 세계화는 절대적 주권을 주장하는 것에 대한 중요한 반론을 제공한다. 세계화는 국가에 의존하는 원주민들의 종속성을 약화시키는 경제적인 기회를 만들고 또한 현대적인 표현으로 내생적인 갈망을 금지시키는데 국내적인 요인들보다 덜 중요하다.
Keywords: globalisation; government; rangatiratanga; sovereignty

Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

The Role of Biodiversity in Maori Advancement: A Research Framework. - Harmsworth, Garth (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: biodiversity; environment; planning; sustainable development

A difference of perspective? Māori Members of Parliament and te ao Māori in Parliament - White, Te Hau (Political Science, 2016)
This article will aim to determine the form and place of te ao Māori in the New Zealand Parliament. The article will analyse the maiden speeches of 12 Māori Members of Parliament from across the political spectrum and from different Parliaments since the adoption of Mixed Member Proportional Electoral System in 1996, and will investigate their commitment to te ao Māori based on deductive and inductive discourse analysis. It seeks to determine the presence of Māori identity indicators, as well as to determine themes unique to the Māori political context. The election of the 51st New Zealand Parliament was noted as having the greatest representation of Māori of any parliament in New Zealand history. Of the 121 Members of Parliament, 26 identify as Māori or as having Māori heritage. However, while the number of Māori Members of Parliament has increased, this does not provide the full picture of Māori representation in Parliament. This article will ask ‘How do Māori Members of Parliament best represent te ao Māori in the New Zealand Parliament?’. The research considers how Māori Members of Parliament ‘represent’ Māori in the debating chamber in Parliament, specifically, to what extent these Members of Parliament represent te ao Māori. This research also asks whether substantive representation of te ao Māori varies across the electorate types, Māori, general and list seats. The research seeks to provide qualitative analysis of the presence of te ao Māori in Parliament and which Members of Parliament most often represent a Māori worldview. Both descriptive and substantive representation provide the means for a minority perspective to be present within a parliament.
Keywords: government; kāwanatanga; political perspective; te ao Māori

Opinion: Decriminalise cannabis, decriminalise Maori? - Kaa, Hirini (Matters of Substance, 2014)
That Maori are more often criminalised for cannabis use is often used as another good argument for decriminalisation. But Hirini Kaa argues things are more complex and that, as many Maori probably know, decriminalisation won't be the panacea proposed so often by privileged pakeha.
Keywords: cannabis; decriminalization; discrimination; social conditions

Marginalised: An Insider’s View of the State, State Policies in New Zealand and Gang Formation - McIntosh, Tracey; Andrae, Dominic; Coster, Stan (Critical Criminology, 2017)
Following the annexation of Aotearoa/New Zealand by the British in 1840, Māori, as the Indigenous people of that country, experienced loss of sovereignty through the imposition of and application of new and transformative policies, including the law and unfamiliar legal and social codes. This paper considers the state and the influential legacy of an imposed, Settler-state social welfare and criminal justice system on Māori. An explicit, insider narrative will highlight how suppression, disconnection and abandonment, made manifest through particular and abusive state policies, has informed and constructed the life pathway of a member of a culturally and socially-submerged population, the Mongrel Mob gang.
Keywords: child welfare; criminal justice system; crown policy; foster care; gangs; incarceration; social welfare

Indigenous Insider Knowledge and Prison Identity - McIntosh, Tracey; Coster, Stan (Counterfutures, 2017)
This article draws on the personal experiences and state documentation of Stan Coster (Ngāti Kahungungu) whose life has been characterised by different forms of state confinement, including over 25 years in prison serving both short and long lags. Through the use of the Official Information Act, Stan recovered state documentation on himself spanning over 40 years. Stan is not a research participant, but a full research collaborator and is engaged in all elements of this paper, so while not a writer he is both auteur and author of this piece. Stan’s story is his own and yet many of its features speak to a much broader collective experience. His prison identity and gang identity can be seen as being both informed and generated by state sponsored activity. By traversing the issues that pertain to the crisis of mass imprisonment, Māori disproportionality in the prison system, the contribution of the state to prison, and gang identity, we look at the possibilities of drawing on knowledge acquired under conditions of state constraint.
Keywords: crown policy; crown violence; identity; incarceration; marginalisation; prison

Mana whenua, mana moana, mana tinana, mana momona - Gillon, Ashlea; Le Grice, Jade; Webber, Melinda; McIntosh, Tracey (New Zealand Sociology, 2022)
The ways in which we understand bodies and fatness are complex. While coloniality unduly influences and shapes normative meanings of the body in everyday contexts, Maori conceptualisations of the b...
Keywords: identity; self-identification; te ao Māori

Anti-Colonial Abolitionism: International Context - Pranteau, Sheri; McIntosh, Tracey; Anthony, Thalia; Chartrand, Vicki (Journal of Prisoners on Prisons, 2022)
Keywords: colonisation; crown policy; prison abolition; racism; systematic racism

The Multi-Dimensional Model of Māori Identity and Cultural Engagement - Houkamau, Carla A; Sibley, Chris G (New Zealand Journal of Psychology, 2010)
Keywords: census; identity

Social identity and differences in psychological and economic outcomes for mixed and sole-identified Māori - Houkamau, Carla A.; Sibley, Chris G. (International Journal of Intercultural Relations, 2014)
Māori are the indigenous peoples of New Zealand and are culturally and ethnically diverse. Previous research suggests that Māori who identify jointly as European (New Zealand's dominant group) may have improved employment outcomes, income and levels of education relative to those who identify solely as Māori. However, research exploring the broader constellation of factors linked to multiple versus sole-ethnic affiliation for Māori remains scarce. We examine differences in outcomes for Māori depending upon their single versus multiple ethnic affiliation as Māori, Māori/European, or European (but with Māori ancestry) in a national probability sample (N=1416). Results indicated that people who identified jointly at Māori/European expressed political attitudes more aligned with Europeans. However, while Māori/Europeans may be more aligned with other Europeans in terms of support for mainstream political parties and intergroup attitudes, they remained lower on various indicators of social and economic status. In this latter regard, Māori/Europeans reported outcomes more similar to their sole-Māori counterparts.
Keywords: ethnicity; health; identity; ideology; wellbeing; whakapapa

Perceived discrimination predicts increased support for political rights and life satisfaction mediated by ethnic identity: A longitudinal analysis - Stronge, Samantha; Sengupta, Nikhil K.; Barlow, Fiona Kate; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (Cultural Diversity and Ethnic Minority Psychology, 2016)
Objectives: The aim of the current research is to test predictions derived from the rejection-identification model and research on collective action using cross-sectional (Study 1) and longitudinal (Study 2) methods. Specifically, an integration of these 2 literatures suggests that recognition of discrimination can have simultaneous positive relationships with well-being and engagement in collective action via the formation of a strong ingroup identity. Method: We test these predictions in 2 studies using data from a large national probability sample of Māori (the indigenous peoples of New Zealand), collected as part of the New Zealand Attitudes and Values Study (Ns for Study 1 and 2 were 1,981 and 1,373, respectively). Results: Consistent with the extant research, Study 1 showed that perceived discrimination was directly linked with decreased life satisfaction, but indirectly linked with increased life satisfaction through higher levels of ethnic identification. Perceived discrimination was also directly linked with increased support for Māori rights and indirectly linked with increased support for Māori rights through higher levels of ethnic identification. Study 2 replicated these findings using longitudinal data and identified multiple bidirectional paths between perceived discrimination, ethnic identity, well-being, and support for collective action. Conclusion: These findings replicate and extend the rejection-identification model in a novel cultural context by demonstrating via cross-sectional (Study 1) and longitudinal (Study 2) analyses that the recognition of discrimination can both motivate support for political rights and increase well-being by strengthening ingroup identity. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; community; discrimination; ethnic identity; hauora; identity; protest

Indigenous identity and environmental values: Do spirituality and political consciousness predict environmental regard among Māori? - Cowie, Lucy J.; Greaves, Lara M.; Milfont, Taciano L.; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2016)
Indigenous peoples often have a unique and deep connection to the land. However, quantitative research exploring this issue is scarce. The current research investigates cultural variation in environmental regard in New Zealand, where more recent settler groups have questioned the strength of Indigenous environmental regard. Study 1 examined differences in environmental regard held by Indigenous and non-Indigenous ethnic groups in a nationally representative data set, the New Zealand Attitudes and Values Study (N = 9,269). Māori (the Indigenous group) expressed the highest levels of regard for the environment on average, although there was also considerable variance among Māori as a group. Study 2 adopted an emic perspective to investigate which dimensions of Māori identity are related to higher environmental value specifically among Māori (N = 193). Bayesian regression indicated that sociopolitical consciousness—the extent to which participants recognize the importance of and stand up for Māori political rights—was linked with higher environmental regard. Contrary to predictions, belief in Māori spiritual concepts was not linked with increased environmental regard. These findings suggest that Māori tend to value the natural environment more than non-Indigenous New Zealanders at least in part because high environmental regard is central to Māori political consciousness. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: environment; environmental attitudes; ethnic identity; identity; land protection; spirituality

The prevalence and impact of racism toward indigenous Māori in New Zealand - Houkamau, Carla A.; Stronge, Samantha; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2017)
Intolerance toward indigenous people is a common feature of colonial societies, and New Zealand is no exception. Despite aspirations of equality, evidence suggests that discrimination toward Māori remains pervasive and may relate to continued inequalities in social, economic, and psychological domains. This article analyzes self-report questionnaire data from 1,790 Māori sampled as part of the New Zealand Attitudes and Values Study. We describe a Bayesian regression model assessing the links between perceived discrimination and 15 social, economic, and psychological indicators of well-being (including health care access, evaluation of own health, job security, self-esteem, life satisfaction, and psychological distress). The model adjusts for relevant covariates (including age, ethnicity, gender, and income). Forty-three percent of the sample reported experiencing either some discrimination or high levels of discrimination. Higher levels of perceived discrimination among Māori were associated with poorer outcomes in every measure, across multiple domains. This study demonstrates that New Zealand’s “bi-cultural” aspirations are far from realized, and should raise concerns for all countries with a history of colonisation. We call for more research on the incidences and impact of various forms of discrimination throughout New Zealand society, specifically in relation to the perpetuation of Māori disadvantage. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: discrimination; racism; wellbeing

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting

New Zealand’s Waitangi Day divided? Support for national Day predicts in-group and out-group warmth for Pākehā but only in-group warmth for Māori - Matika, Correna M.; Houkamau, Carla A.; Sibley, Chris G. (International Journal of Intercultural Relations, 2021)
Waitangi Day, New Zealand’s official national day, is often claimed as contentious by commentators and academics. However, research analysing the wider population’s opinions about Waitangi Day are lacking. We address this with two studies using national probability data from the New Zealand Attitudes and Values Study. Most participants supported (51%), rather than opposed (8%), Waitangi Day as a national celebration of biculturalism. Study one indicated that, on average, Pākehā (N = 12390) who opposed Waitangi Day as a bicultural celebration expressed warmer attitudes towards Pākehā but colder attitudes towards Māori. Conversely, support for Waitangi Day as a bicultural celebration among Māori (N = 1928) was, on average, related to warmth towards Māori but uncorrelated with warmth towards Pākehā. Study two assessed whether socio-political attitudes changed in the weeks leading up to, during, and immediately following Waitangi Day in 2015. Contrary to narratives of divisiveness, we failed to detect reliable change in the attitudes of Māori (N = 556) and Pākehā (N = 3203) around Waitangi Day. These findings are inconsistent with anecdotal claims that Waitangi Day may be divisive.
Keywords: Waitangi Day; commemoration; national day; tiriti o waitangi/treaty of waitangi

Exploring the relationship between support for protest and psychological well-being for Māori - Houkamau, Carla A; Stronge, Samantha; Osborne, Danny; Sibley, Chris G; Dell, Kiri (New Zealand Journal of Psychology, 2020)
As a colonised peoples, many Māori have engaged in various forms of political resistance. Accordingly, research suggests that socio-political consciousness, which will sometimes involve at least considering protest, is an increasingly important aspect of identifying as Māori. This paper draws on a large, nationally representative sample of Māori (N = 1,977) to examine the links between expressing support for political activism (“activism” being used here synonymously with “protest”) and well-being. Support for political activism includes merely contemplating protesting and voting to support Māori issues, as well as actually signing petitions. Well-being includes selfreported mental health via the Kessler-6 and subjective health. Results show that support for political activism was strongly associated with greater subjective psychological distress and lower subjective health, above and beyond the variance explained by exhaustive demographic factors. This research presents the first empirical data in New Zealand demonstrating the strength of this relationship, and provides a good starting point for further investigation.
Keywords: activism; protest

Being Present: Embodying Political Relations in Indigenous Encounters with the Crown - Hoskins, Te Kawehau; Bell, Avril (Contemporary Political Theory, 2021)
Political encounters between settler governments and indigenous communities are freighted with the unresolved issues of indigenous independence asserted under ongoing conditions of colonial domination. Within political science, these encounters have been primarily theorised and analysed as struggles of indigenous communities for political recognition from settler states. Further, the politics of recognition is widely understood as colonising by indigenous scholars, with some arguing for an alternative politics of (indigenous) resurgence and refusal, a ‘turning away’ from the state. In this article, we argue that in the case of Ma¯ori in Aotearoa ‘turning up’ is the ethical and correct practice of politics, a practice stemming from the relational ontology of the Ma¯ori world. Thus ‘turning up’ rather than ‘turning away’ can, for Ma¯ori, itself be a practice of refusal. We outline the centrality of the embodied, face-to-face encounter within Ma¯ori politics, and identify the ongoing presence of the sovereign’s body and embodiment more broadly within the Westminster tradition, as symbolised in the concept of the Crown. Building on these compatibilities within distinct political ontologies, we argue for the potential and productivity of face-to-face political encounters, and call on the New Zealand Crown to also prioritise ‘turning up’ in its engagement with indigenous communities.
Keywords: kāwanatanga; rangatiratanga; self-determination

Indigenous Māori values and perspectives to inform freshwater management in Aotearoa-New Zealand - Harmsworth, Garth; Awatere, Shaun; Robb, Mahuru (Ecology and Society, 2016)
In response to widespread water quality and quantity issues, the New Zealand Government has recently embarked on a number of comprehensive freshwater management reforms, developing a raft of national discussion and policy documents such as "Freshwater Reform 2013 and Beyond" and a National Policy Statement for freshwater management (NPS-FM 2014). Recent resource management reforms and amendments (RMA 2014), based on previous overarching resource management legislation (RMA 1991), set out a new approach and pathway to manage freshwater nationwide. Internationally, there is an increasing trend to engage with indigenous communities for research and collaboration, including indigenous groups as active participants in resource management decision making. What is driving this change toward more engagement and collaboration with indigenous communities is different for each country, and we document the progress and innovation made in this area in New Zealand. The indigenous rights of Māori in New Zealand are stated in the 1840 Treaty of Waitangi and in many forms of New Zealand's legislation. Local and central governments are eager to include local indigenous Māori groups (iwi/hapū) in freshwater management planning processes through meaningful engagement and collaboration. Key to the success of collaborative planning processes for Māori are enduring relationships between local government and Māori, along with adequate resourcing for all partners contributing to the collaborative process. A large number of shared governance and management models for natural resource management have emerged in New Zealand over the past 20 years, and some recent examples are reviewed. We provide some discussion to improve understanding and use of the terms used in these management models such as cogovernance, comanagement, and coplanning, and describe some of the more important frameworks and tools being developed with Māori groups (e.g., iwi/hapū), to strengthen Māori capacity in freshwater management and to support good collaborative process and planning.
Keywords: co-governance; environment; hapū; iwi; kāwanatanga; local government; mātauranga māori; resource management; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; water management

From hydrology to policy development and implementation: Trends in Aotearoa New Zealand's freshwater management and governance - Fenemor, Andrew; Kirk, Nicholas; Harmsworth, Garth; Taylor, Lara; Weir, Julian; Robson, -Williams Melissa (Journal of Hydrology (New Zealand), 2021)
This section reviews changes to water management and governance in the past ten years. We open with a summary of Aotearoa New Zealand's historical legislative context in regard to rivers, catchments and freshwater resources. We describe the roles of local government, Maori and central government. We detail the growing recognition of tangata whenua values in water management alongside belated development of national policy direction on water quality and allocation. Drawing on the description of modelling advances, we summarise how models are being used in contemporary water management. Finally, we review the implementation of freshwater policy and the integration of science and water policy. In concluding, we argue that integration and implementation challenges must be addressed as hydrologists look beyond 2021 towards future significant legislative changes affecting water and catchment management nationwide.
Keywords: environmental management; policy making; water management

Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand’s land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.
Keywords: co-governance; land policy; policy; water management

A Māori perspective of being and belonging - Rameka, Lesley (Contemporary Issues in Early Childhood, 2018)
Belonging and being are inextricably linked. From a M?ori perspective, belonging and being can be viewed through a number of interconnected historical and contemporary frames. One frame is derived from M?ori perceptions of the creation of the universe and genealogical relationships to the universe and everything in it. Another frame of belonging and being stresses increasingly diverse and complex positionings that require negotiation of radically different terrains of assumptions, behaviours, values and beliefs. This article explores two interrelated aspects of being and belonging from a M?ori perspective: whakapapa (?genealogical connections?) and whanaungatanga (?family relationships?). It discusses how each aspect has changed over time as a result of colonisation, urbanisation and western education, and identifies how the reflection of each has been transformed.
Keywords: belonging; colonisation; education; urbanisation; whakapapa; whanaungatanga

Unfolding tensions within post-settlement governance and tribal economies in Aotearoa New Zealand - Mika, Jason Paul; Smith, Graham Hingangaroa; Gillies, Annemarie; Wiremu, Fiona (Journal of Enterprising Communities: People and Places in the Global Economy, 2019)
Purpose This paper aims to examine indigenous governance and economies of iwi Maori (Maori tribes) in Aotearoa New Zealand. Research into persisting inequities amongst iwi that have settled treaty claims and the potential for intervention through new governance models and indigenous entrepreneurship contextualise the paper. Design/methodology/approach Kaupapa Maori (Maori philosophy) is used as an indigenous methodology to facilitate and empower transformative change, underpinned by Maori knowledge, language and culture. A multi-level approach is used to collect data from international, national and local tribal organisations. Validity is established through stakeholder engagement. Findings A central challenge in the post-treaty settlement context is exponentialising tribal capabilities because of the multiple purposes ascribed to post-settled iwi. Four themes, characterised as “unfolding tensions”, offer a critique and basis for solving tribal development challenges: how do tribes create culturally grounded global citizens; how do tribes rebalance wealth creation and wealth distribution; how do tribes recalibrate tribal institutions; and how do tribes embed entrepreneurship and innovation within their economies? Research limitations/implications As data collection is still underway, the paper is conceptual. Practical implications Five strategies to address unfolding tensions are identified for tribes to consider. Social implications Tribal governors and tribal members are implicated in the analysis, as well as the architects of post-treaty settlement governance models. Originality/value The paper contributes to theorising about tribal governance, economies and entrepreneurship.
Keywords: colonisation; indigenous economics; indigenous entrepreneurship; indigenous governance; mana motuhake; māori economies; post-settlement (waitangi tribunal); tribal development

Indigenous environmental defenders in Aotearoa New Zealand: Ihumātao and Ōroua River - Mika, Jason Paul; Dell, Kiri; Elers, Christine; Dutta, Mohan; Tong, Qing (AlterNative: An International Journal of Indigenous Peoples, 2022)
This article theorises the question?what is the role and nature of Indigenous environmental defenders in Aotearoa New Zealand? We explore M?ori?the Indigenous people of Aotearoa New Zealand?who act as environmental defenders of their lands and waters despite the perpetual insecurity of their constitutional rights and imbalances in power and resources compared with state and corporate actors. The environmental defence of Aotearoa New Zealand by M?ori began with the arrival of European explorers? intent on overturning Indigenous institutions of environmental management that has sustained their peoples for a thousand years. Stemming from case study analysis of M?ori environmental defenders at Ihum?tao in M?ngere and ?roua River in Manawat?, we propose whenua (land) resilience theory to explain the concomitance of environmental defence and development from an Indigenous perspective.
Keywords: colonisation; environment; kaitiakitanga; land protection

Whose citizenship anyway? - Godfery, Morgan (set: Research Information for Teachers, 2016)
Keywords: belonging; citizenship; education

A Seat At The Table - Winter, Christine J. (Borderlands Journal, 2021)
Abstract Aotearoa New Zealand acknowledges mātauranga Māori in the two Acts and one Memorandum of Understanding recognising the ‘personhood’ status of three geographical regions—Te Awa Tupua, Te Urewera and Taranaki Maunga. They blend the legal fiction of corporate personhood with the already always understanding of human-nonhuman kinship and entanglement of M!ori philosophy, Māori knowledge and wisdom, and Māori epistemology. Through kaitiaki (trustees) these three entities have volition in their ongoing maintenance, development negotiations, and ‘land-use’, and ‘the rights, powers, duties and liabilities of a legal person’. These attributes suggest something more than mere volition in self-management and protection: they suggest agency. This article explores the implications of nonhuman agency as potential for political voice. As representatives of entanglement for all being—animal (including human), vegetable and elemental—and as a matter of justice they are, perhaps, obliged to participate in democracy and the nation is, perhaps, obliged to give them a ‘seat at the table’. As political agents with equal status to human and corporate persons Te Awa Tupua, Te Urewera and Taranaki Maunga might unsettle settler politics and challenge the imbalances of the Anthropocene.
Keywords: decolonisation; democracy

The Role of Emotion in Understanding Whiteness - Borell, Belinda (Journal of Bioethical Inquiry, 2021)
This paper argues that stoicism as a central element of whiteness shapes, controls, and ultimately limits the experience and expression of emotion in public space. I explore how this may play out in particular medical settings like hospitals in Aotearoa New Zealand. I argue that working in conjunction with other values of whiteness identified by Myser (2003)—hyper-individualism, a contractual view of relationships, and an emphasis on personal control and autonomy—this makes hospitals emotionally unsafe spaces for Māori and other groups who place high importance in the collective sharing of emotion. Using death and bereavement as an example, I suggest that challenging and addressing stoicism in the structure and performance of whiteness in hospital settings may provide an important point of entry for anti-racism measures and health equity.
Keywords: colonisation; health; healthcare; identity; racism; white privilege

Decolonising Dignity for Inclusive Democracy - Winter, Christine J. (Environmental Values, 2019)
Gale Academic OneFile includes Decolonising Dignity for Inclusive Democracy by Christine J. Winter. Click to explore.
Keywords: decolonisation; dignity; environment; mana party; mauri; tapu

Anti-Maori themes in New Zealand journalism–toward alternative practice - Moewaka Barnes, Angela; Borell, Belinda; Taiapa, Ken; Rankine, Jenny; Nairn, Ray; McCreanor, Tim (Pacific Journalism Review, 2012)
Gale Academic OneFile includes Anti-Maori themes in New Zealand journalism–toward alt by Angela Moewaka Barnes, Belinda Borell, . Click to explore.
Keywords: health; media; privilege; racism; representation; wellbeing

"It's Hard at the Top but It's a Whole Lot Easier than Being at the Bottom:" The Role of Privilege in Understanding Disparities in Aotearoa/New Zealand - Borell, Belinda A. E.; Gregory, Amanda S.; McCreanor, Tim N.; Jensen, Victoria G. L.; Moewaka Barnes, Helen E. (Race/Ethnicity: Multidisciplinary Global Contexts, 2009)
Objective: An initial exploration of the available conceptualizations of privilege in Aotearoa/New Zealand with the goal of developing a more in-depth qualitative study, incorporating kaupapa Maori and public health framings. Design: Interviews were conducted with a purposive sample of key informants that span the academic, community development, health service provision, and activist sectors. Participants were selected from multiple networks for their expressed interest and insight into the concept of privilege and its importance to analyses of social justice. Results: Six key themes emerged that include the invisibility of privilege; the weighting of different variables; individual vs group privilege; class; the active aspects of privilege; and links between privilege and Pakeha culture. Conclusion: Participants' constructions of privilege emphasize the multifaceted complexity and discursive ambiguities of the ways in which the concept is utilized within our political economy to account for disparity and covertly reproduce the status quo of Pakeha advantage.
Keywords: disparities; privilege

Conceptualising historical privilege: the flip side of historical trauma, a brief examination - Borell, Belinda; Moewaka Barnes, Helen; McCreanor, Tim (AlterNative: An International Journal of Indigenous Peoples, 2018)
Historical trauma is an important and growing area of research that provides crucial insights into the antecedents of current-day inequities in health and social wellbeing experienced by Indigenous people in colonial settler societies. What is not so readily examined is the flip side of historical trauma experienced by settlers and their descendants, what might be termed ?historical privilege?. These historic acts of privilege for settlers, particularly those emigrating from Britain, provide the antecedents for the current-day realities for their descendants and the structural, institutional and interpersonal levels of advantage that are also a key feature of inequities between Indigenous and settler. This article theorises an explicit link between historical trauma and historical privilege and explores how the latter may be examined with particular reference to Aotearoa New Zealand. Three core elements of historical trauma are posited as a useful framework to apply to historical privilege.
Keywords: colonisation; trauma

He Kōrero Whānau o Te Rarawa - Henwood, Wendy; Pirini, Jasmine; Harris, Aroha (MAI Review, 2010)
He Kōrero Whānau is a component of a wider whānau and hapū development project within Te Rarawa, an iwi located in the Far North of Aotearoa. It aimed to prepare and support whānau and hapū to record their own histories, and in doing so to develop research methods and strategies to suit Te Rarawa purposes and realities. The innovation of the approach is the inclusion of oral and life histories in any interview-based research Te Rarawa might undertake, and the training of community interviewers in the skills of research and oral history interviews. The approach is grounded in iwi and hapū development and responsive to needs and aspirations. It also works to demystify research and focuses on research making a difference in Te Rarawa communities. This paper discusses our experience of developing Te Rarawa research methods and applying them in ways that harmonise with the goals of Te Rarawa iwi development.
Keywords: rangatiratanga; unsure if politics

Concurrent Narratives of Maori and Integration in the 1950s and 60s - Harris, Aroha (Journal of New Zealand Studies, 2008)
Maori and government policies of integration in the 1950s and 60s by accessing two concurrent narratives are discussed. The two narratives are the narrative of the state embedded in a one-size-fits-all Maori policy, and the narratives of the Maori 'business of life'.
Keywords: crown policy; social conditions; urbanisation

Reconciliation, Representation and Indigeneity: 'Biculturalism' in Aotearoa New Zealand - Harris, Aroha (The Journal of New Zealand Studies, 2017)
Reconciliation, Representation, and Indigeneity begins with the claim that it ‘offers an up-to-date analysis of the reconciliation process between Māori and the Crown’ (7). The editors do not stop at up-to-date analysis. They push the edited collection of thirteen essays that were once conference papers into more complicated territory, inviting a range of ontologies, nestled in the links between ‘contemporary politics, the notion of activist research and historical and anthropological analysis’ (7). This introduction seemed a lot for me to take in, though I fully appreciated the intellectual care the editors took as they combed through the argument, organisation, themes, and academic approaches and positions of the book.
Keywords: kāwanatanga

Empowering Equitable Data Use Partnerships and Indigenous Data Sovereignties Amid Pandemic Genomics - Haring, Rodney C.; Blanchard, Jessica W.; Korchmaros, Josephine D.; Lund, Justin R.; Haozous, Emily A.; Raphaelito, Josie; Hudson, Maui; Tsosie, Krystal S. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has inequitably impacted Indigenous communities in the United States. In this emergency state that highlighted existing inadequacies in US government and tribal public health infrastructures, many tribal nations contracted with commercial entities and other organization types to conduct rapid diagnostic and antibody testing, often based on proprietary technologies specific to the novel pathogen. They also partnered with public-private enterprises on clinical trials to further the development of vaccines. Indigenous people contributed biological samples for assessment and, in many cases, broadly consented for indefinite use for future genomics research. A concern is that the need for crisis aid may have placed Indigenous communities in a position to forego critical review of data use agreements by tribal research governances. In effect, tribal nations were placed in the unenviable position of trading short-term public health assistance for long-term, unrestricted access to Indigenous genomes that may disempower future tribal sovereignties over community members' data. Diagnostic testing, specimen collection, and vaccine research is ongoing; thus, our aim is to outline pathways to trust that center current and future equitable relationship-building between tribal entities and public-private interests. These pathways can be utilized to increase Indigenous communities' trust of external partners and share understanding of expectations for and execution of data protections. We discuss how to navigate genomic-based data use agreements in the context of pathogen genomics. While we focus on US tribal nations, Indigenous genomic data sovereignties relate to global Indigenous nations regardless of colonial government recognition.
Keywords: indigenous data sovereignty

First Nations, Maori, American Indians, and Native Hawaiians as Sovereigns: EAP with Indigenous Nations Within Nations - Haring, Rodney C.; Hudson, Māui; Erickson, Louisa; Taualii, Maile; Freeman, Bonnie (Journal of Workplace Behavioral Health, 2015)
Indigenous workforces have existed across the world since the creation of Earth. What has changed is the evolution of multicultural societies, governments, and landscapes that have become part of, or sit parallel to, sovereign Indigenous nations and their workforces. An international response to Employee Assistance Programming (EAP) and workplace health will be shared from various Indigenous groups across the globe. These societies include the Maori of New Zealand, First Nations of Canada, American Indian groups from the U.S. mainland, and Native Hawaiians. Guidelines for EAP practice include the discussion of historical trauma, communication skills, confidentiality, and environmental issues. Theoretical underpinnings for health sovereignty are shared through ancient teachings of Indigenous philosophies and their relationships to contemporary EAP development and utilization.
Keywords: indigenous data sovereignty; native americans

'Pissed Off and Confused'/'Grateful and (Re)Moved': Affect, Privilege and National Commemoration in Aotearoa New Zealand - McConville, Alex; Wetherell, Margaret; McCreanor, Tim; Borell, Belinda; Moewaka Barnes, Helen (Political Psychology, 2020)
This article explores affect, colonial privilege, and the cultural politics of national commemoration in Aotearoa New Zealand. Based on focus‐group interviews around two major national days, we examine means through which feelings and emotions are deployed in ways that enable the reproduction of social advantage. Situating affect within patterns of relationship, four interrelated affective‐discursive practices are explored. In relation to Waitangi Day, agents tend to work under the rubric of anger and confusion. For Anzac Day, being grateful and moved shapes the interaction, although participants often indicate preferences towards "having a day off." Given the colonial context in which these practices circulate, analysis observes the associated freedom and ease by which affective‐discursive privilege is (re)produced. Often incongruent and rarely challenged, privilege allows associated actors to do what they want, when they want, however they want. This affective climate authorizes the ongoing reproduction of, and justification for, membership to a higher‐status ethnic group of which unearned opportunities and entitlements remain its everyday, expected currency.
Keywords: colonisation; memorialisation; national identity; white privilege

Beyond the veil: Kaupapa Māori gaze on the non-Māori subject - Borell, Belinda; Waru Rewiri, Kura Te; Moewaka Barnes, Helen; McCreanor, Tim (Journal of Sociology, 2020)
Kaupapa M?ori methodologies in Aotearoa New Zealand have often been applied to content of immediate and direct relevance to M?ori communities. Some of these include research about aspects of cultural revitalisation or examinations of the position M?ori occupy within broader ethnic disparities, particularly in health and social outcomes. This article seeks to expand the application of Kaupapa M?ori paradigms to research topics outside ?te ao Maori? (the M?ori world). We argue that the Kaupapa M?ori theorising of a M?ori visual arts and culture scholar can provide crucial insights on white privilege in Aotearoa New Zealand with a view to addressing disparities and creating more embracing and equitable perspectives of belonging, citizenship and nationhood.
Keywords: belonging; citizenship; identity; kaupapa māori

Decolonisation starts in a name: Moving on from the colonial pretence that 'Maori' or 'indigenous peoples' are explanatory frames - MacDonald, Lindsey Te Ata o Tu (Political Science, 2016)
This article examines why and how scholars should acknowledge and name each of the diverse political actors and institutions that typically are objectified as ‘indigenous peoples’ on the global stage, or ‘Māori’ in New Zealand. For instance, rather than suggesting a political relationship or conflict exists between ‘Māori and the Crown’, political scientists and theorists should name the political actors and political institutions for which Māori is a shorthand, for example, ‘Te Runanga o Ngai Tahu (the corporate entity of the Ngai Tahu whanui) and the Committee of Tuahiwi Marae disagreed with the Crown’. A variety of reasons are discussed as to why this objectification of Māori (and any other indigenous population) as a single political actor has occurred, the problems are pointed out, and a range of examples are given. Not every use of the terms ‘Māori’, ‘indigenous peoples’ or similar descriptors in political science stands in for a specific political actor (e.g. sometimes, it is suggesting a cleavage or a group at whom a policy is directed), but where scholars are describing or suggesting political action, they should be careful in their use of ethnic labels. I suggest that it would be more productive to study the specific contexts, intentions and actions of individuals and institutions that might consider indigeneity as being part of their identity.
Keywords: decolonisation; mana wāhine; self-determination

The diverse stories of Māori political agency: a Q method study - Sheed, Toni; MacDonald, Lindsey Te Ata o Tu (Political Science, 2017)
While there is much research and writing on Māori self-determination, little of it focuses on how Māori individuals and organisations conceive the necessary antecedent to self-determination; Māori political agency. To remedy this research gap, we explored the political aspirations of Māori individuals with a research method built to study such subjective topics: Q method. Combining Q method with some practical innovations from Kaupapa Māori Research method, we developed a unique way of researching the stories our participants tell themselves about politics. Our results suggest some Māori individuals do think of politics as a collective endeavour as the self-determination literature suggests, but just as often Māori collective forums and other non-Māori political institutions are seen as barriers to Māori individual and collective political agency and thus to Māori self-determination. We also found that Māori view the political autonomy and participation necessary for self-determination as possible in numerous diverse spaces, suggesting the focus on low voter turnout amongst Māori in the literature is missing the point: the stories told by this research suggest Māori individuals perceive their political agency to be hindered, not by majoritarian politics of non-Māori, but by Māori and non-Māori elites.
Keywords: mana motuhake; political agency; self-determination; tino rangatiratanga

Theorising representation in the Māori seats: The crucial role of accountability - Nissen, Sylvia; MacDonald, Lindsey Te Ata o Tu (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
The guaranteed Mäori seats are a distinguishing and controversial feature of New Zealand’s democracy. In recent years, a number of reports, commentators and politicians have called for the seats to be abolished on the grounds that they are no longer “needed” in New Zealand’s proportional electoral system. These claims are usually grounded in principles of equality. This paper makes the opposite claim: that principles of equality create convincing and coherent justifications for the Mäori seats. Drawing on feminist theories of representation, particularly the work of Iris Marion Young, Melissa Williams and Anne Phillips, this paper argues that the Mäori seats provide crucial mechanisms of accountability that ensure the fidelity of Mäori representatives to their constituencies. This notion of accountability has been largely absent in debates about the Mäori seats and challenges arguments against the seats that are based solely on perceived “need” relative to proportionate presence.
Keywords: equality; identity; representation

(C)ELSI‐us: Reducing friction with indigenous communities in genomic research - Hudson, Maui; Wilcox, Phillip; Smith, Barry; Beaton, Angela; Milne, Moe; Russell, Khyla (American Anthropologist, 2018)
As government policy settings have become more responsive to aspirations of Indigenous communities and researchers are more sensitive to the concerns of Indigenous communities, the research environment has become more conducive to understanding the cultural implications of genomic research. CELSI-us is a tongue-in-cheek reference to taking the temperature of the relationship between genomic researchers and Indigenous communities. If we create friction, then the temperature rises. But if we engage in a culturally responsive manner, then we take the heat out of the relationship and can focus on achieving mutually beneficial outcomes. This has been the focus of our work to date, and we hope that the guidelines we have produced make this challenging path easier for others to traverse.
Keywords: data; indigenous data

Enacting Kaitiakitanga: Challenges and Complexities in the Governance and Ownership of Rongoa Research Information - Boulton, Amohia; Hudson, Māui; Ahuriri-Driscoll, Annabel; Stewart, Albert (The International Indigenous Policy Journal, 2014)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: data; indigenous data sovereignty; kaitiakitanga; rangatiratanga

Indigenous Perspectives and Gene Editing in Aotearoa New Zealand - Hudson, Maui; Mead, Aroha Te Pareake; Chagné, David; Roskruge, Nick; Morrison, Sandy; Wilcox, Phillip L.; Allan, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2019)
Gene editing is arguably the most significant recent addition to the modern biotechnology toolbox, bringing both profoundly challenging and enabling opportunities. From a technical point of view the specificity and relative simplicity of these new tools has broadened the potential applications. However, from an ethical point of view it has re-ignited the debates generated by earlier forms of genetic modification. In New Zealand gene editing is currently considered genetic modification and is subject to approval processes under the Environmental Protection Authority (EPA). This process requires decision makers to take into account Māori perspectives. This article outlines previously articulated Māori perspectives on genetic modification and considers the continuing influence of those cultural and ethical arguments within the new context of gene editing. It also explores the range of ways cultural values might be used to analyse the risks and benefits of gene editing in the Aotearoa New Zealand context. Methods used to obtain these perspectives consisted of (a) review of relevant literature regarding lessons learned from the responses of Maori to genetic modification, (b) interviews of selected ‘key Maori informants’ and (c) surveys of self-selected individuals from groups with interests in either genetics or environmental management. The outcomes of this pilot study identified that while Māori informants were not categorically opposed to new and emerging gene editing technologies a priori, they suggest a dynamic approach to regulation is required where specific uses or types of uses are approved on a case by case basis. This study demonstrates how the cultural cues that Māori referenced in the genetic modification debate continue to be relevant in the context of gene editing but that further work is required to characterize the strength of various positions across the broader community.
Keywords: data; indigenous data sovereignty

Let the people decide? Support for referenda since the New Zealand flag change referendums - Greaves, Lara M.; Oldfield, Luke D.; Milne, Barry J. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
The number of referenda taking place in established democracies has been increasing, but oftentimes the use of referenda is controversial. This paper utilises two New Zealand national probability mail surveys collected before (2015; n = 901) and after (2016; n = 1350) the controversial flag change referendums initiated by Prime Minister John Key. We found that support for referenda increased from 54.5% in 2015 to 70.7% in 2016. We examined how demographics, party vote, political attitudes, and support for changing the flag related to change in support for referenda Younger age groups and those with moderate levels of education had larger increases in support for referenda. We did not find any evidence of ‘loser effects’ as National voters and flag change supporters were just as likely to increase in support for referenda as other voters and those opposing change, respectively. In summary, the results of this paper show that despite controversy, referenda have become more popular, especially among certain groups.
Keywords: democracy; flag referendums; political disaffection; referendum

Indigenous ‘stakeholders’? Theorising external citizenship rights for Māori in Australia - West, Kiri (MAI Journal 2015, 2015)

Maori identity and "political arithmetick" : the dynamics of reporting ethnicity - Kukutai, Tahu (2022)
Thesis (M. Soc.Sc. Demography)–University of Waikato, 2001. Includes bibliographical references (leaves 193-203)
Keywords: crown policy; ethnic identity; ethnicity

Contemporary Issues in Māori Demography - Kukutai, Tahu (Maori and Social Issues, 2012)
Contemporary Issues in Māori Demography
Keywords: census; demographic aspects; identification; identity

Does the Domestic Violence Act discriminate against Māori? - Hook, Gary E. R. (MAI review, 2009)
Attempts to establish a measure of Māori domestic violence over the last 27 years by using data from the Statistics New Zealand database, looking at the records concerning only convictions for violent crimes. Seeks to get a picture of just how serious Māori domestic violence is compared with that of the Pākehā. Considers the role of unemployment and the influence of government policy and legislation. Suggests the possibility of discriminatory application of the law against Māori by the courts that deal with domestic violence issues. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: crown policy; discrimination; family violence; legislation; statistics

White Mothers, Brown Children: Ethnic Identification of Maori-European Children in New Zealand - Kukutai, Tahu H (Journal of Marriage and Family, 2007)
Studies of multiethnic families often assume the ethnic identification of children with the minority group results from the minority parent. This study examines an alternate view that mainstream parents also play an important role in transmitting minority ethnicity. It explores this argument using data from New Zealand on the ethnic labels mothers assign to their Maori-European children. It finds that European mothers are just as disposed as Maori mothers to designate their child as Maori, either exclusively or in combination. Two explanations, grounded in ethnic awareness and gendered inheritance, are proposed. Although neither satisfactorily predicts maternal designation decisions, the readiness of European mothers to identify their child as Maori underscores their role in diffusing Maori ethnicity.
Keywords: ethnic identity; ethnicity; interethnic marriage

The relevance of Te Tiriti o Waitangi in the COVID-19 era - Charters, Claire (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; governance; rangatiratanga; tiriti o waitangi/treaty of waitangi

The future of Māori health is here – The 2022 Aotearoa New Zealand health reforms - Ahuriri-Driscoll, Annabel; Lovell, Sarah; Kawa, Deborah Te; MacDonald, Lindsey Te Ata o Tū; Mathias, Kaaren (The Lancet Regional Health – Western Pacific, 2022)
Keywords: health; healthcare system; rangatiratanga

Alternative models of ethical governance: The 2016 new Brunswick-Otago declaration on research ethics - Gontcharov, Igor; MacDonald, Lindsey (New Zealand Sociology, 2016)
The current model of ethical governance in research involving humans in the social sciences and humanities relies on prospective ethics review in ensuring that research in conducted ethically. One of its key features is distrust to researchers and their initiatives regardless of the subject matter, discipline, research methodology or settings, sources of funding, or researcher's experience. This article discusses the New Brunswick Declaration on Research Ethics adopted by the participants of the Ethics Rupture: Alternatives to Research-Ethics Review Summit in 2013. In particular, it provides background for the regulatory capture of the social sciences by the biomedical institutions of ethics review. It concludes by examining the limitations of the Declaration, and offers a set of principles for the development of the New Brunswick Declaration following its discussion at the Ethics in Practice: Tensions around Ethics Review and Maori Consultation Conference at the University of Otago in Dunedin in May 2015.
Keywords: ethics; ethics committees; health; indigenous research ethics

Globalisation, neo-liberalism and the struggle for indigenous citizenship - MacDonald, Lindsey Te Ata o Tu; Muldoon, Paul (Australian Journal of Political Science, 2006)
Using indigenous citizenship as a frame, the article examines the deeply ambiguous effects of globalisation for indigenous peoples in the Antipodes. We demonstrate that processes of economic globalisation have had an impact upon New Zealand Maori and Australian Aboriginals in ways that have heightened their vulnerability and undermined their citizenship entitlements. However, we also argue that Maori and Aboriginal peoples have used the reforms of state practice brought about by globalisation to gain greater control over their existence.

Cultural Well-being and Local Government: Lessons from New Zealand - Dalziel, Paul; Matunga, Hirini; Saunders, Caroline (The Australasian Journal of Regional Studies, 2006)
Reforms of local government legislation in the United Kingdom (2000) and in New Zealand (2002) both introduced well-being powers. The UK reform gave local government a new power to promote social, economic and environmental well-being, but New Zealand added a fourth dimension - cultural well-being. This paper examines the background to New Zealand's 'quadruple bottom line' approach. It explains that it was the result of policymakers in New Zealand grappling for 25 years with the question of how to give effect to what the Town and Country Planning Act 1977 described as 'the relationship of the Maori people and their culture and traditions with their ancestral lands'. New Zealand's legislation requires a fully integrated approach by decision-makers using the well-being power, and the essay concludes with a discussion of how this has provided a forum for contests and compromises over cultural well-being to take place within a framework of democratic local decision-making by communities.
Keywords: assimilation; government relations; local government; sustainable development

New normal - Same inequities or engaged Te Tiriti partnership? - Kukutai, Tahu; McIntosh, Tracey; Moewaka Barnes, Helen; McCreanor, Tim (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; mātauranga māori; tiriti o waitangi/treaty of waitangi; treaty partnership; treaty-based relationships

Same inequities or engaged te tiriti partnership? - Kukutai, T.; McIntosh, T.; Moewaka Barnes, H.; McCreanor, T. (MAI Journal, 2020)
Keywords: community; covid-19; treaty obligations

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Indigenous data and health: critical research approaches and indigenous data governance - Reid, Papaarangi; Kukutai, Tahu; Cormack, Donna (European Journal of Public Health, 2018)
Background and objectives:‘Race’ and ethnicity data have become increasingly institutionalised within health research about indigenous peoples. While these data are critical to monitoring the differential distribution of risks and benefits in racialised societies, their uncritical and under-theorised use can perpetuate harmful biologically-deterministic and essentialist approaches to indigenous health. Additionally, indigenous rights and interests in data about us are often overlooked, with issues of indigenous data governance unresolved. The workshop objectives are to: Develop skills to critique uncritical use of ‘race’/ethnicity in indigenous health researchProvide examples from Aotearoa/New Zealand of frameworks or principles of indigenous data sovereignty
Keywords: data; health; indigenous data sovereignty

Tallying Tribes: Waikato-Tainui in the Census and Iwi Register - Walling, Julie; Small-Rodriguez, Desi; Kukutai, Tahu (2009)
In the last decade iwi have begun to shift their focus from challenging the state to developing internal capacity. In so doing, the need for accurate, relevant data on iwi populations has been amplified. Using Waikato-Tainui as a case study, we examine the potential gaps between the statistical needs of iwi in a postsettlement context and the official data available to them. Our analysis uses two time points: 1996, shortly after the raupatu settlement, and 2006, the most recent census. Comparing data from the Waikato-Tainui register with those from the 1996 and 2006 censuses, we find significant variation in the parameters and characteristics of Waikato-Tainui in official statistics versus the tribe’s own register. We discuss some of the implications of these gaps and suggest ways in which the statistical needs of iwi could be better met. Our key recommendation is that the existing iwi question in the census be expanded to prompt for tribal registration status. This change would better align official data with the concept of membership used by iwi authorities and yield data that are more relevant for their policy and planning needs.
Keywords: census; iwi; post-settlement (waitangi tribunal); waitangi tribunal

Statistics on indigenous peoples: International effort needed - Madden, Richard; Axelsson, Per; Kukutai, Tahu; Griffiths, Kalinda; Storm Mienna, Christina; Brown, Ngaire; Coleman, Clare; Ring, Ian (Statistical Journal of the IAOS, 2016)
In 2007, the UN General Assembly endorsed the United Nations Declaration on the Rights of Indigenous Peoples. In the following years, there has been a strong call from a range United Nations agencies and spokespersons for countries to act to improve their statistics relating to Indigenous peoples as part of their response to the Declaration. These calls have emphasised the need for a holistic approach, describing strengths and resilience of Indigenous peoples and not just a focus on gaps and disadvantage. National responses have been mixed and overall statistics remain inadequate. Signiﬁcantly, there has been no international statistical effort through the United Nations statistical structures to respond to the Declaration and the increasing array of calls for improved statistics. The United Nations Statistical Commission in particular has an array of mechanisms to study statistical needs and develop solutions across a broad international statistical agenda. It is time for countries to make a concerted effort to improve their own statistics on Indigenous peoples, and to insist that the Statistical Commission work in partnership with the Permanent Forum on Indigenous Issues and other stakeholders to lead a major international drive to improve statistics on and for Indigenous peoples.
Keywords: data; statistics

Addressing racism to eliminate Maori health inequity - Simmons-Donaldson, Lana; Cormack, Donna (Public Sector, 2021)
Lana Simmons-Donaldson speaks to University of Auckland Associate Professor Donna Cormack about the dire state of Maori health inequity and her thoughts on the government's health sector reforms.
Keywords: crown policy; government reforms; health inequity; racism

Census 2018 and Implications for Māori - Kukutai, Tahu; Cormack, Donna (New Zealand Population Review, 2018)
The population census is a universal tool of governance but has come under increasing pressure as governments look to reduce costs, gain efficiencies and counter declining response rates. In Aotearoa New Zealand, the census transformation strategy has a short-term focus on modernising the census and a long-term vision of a fully administrative census. The digital-first 2018 Census was an ambitious step towards modernisation but there are growing concerns that it may fail to deliver high-quality data, particularly for Māori and iwi. This research note considers the implications of lower response rates and reflects on the steps that might be taken to retain the trust and confidence of Māori in the census, including possibilities for Māori data governance across the official statistics system.
Keywords: census; data collection; governance; methodology; population; population studies; sovereignty; transformation

Understanding Maori 'lived' culture to determine cultural connectedness and wellbeing - Reid, John; Varona, Golda; Fisher, Martin; Smith, Cherryl (Journal of Population Research, 2016)
Maori tribal authorities have sought to measure the wellbeing of their people as a baseline for determining the extent to which their economic, social, and cultural goals are being achieved. In recent years, data from government-administered social surveys and/or censuses have become a significant source of information. Using the tribal authority of Te Runanga o Ngai Tahu (TRONT) as a case study, this paper explores and compares data concerning Ngai Tahu wellbeing contained in two recently completed TRONT reports: the Ngai Tahu State of the Nation 2015 report (a quantitative study derived from government-administered survey data); and, the preliminary findings from the Ngai Tahu Whenua Project (a qualitative study undertaken by TRONT). Both studies present similar results regarding levels of tribal economic wellbeing, however, they show different results in regards to levels of cultural wellbeing. The qualitative study reveals reasonably high levels of cultural engagement among participants. Conversely, the quantitative study demonstrates reasonably low levels of cultural engagement. The difference is explained in each study's approach to understanding culture. The quantitative study viewed culture as engagement in 'static' cultural practices, whereas the qualitative study viewed Maori culture as a 'lived' set of deep networks and connections between individuals, their whanau (extended family), and places of symbolic cultural importance (particularly land and water). It is argued that measuring 'lived' culture would provide a better means of ascertaining cultural wellbeing. It is suggested that a useful means of measuring Maori lived culture would be to determine the quality and depth of relational networks.
Keywords: colonisation; ethnicity; health; iwi; wellbeing

Towards a Social-Structural Model for Understanding Current Disparities in Maori Health and Well-Being - Reid, John; Taylor-Moore, Karyn; Varona, Golda (Journal of Loss and Trauma, 2014)
Colonization has resulted in Maori occupying a vulnerable position in New Zealand society. Comparatively poor health, along with complex social and economic problems, is a reflection of this fundamental insecurity. This article aims to put forward a historical and developmental perspective for understanding some of the current health disparities experienced by Maori, by exploring the concepts of historical trauma, loss of land, and alternative theories of development from post-development theory.
Keywords: colonisation; health; historical trauma; land loss

Whakatipu rawa ma ngā uri whakatipu: optimising the “Māori” in Māori economic development - Awatere, Shaun; Mika, Jason; Hudson, Maui; Pauling, Craig; Lambert, Simon; Reid, John (AlterNative: An International Journal of Indigenous Peoples, 2017)
One of the great challenges for indigenous and non-indigenous entrepreneurs in the twenty-first century is to move beyond profit maximisation as an acceptable modality for doing business and gravitate towards the concept of socially optimal outcomes, where maximising community well-being and minimising externalities to the natural environment and social justice are paramount. We present findings from a case-study analysis of M?ori enterprises that demonstrate a wealth of successfully kaupapa M?ori (M?ori ideology)-attuned strategy and policy. The case studies provide practical examples of the incorporation and expression of kaupapa M?ori values into strategy and policy of M?ori enterprises. We also identify the numerous challenges to implementing kaupapa M?ori in the management of M?ori Asset Holding Institutions and offer a way forward. Although the case studies are context specific, they provide some key principles and learning that can guide the greater uptake of kaupapa M?ori entrepreneurship.
Keywords: kaupapa māori; mahi; māori enterprise; māori entrepreneurship; policy

Returning the indigenous to the centre: a view from Aotearoa/New Zealand - DeSouza, Ruth; Cormack, Donna (Diversity in Health and Social Care, 2009)
Keywords: colonisation; discrimination; identity; māori rights; social aspects; social justice

COVID-19 and the mass incarceration of Indigenous peoples - King, Paula; Cormack, Donna; Keenan, Rawiri (Journal of Indigenous Social Development, 2020)
Similar to experiences of Indigenous peoples globally, Māori in the nation-state known as New Zealand (NZ) have been subjected to mass incarceration by the colonial state. Places of detention are dangerous environments for the spread of COVID-19. We are deeply concerned about the potential for disproportionate impacts of COVID-19 on Māori and other Indigenous peoples within these environments as many have health conditions and/or multiple comorbidities compounding the risks of severe illness and death from COVID-19. We call for the NZ government to honour te Tiriti o Waitangi obligations and uphold Indigenous rights contained within the United Nations Declaration on the Rights of Indigenous Peoples and other international rights instruments. A whole-of-government commitment to an equitable public health approach is required to: 1) rapidly reduce the numbers of Māori in sites of detention; 2) implement effective, timely, evidenced informed measures to reduce the risk of COVID-19, in line with World Health Organization recommendations; 3) prevent the torture and cruel, inhuman or degrading treatment or punishment of detained Māori during COVID-19; and, 4) eliminate double-celling. Although focused on NZ, the themes we highlight are likely of relevance for Indigenous peoples across the globe in our collective resistance to the COVID-19 pandemic.
Keywords: UNDRIP; covid-19; incarceration; racism; tiriti o waitangi/treaty of waitangi; treaty obligations

Māori experiences of multiple forms of discrimination: findings from Te Kupenga 2013 - Cormack, Donna; Harris, Ricci; Stanley, James (Kōtuitui: New Zealand Journal of Social Sciences Online, 2020)
Comprehensive exploration of Māori experiences of discrimination in Aotearoa New Zealand remains limited, particularly in relation to exposure to multiple and interlocking forms of discrimination. This paper presents findings from a secondary analysis of Te Kupenga 2013, the first Māori Social Survey, examining patterning and prevalence of different forms of discrimination for Māori (n = 5,549). Māori report experiencing multiple forms of discrimination, both over their lifetimes and within the last year. Although racial discrimination was the most commonly reported form, Māori also experience discrimination on the basis of other grounds including age, gender, and income. Māori also report exposure to multiple forms of discrimination. Discrimination occurred in a range of settings, with schools and workplaces common sites. The findings support the lived reality of Māori that racial and other forms of discrimination are pervasive, and experienced in multiple domains across the life course, representing a persistent breach of rights. It is critical that other forms of discrimination are measured alongside racism in order to understand and address the realities of multiple discrimination for Māori in Aotearoa New Zealand.
Keywords: discrimination; racism; te kupenga; treaty obligations

Challenges on the path to Treaty-based Local Government relationships - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
In this article I examine some of the challenges for Māori and Local Government on the path to Treaty-based Local Government relationships. I suggest significant challenges exist in three core areas. The first relates to the attitudes towards the ideas of Treaty-based Local Government and evident in common terminology which has a narrow focus on the identity of Māori as ‘representatives' rather than ‘Treaty partners’. The second area of challenge is in having Māori wards/constituencies established which, when they are established, are symbolically the beginnings of an acknowledgment of Treaty obligations and relationships. The third challenge is the lack of good data which limits understandings of Māori involvement in Local Government. In the second part of the article I ask whether any specific challenges can be seen that might impact on Treaty-based relationships in regard to Māori involvement as candidates and voters in Local Government elections.
Keywords: elections; local elections; local government; māori electorates; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty-based relationships; voting

For a tika transition: strengthen rangatiratanga - Bargh, Maria; Tapsell, Ellen (Policy Quarterly, 2021)
Examines two prominent environmental issues – sea level rise and taonga species protection – facing iwi, hapū, Māori and the Crown, exploring the barriers, solutions and positive steps in each area towards a ‘tika transition’ whereby iwi, hapū and Māori (the rangatiratanga sphere) and the Crown (kāwanatanga sphere) exist within distinct and equal political entities, with the rangatiratanga sphere leading and governing tikanga and mātauranga Māori policy and legislation. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: citizenship; climate change; co-governance; environment; environmental management; government relations; kāwanatanga; mātauranga māori; protection; rangatiratanga; sea level; taonga; tikanga | indigenous law

Does the crown minerals act undermine partnership with Maori? - Billington, Carl (Public sector (Wellington), 2022)
The Crown Minerals Act 1991 (CMA) was introduced "to promote prospecting for, exploration for, and mining of Crown owned minerals for the benefit of New Zealand". A series of fundamental questions has emerged as to whether the Act undermines the ability of the Crown and tangata whenua, anchored in Te Tiriti o Waitangi, to operate in a true sense of partnership. Carl Billington takes a closer look.
Keywords: crown lands; crown policy; land tenure; law; legislation; mines and mineral resources; mining law; tiriti o waitangi/treaty of waitangi; treaty obligations

Maori crown relationships: Working with IWI in ways that enhance capability - Bargh, Maria; Birch, Nicky (Public sector (Wellington), 2022)
The emphasis on strengthening Maori Crown relationships in the Public Service Act 2020 and the establishment of Te Arawhiti signalled a new era in the public service's interactions with tangata whenua. Carl Billington investigates whether this is changing the way public sector agencies approach their interactions with Maori.
Keywords: administration; crown; kāwanatanga; planning; project management

Fostering sustainable tribal economies in a time of climate change - Bargh, Maria; Douglas, Sarsha-Leigh; Te One, Annie (New Zealand geographer, 2014)
In this article, we explore how Māori tribal organisations are responding to calls by other Indigenous peoples to become more sustainable in a time of climate change. From a close examination of tribal Environmental Management Plans, we move to a specific case study in the Bay of Plenty area, Ngāti Kea/Ngāti Tuara. Ultimately, we suggest that many tribal organisations are seeking to respond to climate change and transition to becoming producers of their own food and energy needs, and are often articulating these responses in relation to specific local resources and contexts.
Keywords: climate change; economic aspects; environmental management; iwi; iwi development; sustainable development

Tino Rangatiratanga and Well-being: Māori Self Determination in the Face of Covid-19 - Te One, Annie; Clifford, Carrie (Frontiers in sociology, 2021)
The New Zealand government has been globally praised for its response to Covid-19. Despite the global accolades, little attention has been given to the swift and innovative Māori response to Covid-19. This paper will detail some of this rapid Māori response to Covid-19 in Aotearoa New Zealand and argue the response can be understood as key examples of Māori exercising tino rangatiratanga (self-determination), independent of the government's measures and policies. We suggest that this exploration of tino rangatiratanga during Covid-19 demonstrates central aspects of Māori well-being that move beyond a government focus on statistics as the key measure of well-being and how tikanga Māori (Māori values) are being used to develop successful responses to the global pandemic.
Keywords: covid-19; hauora; health; māori health; self-determination; sociology; tikanga | indigenous law; tino rangatiratanga

Mana motuhake ā-raraunga: datafication and social science research in Aotearoa - Kukutai, Tahu; Cormack, Donna (Kōtuitui: New Zealand Journal of Social Sciences Online, 2019)
Keywords: census; colonisation; data; ethics; statistics

Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.
Keywords: colonisation; covid-19; data; data sovereignty; inequity; racism; self-determination

Oh, you don’t look Māori: Socially assigned ethnicity. - Cormack, Donna; Borell, Belinda; Gillon, Ashlea (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2019)
Keywords: blood quantum; ethnic identity; ethnicity; identity; kaupapa māori; racism; white privilege

The relationship between socially-assigned ethnicity, health and experience of racial discrimination for Māori: analysis of the 2006/07 New Zealand Health Survey - Harris, Ricci B.; Cormack, Donna M.; Stanley, James (BMC Public Health, 2013)
In New Zealand, there are significant and long-standing inequalities in a range of health outcomes, risk factors and healthcare measures between Māori (indigenous peoples) and Pākehā (European). This study expands our understanding of racism as a determinant of such inequalities to examine the concept of socially-assigned ethnicity (how an individual is classified by others ethnically/racially) and its relationship to health and racism for Māori. There is some evidence internationally that being socially-assigned as the dominant ethnic group (in this case European) offers health advantage.
Keywords: discrimination; ethnic identity; ethnicity; health; identity; inequity; racism; trauma

The field of Indigenous health and the role of colonisation and history - Axelsson, Per; Kukutai, Tahu; Kippen, Rebecca (Journal of Population Research, 2016)
Keywords: Inequity; colonisation; disparities; displacement; health; health outcomes

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics

The Problem of Defining an Ethnic Group for Public Policy: Who is Māori and Why Does it Matter? - Kukutai, Tahu (Social Policy Journal of New Zealand, 2004)
Governments in multicultural democracies are increasingly being challenged to justify the collection of ethnic and racial data, and the targeted policies they support. Given mounting opposition to ethnicbased policies in New Zealand, it is timely to consider two questions that have arisen from ongoing debate. The first is what criteria ought to apply to determine who is Mäori for policy purposes. The second is which Mäori ought to benefit from targeted policies and programmes. This paper addresses both questions empirically and makes two suggestions: (1) that statistical and legal definitions of Mäori be amended to take account of both self-identified ethnicity and descent; (2) that programmes which seek to militate Mäori disadvantage be oriented towards those who strongly identify as Mäori, since they are the most likely to be in need.
Keywords: Inequity; data sovereignty; identity; policy; self-identification

‘Colonised by a rich pākehā’: the metaphorical characterisation of the Internet Mana alliance - Peters, Rachel; Hocking, Darryl (Media International Australia, 2022)
In 2014, the Internet Mana alliance unsuccessfully ran in the New Zealand general election gaining just 1.42% of the party vote and failing to secure an electorate seat. The leaders of the alliance attributed their poor election result to the narratives constructed by the mainstream media, which they believed negatively influenced the public?s perception of Internet Mana. This study agrees that the mainstream media was complicit in the alliance?s poor election result, and drawing upon the discourse dynamics framework for metaphor analysis, it shows how these potentially damaging public narratives were predominantly constituted through complex sets of systematic metaphors which together created broader schematic frames or conceptual scenarios and carried certain evaluative and attitudinal perceptions. This analysis shows how systematic metaphors such as the internet mana alliance is a marriage of convenience and the internet mana alliance is a colonial trade were used to construct a negative public narrative.
Keywords: colonisation; elections; mainstream media; political parties

The geography of deprivation in New Zealand by electorate - Exeter, Daniel J.; Crengle, Sue; Cavadino, Alana; Greaves, Lara; Zhao, Jinfeng; Lee, Arier; Browne, Michael (Kōtuitui: New Zealand Journal of Social Sciences Online, 2018)
In the run-up to the 2017 General Election, the economy, housing, health, education, inequality and justice were important policy issues. General Elections are a time when voters exercise their democratic right to vote for their preferred party and parliamentary candidate to represent themselves, their whānau and community. In many cases, political parties’ policies seek to improve the wellbeing of people who are living in more deprived communities, but people in deprived communities are typically less likely to vote. The recently released New Zealand Index of Multiple Deprivation (IMD) enables users to explore deprivation in electorates across the country. This paper compares the distribution of deprivation and voter turnout across a selection of General Electoral Districts (GEDs) and demonstrates that while overall patterns of deprivation may be similar between GEDs, the drivers of these patterns can differ immensely.
Keywords: Inequity; disparities; elections; electorates; voter turnout

Decolonizing politics with insights from Indigenous Studies - Bargh, Maria (Identities, 2022)
Keywords: colonisation; decolonisation; education; mātauranga māori; rangatiratanga; tikanga | indigenous law

Colonisation, hauora and whenua in Aotearoa - Moewaka Barnes, Helen; McCreanor, Tim (Journal of the Royal Society of New Zealand, 2019)
Colonisation has deeply harmed Maori communities, seriously and consistently undermining their vitality, aspirations and potentials, particularly since the 1860s, at inestimable cost to the entire nation. The British arrival in Aotearoa commenced a relationship between two very different peoples that has profoundly influenced their distinct and collective fortunes ever since. Despite manifest breaches of te Tiriti o Waitangi, this relationship has centred settler interests ensuring that Maori sovereignty has been displaced in favour of colonial hegemony, entrenching longstanding, preventable inequities in health and other important domains of social life. In this paper we trace some broad indicators of relational health and wellbeing in Aotearoa and consider how Maori thinking about whenua, health and wellbeing might lead healing opportunities for people and whenua. We outline ways in which a unified, dynamic, relational Maori concept based on whenua as the determinant of health could contribute. We believe this could expand, strengthen and revitalise prevention, protection and promotion approaches, to counter the injustices of colonisation, contribute toward health equity and move toward just, sustainable shared futures for the benefit of all New Zealanders.
Keywords: colonisation; disparities; hauora; health; policy; regeneration; social determinants; sovereignty; tiriti o waitangi/treaty of waitangi; whenua